Lithium secondary battery and non-aqueous electrolyte solution used therein
By using a positive electrode and an anode of specific compositions, combined with a nonaqueous electrolyte of a specific compound, the problem of high output and long life of lithium secondary batteries in large applications is solved, especially the discharge characteristics are significantly improved under low temperature conditions.
Patent Information
- Application Number
- CN202510122565.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2006-01-27
- Filing Date
- 2006-10-19
- Publication Date
- 2025-04-11
AI Technical Summary
Existing lithium secondary batteries are difficult to meet the requirements of high output and long life in large applications, especially in poor discharge characteristics under low temperature conditions.
A positive electrode and an anode with specific composition and physical properties are used to combine a nonaqueous electrolyte with a specific compound to form a lithium secondary battery with high capacity, long life and high output.
It realizes the demand for high output and long life of lithium secondary batteries in large applications, and maintains excellent discharge characteristics under low temperature conditions.
Smart Images

Figure CN119812477A_ABST
Abstract
Description
[0001] This application is a divisional application of an application filed on October 19, 2006, with application number 202110646170.7 and invention name “Lithium secondary battery and non-aqueous electrolyte used therein”. Technical Field
[0002] The present invention relates to lithium secondary batteries and non-aqueous electrolytes used therein, and more particularly to lithium secondary batteries having a non-aqueous electrolyte containing specific components, and a positive electrode and a negative electrode having specific composition and physical properties capable of absorbing and releasing lithium, and in particular to lithium secondary batteries having excellent low-temperature discharge characteristics, high capacity, long life, and high output, and the non-aqueous electrolytes used therein. Background Art
[0003] In recent years, with the miniaturization of electronic devices, the demand for higher capacity secondary batteries has been increasing, and lithium secondary batteries, which have higher energy density than nickel-cadmium batteries and nickel-metal hydride batteries, have attracted attention.
[0004] Since lithium secondary batteries are high-capacity secondary batteries, they can be used in various applications, but they are mainly used in relatively small batteries such as mobile phones. It is expected that their application will be expanded in large batteries such as those for automobiles in the future. In large batteries, there is a particular demand for output, and simply making the previous small batteries larger is not sufficient in terms of performance. In addition, various methods for improving battery materials for increasing output have been proposed (for example, see Patent Documents 1 to 25, Non-Patent Document 1, etc.). However, sufficient output is still not obtained, and further improvement is required.
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2005-071749
[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 2005-123180
[0007] Patent Document 3: Japanese Patent Application Laid-Open No. 2001-206722
[0008] Patent Document 4: Japanese Patent Application Laid-Open No. 2003-267732
[0009] Patent Document 5: Japanese Patent Application Laid-Open No. 2001-015108
[0010] Patent Document 6: WO2003 / 34518
[0011] Patent Document 7: Japanese Patent Application Laid-Open No. 11-067270
[0012] Patent Document 8: Japanese Patent Application Laid-Open No. 61-168512
[0013] Patent Document 9: Japanese Patent Application Laid-Open No. 6-275263
[0014] Patent Document 10: Japanese Patent Application Laid-Open No. 2000-340232
[0015] Patent Document 11: Japanese Patent Application Laid-Open No. 2005-235397
[0016] Patent Document 12: Japanese Patent Application Laid-Open No. 11-031509
[0017] Patent Document 13: Japanese Patent Application Laid-Open No. 3-055770
[0018] Patent Document 14: Japanese Patent Application Publication No. 2004-071458
[0019] Patent Document 15: Japanese Patent Application Publication No. 2004-087459
[0020] Patent Document 16: Japanese Patent Application Laid-Open No. 10-270074
[0021] Patent Document 17: Japanese Patent Application Publication No. 2002-075440
[0022] Patent Document 18: Japanese Patent Application Laid-Open No. 10-270075
[0023] Patent Document 19: Japanese Patent Application Laid-Open No. 8-045545
[0024] Patent Document 20: Japanese Patent Application Laid-Open No. 2001-006729
[0025] Patent Document 21: Japanese Patent Application Laid-Open No. 10-050342
[0026] Patent Document 22: Japanese Patent Application Laid-Open No. 9-106835
[0027] Patent Document 23: Japanese Patent Application Publication No. 2000-058116
[0028] Patent Document 24: Japanese Patent Application Publication No. 2001-015158
[0029] Patent Document 25: Japanese Patent Application Publication No. 2005-306619
[0030] Non-patent document 1: J. Electrochem. Soc., 145, L1 (1998) Summary of the Invention
[0031] Problems to be solved by the invention
[0032] The present invention has been made in view of the above background technology, and an object of the present invention is to provide a lithium secondary battery having high capacity, long life, and high output even when it is made larger.
[0033] Solutions to Problems
[0034] The present inventors have conducted in-depth research on the above-mentioned issues and found that by using a positive electrode and a negative electrode with specific composition and physical properties, and a non-aqueous electrolyte containing a compound selected from a specific group, a high-capacity, long-life, and high-output lithium secondary battery can be obtained, thereby completing the present invention.
[0035] That is, the present invention provides a lithium secondary battery comprising at least: an electrode group consisting of a positive electrode and a negative electrode with a microporous membrane separator sandwiched therebetween, and a non-aqueous electrolyte solution containing a lithium salt in a non-aqueous solvent, which are housed in a battery case, wherein:
[0036] The positive electrode and the negative electrode each form an active material layer on a current collector, the active material layer containing an active material capable of occluding and releasing lithium ions;
[0037] The non-aqueous electrolyte contains at least one compound selected from the following substances, the content of which in the entire non-aqueous electrolyte is 10 ppm or more, the substances including:
[0038] A cyclic siloxane compound represented by the following general formula (1):
[0039] [Chemical Formula 1]
[0040]
[0041] [In the general formula (1), R 1 and R 2 They may be the same or different and represent an organic group having 1 to 12 carbon atoms, and n represents an integer of 3 to 10.]
[0042] A fluorosilane compound represented by the following general formula (2),
[0043] [Chemical Formula 2]
[0044] SiF x R 3 p R 4 q R 5 r (2)
[0045] [In general formula (2), R 3 ~R 5 They may be the same or different, and represent an organic group having 1 to 12 carbon atoms, x represents an integer of 1 to 3, p, q, and r each represent an integer of 0 to 3, and 1≤p+q+r≤3.]
[0046] The compound represented by the following general formula (3),
[0047] [Chemical Formula 3]
[0048]
[0049] [In general formula (3), R 6 ~R 8 may be the same or different, and represent an organic group having 1 to 12 carbon atoms, and A represents a group composed of H, C, N, O, F, S, Si and / or P.], and
[0050] Compounds with SF bonds within their molecules, nitrates, nitrites, monofluorophosphates, difluorophosphates, acetates, and propionates;
[0051] Furthermore, the positive electrode is any one selected from the following positive electrodes [1] to [5]:
[0052] Positive electrode [1]: A positive electrode comprising a positive electrode active material containing manganese;
[0053] Positive electrode [2]: A positive electrode comprising a positive electrode active material having a composition represented by the following composition formula (4):
[0054] Li x Ni (1-y-z) Co y M z O2 composition formula (4)
[0055] [In composition formula (4), M represents at least one element selected from Mn, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn, and Nb, x represents a number satisfying 0 < x ≤ 1.2, y represents a number satisfying 0.05 ≤ y ≤ 0.5, and z represents a number satisfying 0.01 ≤ z ≤ 0.5.];
[0056] Positive electrode [3]: a positive electrode comprising any one of the positive electrode active materials selected from the following (a) to (d),
[0057] (a) BET specific surface area is 0.4 m 2 / g~2m 2 / g of positive electrode active material
[0058] (b) Positive electrode active material with an average primary particle size of 0.1 μm to 2 μm
[0059] (c) Median particle size d 50 Positive electrode active material with a diameter of 1μm to 20μm
[0060] (d) Tap density is 1.3 g / cm 3 ~2.7g / cm 3 positive electrode active material;
[0061] Positive electrode [4]: a positive electrode that satisfies any one of the following conditions (e) to (f),
[0062] (e) A positive electrode produced by forming a positive electrode active material layer containing a positive electrode active material, a conductive material, and a binder on a current collector, wherein the content of the conductive material in the positive electrode active material layer is in the range of 6% by mass to 20% by mass
[0063] (f) A positive electrode is prepared by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector, wherein the density of the positive electrode active material layer is 1.7 g / cm 3 ~3.5g / cm 3 Range
[0064] (g) a positive electrode produced by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector, wherein the ratio of the thickness of the positive electrode active material layer to the current collector (the thickness of the active material layer on one side before injection of the non-aqueous electrolyte) / (the thickness of the current collector) is 1.6 to 20;
[0065] Positive electrode[5]: A positive electrode containing two or more positive electrode active materials with different compositions.
[0066] The present invention also provides a lithium secondary battery comprising at least: an electrode group formed by sandwiching a microporous membrane separator between a positive electrode and a negative electrode, and a non-aqueous electrolyte solution containing a lithium salt in a non-aqueous solvent, and these are housed in a battery case, wherein:
[0067] The positive electrode and the negative electrode each form an active material layer on a current collector, the active material layer containing an active material capable of occluding and releasing lithium ions;
[0068] The non-aqueous electrolyte contains at least one compound selected from the following substances, and the content of the compound in the entire non-aqueous electrolyte is 10 ppm or more, the substances including: a cyclic siloxane compound represented by the general formula (1), a fluorosilane compound represented by the general formula (2), a compound represented by the general formula (3), a compound having an SF bond in the molecule, a nitrate, a nitrite, a monofluorophosphate, a difluorophosphate, an acetate, and a propionate;
[0069] Furthermore, the negative electrode is selected from any one of the following negative electrodes [1] to
[10] :
[0070] Negative electrode[1]: A negative electrode containing two or more carbonaceous materials with different crystallinity as negative electrode active materials;
[0071] Negative electrode [2]: A negative electrode containing amorphous carbon as the negative electrode active material, wherein the amorphous carbon has a (002) plane spacing (d002) of 0.337 nm or more as measured by wide-angle X-ray diffraction, a crystallite size (Lc) of 80 nm or less, and a lattice density (C) of 1360 cm-1 as measured by argon ion laser Raman spectroscopy. -1 The peak intensity relative to 1580 cm -1 The Raman R value defined by the ratio of the peak intensities is greater than 0.2;
[0072] Negative electrode [3]: A negative electrode containing a metal oxide as a negative electrode active material, wherein the metal oxide contains titanium capable of occluding and releasing lithium;
[0073] Negative electrode [4]: A negative electrode containing a carbonaceous material as a negative electrode active material, wherein the circularity of the carbonaceous material is greater than 0.85 and the surface functional group O / C value is 0 to 0.01;
[0074] Negative electrode [5]: A negative electrode containing a hetero-oriented carbon composite as a negative electrode active material, wherein the hetero-oriented carbon composite contains two or more carbonaceous materials with different orientations;
[0075] Negative electrode [6]: A negative electrode containing graphite carbon particles as the negative electrode active material, wherein the circularity of the graphite carbon particles is greater than 0.85, the interplanar spacing (d002) of the (002) plane measured by wide-angle X-ray diffraction is less than 0.337nm, and the spectral density of the graphite carbon particles measured by argon ion laser Raman spectroscopy at 1360cm -1 The peak intensity relative to 1580 cm -1 The Raman R value, defined by the ratio of the peak intensities of is 0.12 to 0.8;
[0076] Negative electrode [7]: a negative electrode containing the following multi-element negative electrode active material (C) as a negative electrode active material, wherein the multi-element negative electrode active material (C) contains at least one lithium occluding metal (A) and / or lithium occluding alloy (B) selected from Al, Pb, Zn, Sn, Bi, In, Mg, Ga, Cd, Ag, Si, B, Au, Pt, Pd and Sb, and contains C and / or N as element Z;
[0077] Negative electrode[8]: A negative electrode containing two or more negative electrode active materials with different properties as negative electrode active materials;
[0078] Negative electrode[9]: Contains a tap density of 0.1g / cm 3 A negative electrode having a negative electrode active material having a micropore volume of 0.01 mL / g or more, which is equivalent to particles with a diameter of 0.01 μm to 1 μm, as measured by a mercury porosimeter;
[0079] Negative electrode
[10] : A negative electrode having a reaction resistance of 500Ω or less generated by the opposing battery of the negative electrode when charged to 60% of the nominal capacity of the negative electrode.
[0080] The present invention also provides a lithium secondary battery comprising at least: an electrode group consisting of a positive electrode and a negative electrode sandwiched between a microporous membrane separator, and a non-aqueous electrolyte solution containing a lithium salt in a non-aqueous solvent, which are housed in a battery case, wherein:
[0081] The positive electrode and the negative electrode each form an active material layer on a current collector, the active material layer containing an active material capable of occluding and releasing lithium ions;
[0082] The non-aqueous electrolyte contains at least one compound selected from the following substances, and the content of the compound in the entire non-aqueous electrolyte is 10 ppm or more, the substances including: a cyclic siloxane compound represented by the general formula (1), a fluorosilane compound represented by the general formula (2), a compound represented by the general formula (3), a compound having an SF bond in the molecule, a nitrate, a nitrite, a monofluorophosphate, a difluorophosphate, an acetate, and a propionate;
[0083] Furthermore, the non-aqueous electrolyte is an electrolyte that satisfies any one of the following conditions selected from electrolytes [1] to [9]:
[0084] Electrolyte [1]: The non-aqueous solvent constituting the electrolyte is a mixed solvent containing at least ethylene carbonate, and the proportion of ethylene carbonate relative to the total amount of the non-aqueous solvent is 1% by volume to 25% by volume;
[0085] Electrolyte [2]: The non-aqueous solvent constituting the electrolyte contains at least one asymmetric chain carbonate, and the asymmetric chain carbonate accounts for 5% to 90% by volume of the total non-aqueous solvent;
[0086] Electrolyte [3]: The non-aqueous solvent constituting the electrolyte contains at least one chain carboxylic acid ester;
[0087] Electrolyte [4]: The non-aqueous solvent constituting the electrolyte contains a solvent having a flash point of 70°C or higher, and its content is at least 60% by volume of the total non-aqueous solvent;
[0088] Electrolyte[5]: Contains LiN(C n F 2n+1 SO2)2 (wherein n is an integer of 1 to 4) and / or lithium di(oxalato)borate as lithium salts constituting the electrolyte;
[0089] Electrolyte [6]: The lithium salt constituting the electrolyte is a fluorine-containing lithium salt, and the entire non-aqueous electrolyte contains 10 ppm to 300 ppm of hydrogen fluoride (HF);
[0090] Electrolyte [7]: The electrolyte contains vinylene carbonate, wherein the content of the vinylene carbonate is in the range of 0.001% to 3% by mass of the total mass of the electrolyte;
[0091] Electrolyte [8]: The electrolyte further contains at least one compound selected from the group consisting of a compound represented by the following general formula (4), a heterocyclic compound containing nitrogen and / or sulfur, a cyclic carboxylic acid ester, and a fluorine-containing cyclic carbonate, wherein the content of the compound in the total non-aqueous electrolyte is in the range of 0.001% by mass to 5% by mass.
[0092] [Chemical Formula 4]
[0093]
[0094] [In general formula (4), R 9 ~R 12 may be the same or different and represent a group consisting of at least one element selected from H, C, N, O, F, S and P. ];
[0095] Electrolyte[9]: The electrolyte also contains an overcharge preventer.
[0096] Among the above-mentioned secondary batteries, a secondary battery having any one of the properties selected from the following (1) to (3) is particularly preferred.
[0097] (1) The area ratio of the total electrode area of the positive electrode to the surface area of the secondary battery casing is 20 times or more;
[0098] (2) The DC resistance component of the secondary battery is 20 milliohms (mΩ) or less;
[0099] (3) The battery element housed in one battery case of the secondary battery has a capacity of 3 ampere hours (Ah) or more.
[0100] The present invention also provides a lithium secondary battery comprising at least: an electrode group consisting of a positive electrode and a negative electrode sandwiched between a microporous membrane separator, and a non-aqueous electrolyte solution containing a lithium salt in a non-aqueous solvent, which are housed in a battery case, wherein:
[0101] The positive electrode and the negative electrode each form an active material layer on a current collector, the active material layer containing an active material capable of occluding and releasing lithium ions;
[0102] The non-aqueous electrolyte contains at least one compound selected from the following substances, and the content of the compound in the entire non-aqueous electrolyte is 10 ppm or more, the substances including: a cyclic siloxane compound represented by the general formula (1), a fluorosilane compound represented by the general formula (2), a compound represented by the general formula (3), a compound having an SF bond in the molecule, a nitrate, a nitrite, a monofluorophosphate, a difluorophosphate, an acetate, and a propionate;
[0103] Furthermore, the secondary battery has any one property selected from the following structures [1] to [6]:
[0104] Structure [1]: The area ratio of the total electrode area of the positive electrode to the surface area of the housing of the secondary battery is 20 times or more;
[0105] Structure [2]: The DC resistance component of the secondary battery is less than 20 milliohms (mΩ);
[0106] Structure [3]: The battery element contained in a battery housing of the secondary battery has a capacity of 3 ampere hours (Ah) or more;
[0107] Structure [4]: The current collectors of the positive electrode and the negative electrode of the secondary battery are respectively made of metal materials, and the metal materials of the current collectors and the conductor for extracting current to the outside are welded by any one method selected from slot welding, high-frequency welding, or ultrasonic welding;
[0108] Structure [5]: The outer shell of the secondary battery is aluminum or aluminum alloy;
[0109] Structure [6]: The shell material forming the battery shell of the secondary battery is the following shell material: at least a portion of the inner surface side of the battery contains a sheet formed using a thermoplastic resin, and while accommodating the battery pack, the battery pack can also be sealed by heat-sealing the thermoplastic resin layers to each other.
[0110] In addition, the present invention also provides a non-aqueous electrolyte for a secondary battery, the non-aqueous electrolyte comprising at least a non-aqueous solvent and a lithium salt, wherein:
[0111] The non-aqueous electrolyte contains at least one compound selected from the following substances, and the content of the compound in the entire non-aqueous electrolyte is 10 ppm or more, the substances including: a cyclic siloxane compound represented by the general formula (1), a fluorosilane compound represented by the general formula (2), a compound represented by the general formula (3), a compound having an SF bond in the molecule, a nitrate, a nitrite, a monofluorophosphate, a difluorophosphate, an acetate, and a propionate;
[0112] Furthermore, the non-aqueous electrolyte satisfies any one of the following conditions selected from electrolytes [1] to [9]:
[0113] Electrolyte [1]: The non-aqueous solvent constituting the electrolyte is a mixed solvent containing at least ethylene carbonate, and the proportion of ethylene carbonate relative to the total amount of the non-aqueous solvent is 1% by volume to 25% by volume;
[0114] Electrolyte [2]: The non-aqueous solvent constituting the electrolyte contains at least one asymmetric chain carbonate, and the asymmetric chain carbonate accounts for 5% to 90% by volume of the total non-aqueous solvent;
[0115] Electrolyte [3]: The non-aqueous solvent constituting the electrolyte contains at least one chain carboxylic acid ester;
[0116] Electrolyte [4]: The non-aqueous solvent constituting the electrolyte contains a solvent having a flash point of 70°C or higher, and the content of the solvent is 60% by volume or higher of the total non-aqueous solvent;
[0117] Electrolyte[5]: Contains LiN(C n F 2n+1 SO2)2 (wherein n is an integer of 1 to 4) and / or lithium di(oxalato)borate as lithium salts constituting the electrolyte;
[0118] Electrolyte [6]: The lithium salt constituting the electrolyte is a fluorine-containing lithium salt, and the entire non-aqueous electrolyte contains 10 ppm to 300 ppm of hydrogen fluoride (HF);
[0119] Electrolyte [7]: The electrolyte contains vinylene carbonate, and the content of the vinylene carbonate is in the range of 0.001% to 3% by mass of the total mass of the electrolyte;
[0120] Electrolyte [8]: The electrolyte further contains at least one compound selected from the group consisting of a compound represented by the general formula (4), a heterocyclic compound containing nitrogen and / or sulfur, a cyclic carboxylic acid ester, and a fluorine-containing cyclic carbonate, and the content of the compound in the total non-aqueous electrolyte is in the range of 0.001% by mass to 5% by mass;
[0121] Electrolyte[9]: The electrolyte also contains an overcharge preventer.
[0122] Effects of the Invention
[0123] According to the present invention, a lithium secondary battery having particularly excellent low-temperature discharge characteristics can be provided, and the following effects can be exerted, for example, by various aspects of the invention described below.
[0124] Positive electrode[1]:
[0125] According to the present invention, a long life and high output can be achieved with cheaper materials, and thus a lithium secondary battery particularly suitable for large batteries such as those used in automobiles can be provided.
[0126] Positive electrode[2]:
[0127] According to the present invention, a lithium secondary battery having high capacity, long life, and high output can be provided, and a lithium secondary battery particularly suitable for large batteries such as those used in automobiles can be provided.
[0128] Positive electrode[3]:
[0129] According to the present invention, a long-life, high-output lithium secondary battery can be obtained, and thus a lithium secondary battery particularly suitable for large batteries such as those used in automobiles can be provided.
[0130] Positive electrode[4]:
[0131] According to the present invention, a high-output lithium secondary battery can be obtained, and thus a lithium secondary battery particularly suitable for large batteries such as those used in automobiles can be provided.
[0132] Positive electrode[5]:
[0133] According to the present invention, a lithium secondary battery having high capacity, long life, and high output can be obtained, and the reduction in battery capacity and output caused by repeated charging and discharging of the battery is suppressed (excellent repeated charge and discharge characteristics (cycle characteristics)). Therefore, a lithium secondary battery particularly suitable for large batteries such as those used in automobiles can be provided.
[0134] Negative electrode[1]:
[0135] According to the present invention, a lithium secondary battery that is particularly suitable as a large battery can be provided. The lithium secondary battery can maintain the effect of improved cycle characteristics, and at the same time can maintain high output characteristics from the beginning to the end of the cycle. Even after deterioration after charge and discharge cycles, the output characteristics at high power can be maintained.
[0136] Negative electrode[2]:
[0137] According to the present invention, a lithium secondary battery having excellent short-time, high-current-density charge and discharge characteristics can be provided.
[0138] Negative electrode[3]:
[0139] According to the present invention, a lithium secondary battery having low output resistance and capable of efficiently utilizing energy can be provided.
[0140] Negative electrode[4]:
[0141] According to the present invention, a lithium secondary battery having improved high-temperature storage resistance at a low depth of charge can be provided.
[0142] Negative electrode[5]:
[0143] According to the present invention, a lithium secondary battery can be provided that maintains good performance even when repeatedly charged and discharged at a low depth of charge for a long period of time.
[0144] Negative electrode[6]:
[0145] According to the present invention, a lithium secondary battery can be provided that can quickly recover from a low output state at low temperatures.
[0146] Negative electrode[7]:
[0147] According to the present invention, it is possible to provide a lithium secondary battery having a large capacity even when made larger and having excellent charge acceptance.
[0148] Negative electrode[8]:
[0149] According to the present invention, a lithium secondary battery having excellent cycle characteristics and low-temperature output can be provided.
[0150] Negative electrode[9]
[10] :
[0151] According to the present invention, a lithium secondary battery can be provided which has a large cycle retention rate even when the battery is made larger, can achieve a good battery life, can achieve high output even after a charge and discharge cycle test, or both.
[0152] Electrolyte[1]:
[0153] According to the present invention, the low-temperature characteristics of a nonaqueous electrolyte secondary battery can be significantly improved. More specifically, the low-temperature characteristics can be improved without deteriorating the cycle characteristics and storage characteristics.
[0154] Electrolyte[2]:
[0155] According to the present invention, there can be provided a non-aqueous electrolyte solution for a secondary battery having significantly improved cycle characteristics and low-temperature characteristics, and a secondary battery using the non-aqueous electrolyte solution and having the above-mentioned excellent characteristics.
[0156] Electrolyte[3]:
[0157] According to the present invention, a non-aqueous electrolyte solution for a secondary battery and a secondary battery having significantly improved low-temperature output characteristics can be provided.
[0158] Electrolyte[4]:
[0159] According to the present invention, the following non-aqueous electrolyte for secondary batteries and secondary batteries can be provided: although the non-aqueous electrolyte for secondary batteries has an electrolyte composition with few problems caused by containing a large amount of low-viscosity solvent, such as salt precipitation due to evaporation of the solvent, or a decrease in the flash point, and an easy increase in internal pressure at high temperatures, it can still maintain high low-temperature characteristics and output characteristics.
[0160] Electrolyte[5]:
[0161] According to the present invention, a non-aqueous electrolyte solution for a secondary battery and a secondary battery can be provided which have significantly improved output characteristics and are excellent in high-temperature storage characteristics and cycle characteristics.
[0162] Electrolyte[6]:
[0163] According to the present invention, a non-aqueous electrolyte solution for a secondary battery can be provided which is excellent in high-temperature storage characteristics and cycle characteristics and has significantly improved output characteristics.
[0164] Electrolyte[7]:
[0165] According to the present invention, a secondary battery having significantly improved cycle characteristics and low-temperature characteristics can be provided.
[0166] Electrolyte[8]:
[0167] According to the present invention, a non-aqueous electrolyte solution for a secondary battery and a secondary battery can be provided which have significantly improved low-temperature discharge characteristics and are excellent in high-temperature storage characteristics and cycle characteristics.
[0168] Electrolyte[9]:
[0169] According to the present invention, a secondary battery that satisfies both high rate characteristics and safety during overcharge can be provided.
[0170] Structure [1] to [5]:
[0171] According to the present invention, a lithium secondary battery having high capacity, long life, high output, and high safety even during overcharge can be obtained, thereby providing a lithium secondary battery particularly suitable for large batteries such as those used in automobiles.
[0172] Structure[6]:
[0173] According to the present invention, a lithium secondary battery having high capacity, long life, high output, little gas generation, and high safety even when overcharged can be obtained. Therefore, a lithium secondary battery particularly suitable for large batteries such as those used in automobiles can be provided. DETAILED DESCRIPTION
[0174] The embodiments of the present invention will be described in detail below. However, the description of the constituent elements described below is an example (representative example) of the embodiments of the present invention, and the present invention is not limited to these specific contents unless exceeding the gist thereof.
[0175] The lithium secondary battery of the present invention comprises at least: an electrode group consisting of a positive electrode and a negative electrode sandwiched between a microporous membrane separator, and a non-aqueous electrolyte solution containing a lithium salt in a non-aqueous solvent, and these are housed in a battery case, wherein:
[0176] The positive electrode and the negative electrode each form an active material layer on a current collector, the active material layer containing an active material capable of occluding and releasing lithium ions;
[0177] The non-aqueous electrolyte contains at least one compound selected from the group consisting of the following substances (hereinafter referred to as "specific compounds"), and the content of the specific compound in the entire non-aqueous electrolyte is 10 ppm or more. The specific compound includes: a cyclic siloxane compound represented by the general formula (1), a fluorosilane compound represented by the general formula (2), a compound represented by the general formula (3), a compound having an SF bond in its molecule, a nitrate, a nitrite, a monofluorophosphate, a difluorophosphate, an acetate, and a propionate.
[0178] Furthermore, the positive electrode, negative electrode, electrolyte or battery structure meets specific conditions.
[0179] Next, the lithium secondary battery of the present invention will be described in more detail.
[0180] <positive electrode>
[0181] Next, the positive electrode used in the lithium secondary battery of the present invention will be described.
[0182] The positive electrode used in the present invention is not particularly limited as long as it forms an active material layer containing an active material capable of occluding and releasing lithium ions. The positive electrode is preferably selected from any one of the following positive electrodes [1] to [5]:
[0183] Positive electrode [1]: A positive electrode comprising a positive electrode active material containing manganese;
[0184] Positive electrode [2]: A positive electrode comprising a positive electrode active material having a composition represented by the following composition formula (4):
[0185] Li x Ni (1-y-z) Co y M z O2 composition formula (4)
[0186] [In composition formula (4), M represents at least one element selected from Mn, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn, and Nb, x represents a number satisfying 0 < x ≤ 1.2, y represents a number satisfying 0.05 < y ≤ 0.5, and z represents a number satisfying 0.01 ≤ z ≤ 0.5.];
[0187] Positive electrode [3]: a positive electrode comprising any one of the positive electrode active materials selected from the following (a) to (d),
[0188] (a) BET specific surface area is 0.4 m 2 / g~2m 2 / g of positive electrode active material
[0189] (b) Positive electrode active material with an average primary particle size of 0.1 μm to 2 μm
[0190] (c) Median particle size d 50 Positive electrode active material with a diameter of 1μm to 20μm
[0191] (d) Tap density is 1.3 g / cm 3 ~2.7g / cm 3 positive electrode active material;
[0192] Positive electrode [4]: a positive electrode that satisfies any one of the following conditions (e) to (f),
[0193] (e) The positive electrode is a positive electrode produced by forming a positive electrode active material layer containing a positive electrode active material, a conductive material and a binder on a current collector, wherein the content of the conductive material in the positive electrode active material layer is in the range of 6% by mass to 20% by mass.
[0194] (f) The positive electrode is a positive electrode prepared by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector, wherein the density of the positive electrode active material layer is 1.7 g / cm 3 ~3.5g / cm 3 Range
[0195] (g) The positive electrode is a positive electrode produced by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector, wherein the ratio of the thickness of the positive electrode active material layer to the current collector (the thickness of the active material layer on one side before injection of the non-aqueous electrolyte) / (the thickness of the current collector) is in the range of 1.6 to 20;
[0196] Positive electrode[5]: A positive electrode containing two or more positive electrode active materials with different compositions.
[0197] First, a positive electrode generally used in the lithium secondary battery of the present invention will be described below.
[0198] [Positive electrode active material]
[0199] Next, a description will be given of positive electrode active materials generally used in positive electrodes.
[0200] [[composition]]
[0201] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release lithium ions. Preferably, it contains lithium and at least one transition metal, for example, lithium-transition metal composite oxides and lithium-containing transition metal phosphates.
[0202] As the transition metal of the lithium-transition metal composite oxide, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples, lithium-cobalt composite oxides such as LiCoO2; lithium-nickel composite oxides such as LiNiO2; lithium-manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO3; and substances obtained by replacing part of the transition metal atoms forming the main body of these lithium-transition metal composite oxides with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, etc. Specific examples of the substances obtained by substitution include LiNi 0.5 Mn 0.5 O2、LiNi 0.85 Co 0.10 Al 0.05 O2、LiNi 0.33 Co 0.33 Mn 0.33 O2、LiMn 1.8 Al 0.2 O4、LiMn 1.5 Ni 0.5 O4, etc.
[0203] As the transition metal of the transition metal phosphate compound containing lithium, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples, there can be listed iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7; cobalt phosphates such as LiCoPO4; substances obtained by replacing part of the transition metal atoms that form the main body of these transition metal phosphate compounds containing lithium with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0204] [[Surface coating]]
[0205] In addition, it is preferred that a substance having a different composition from that of the core positive electrode active material is attached to the surface of these positive electrode active materials. Examples of the substance attached to the surface (hereinafter referred to as "surface-attached substance") include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; and carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate.
[0206] These surface-attaching substances can be attached to the surface of the positive electrode active material by the following methods, including: for example, a method of dissolving or suspending the surface-attaching substance in a solvent, then impregnating and adding it to the positive electrode active material and drying it; a method of dissolving or suspending a precursor of the surface-attaching substance in a solvent, then impregnating and adding it to the positive electrode active material, and then reacting it by heating or the like; a method of adding the surface-attaching substance to the precursor of the positive electrode active material and sintering it at the same time, etc.
[0207] The amount of surface-attached material, relative to the mass of the positive electrode active material, has a lower limit of preferably 0.1 ppm or greater, more preferably 1 ppm or greater, and even more preferably 10 ppm or greater; and an upper limit of preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less. Surface-attached material can inhibit the oxidation reaction of the non-aqueous electrolyte on the surface of the positive electrode active material, thereby improving battery life. However, if the amount of surface-attached material is too small, this effect is not fully demonstrated, while if it is too large, it may hinder the entry and exit of lithium ions, thereby increasing impedance.
[0208] [[shape]]
[0209] The particle shape of the positive electrode active material in the present invention can use the block, polyhedron, spherical, ellipsoidal, plate-like, needle-like, columnar, etc. used in the past, wherein, it is preferred that the primary particles condense to form secondary particles, and the shape of the secondary particles is spherical or ellipsoidal. Usually, as the electrochemical element is charged and discharged, the active material in the electrode expands and contracts, and it is easy to cause degradation such as destruction of the active material or cutting off of the conductive path due to the stress. Therefore, compared with a single particle active material that is only a primary particle, it is preferred that the primary particles condense to form secondary particles, because the formation of secondary particles can alleviate the stress of expansion and contraction, thereby preventing degradation. In addition, compared with plate-like equiaxially oriented particles, spherical or ellipsoidal particles are preferred, because spherical or ellipsoidal particles have less orientation when the electrode is formed, and the expansion and contraction of the electrode during charge and discharge are also less, and when mixing with the conductive agent when making the electrode, it is also easy to mix evenly.
[0210] [[Tap density]]
[0211] The tap density of the positive electrode active material is usually 1.3 g / cm 3 Above, preferably 1.5 g / cm 3 More than 1.6 g / cm 3 Above, most preferably 1.7 g / cm 3Above. If the tap density of the positive electrode active material is lower than the above lower limit, the amount of dispersion medium required for forming the positive electrode active material layer increases, and the necessary amount of conductive material or binder increases, the filling rate of the positive electrode active material in the positive electrode active material layer is restricted, and the battery capacity is sometimes restricted. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. Generally speaking, the larger the tap density, the more preferred, and there is no particular upper limit. However, if the tap density is too large, the diffusion of lithium ions in the positive electrode active material layer with a non-aqueous electrolyte as a medium becomes a factor that determines the speed, and the load characteristics are sometimes easily reduced. Therefore, the tap density is usually 2.9 g / cm 3 Below, preferably 2.7g / cm 3 Below, more preferably 2.5g / cm 3 the following.
[0212] In the present invention, the tap density is defined as follows: a sample is passed through a sieve with an aperture of 300 μm and falls to a depth of 20 cm. 3 After filling the container volume in a tapping cell, use a powder density meter (for example, Tap densor manufactured by Seishin Enterprise Co., Ltd.) to perform 1000 vibrations with a stroke length of 10 mm, and the density calculated from the volume at this time and the weight of the sample is used as the tap density.
[0213] [[Median particle size d 50 ]]
[0214] The median particle size d of the positive electrode active material particles 50 (When primary particles aggregate to form secondary particles, the secondary particle diameter is the secondary particle diameter) is usually 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and most preferably 3 μm or more. The upper limit is usually 20 μm or less, preferably 18 μm or less, more preferably 16 μm or less, and most preferably 15 μm or less. If the median particle size d 50 If the particle size is below the lower limit, a product with a high tap density may not be obtained. If the particle size is above the upper limit, the diffusion of lithium in the particles takes time, which may cause a decrease in battery performance. In addition, when the positive electrode of the battery is prepared, that is, when the active material and the conductive agent or binder are slurried in a solvent and then coated into a thin film, streaks may occur. 50 The positive electrode active material can further improve the filling property when making the positive electrode.
[0215] In addition, the median particle size d in the present invention is 50The particle size distribution can be measured using a known laser diffraction / scattering particle size analyzer. An LA-920 manufactured by HORIBA Corporation is used as the particle size distribution analyzer. A 0.1% by mass sodium hexametaphosphate aqueous solution is used as the dispersion medium for the measurement. After ultrasonic dispersion for 5 minutes, the measurement is performed at a refractive index of 1.24.
[0216] [[Average primary particle size]]
[0217] When the primary particles are condensed to form secondary particles, the average primary particle size of the positive electrode active material is usually 0.01 μm or more, preferably 0.05 μm or more, more preferably 0.08 μm or more, most preferably 0.1 μm or more, and usually 3 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and most preferably 0.6 μm or less. If the average primary particle size exceeds the above upper limit, it is difficult to form spherical secondary particles, which has an adverse effect on powder filling properties, or the specific surface area is greatly reduced. Therefore, the possibility of battery performance reduction such as output characteristics sometimes becomes higher. On the contrary, if the average primary particle size is lower than the above lower limit, it is usually due to incomplete crystallization, and therefore sometimes problems such as poor reversibility of charge and discharge are generated.
[0218] The primary particle size can be measured by observation using a scanning electron microscope (SEM). Specifically, the maximum value of the slice formed by the left and right boundaries of the primary particles on a straight line in the horizontal direction is obtained for 50 random primary particles in a photograph with a magnification of 10,000 times, and the average value is taken.
[0219] BET surface area
[0220] The BET specific surface area of the positive electrode active material provided to the lithium secondary battery of the present invention is usually 0.2 m 2 / g or more, preferably 0.3m 2 / g or more, more preferably 0.4m 2 / g or more, and its upper limit is usually 4.0m 2 / g or less, preferably 2.5m 2 / g or less, more preferably 1.5m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, while if the BET specific surface area is larger than this range, it is difficult to increase the tap density, which may cause problems in coating properties when forming the positive electrode active material.
[0221] The BET specific surface area is defined as the value measured by the nitrogen adsorption BET 1-point method using a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken) after pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas correctly adjusted to a relative pressure of 0.3 relative to atmospheric pressure.
[0222] [[Manufacturing method]]
[0223] As a method for producing a positive electrode active material, a common method for producing an inorganic compound is used. In particular, when producing a spherical or ellipsoidal active material, various methods can be considered, for example, the following methods: dissolving or crushing and dispersing a transition metal raw material such as a transition metal nitrate, a transition metal sulfate, and a raw material of other elements used as needed in a solvent such as water, adjusting the pH while stirring to produce and obtain a spherical precursor, drying it as needed, adding a Li source such as LiOH, Li2CO3, LiNO3, and sintering it at a high temperature to obtain an active material; dissolving or crushing and dispersing a transition metal raw material such as a transition metal nitrate, a transition metal sulfate, a transition metal hydroxide, a transition metal oxide, and a raw material of other elements used as needed A method in which a spherical or ellipsoidal precursor is prepared by drying and shaping it in a solvent such as water, and then adding a Li source such as LiOH, Li2CO3, or LiNO3 thereto and sintering it at a high temperature to obtain an active material; and a method in which a transition metal raw material such as a transition metal nitrate, a transition metal sulfate, a transition metal hydroxide, or a transition metal oxide and a Li source such as LiOH, Li2CO3, or LiNO3, as well as raw materials of other elements used as needed, are dissolved or crushed and dispersed in a solvent such as water, and then dried and shaped by a spray dryer to prepare a spherical or ellipsoidal precursor, and then sintering it at a high temperature to obtain an active material.
[0224] [Structure of the positive electrode]
[0225] Next, the structure of the positive electrode used in the present invention will be described.
[0226] [[Electrode structure and fabrication method]]
[0227] The positive electrode used in the lithium secondary battery of the present invention is made by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector. The manufacture of the positive electrode using the positive electrode active material can be carried out according to the usual method. That is, the positive electrode active material and the binder, as well as the conductive material and the thickener used as needed are dry-mixed to form a sheet, and the obtained sheet is pressed and bonded to the positive electrode collector, or these materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is then applied to the positive electrode collector and dried, thereby forming a positive electrode active material layer on the collector, thereby obtaining a positive electrode.
[0228] In the present invention, the content of the positive electrode active material in the positive electrode active material layer is usually 10% by mass or more, preferably 30% by mass or more, and particularly preferably 50% by mass or more. In addition, its upper limit is usually 99.9% by mass or less, preferably 99% by mass or less. If the content of the positive electrode active material powder in the positive electrode active material layer is very low, the capacitance sometimes becomes insufficient. On the contrary, if the content is too high, the strength of the positive electrode is sometimes insufficient. In addition, the positive electrode active material can be used alone or in combination with any combination and ratio. Two or more positive electrode active materials with different compositions or different powder properties can be used.
[0229] [[Compact]]
[0230] In order to increase the packing density of the positive electrode active material, the positive electrode active material layer obtained by coating and drying is preferably compacted using a manual press, a roller press, etc. The lower limit of the density of the positive electrode active material layer is preferably 1 g / cm 3 More than 1.5 g / cm 3 More than 2 g / cm 3 The upper limit is preferably 4 g / cm 3 Below, more preferably 3.5g / cm 3 Below, more preferably 3g / cm 3 If the range is exceeded, the permeability of the non-aqueous electrolyte to the interface of the current collector / active material is reduced, and the charge-discharge characteristics at high current density are sometimes reduced. In addition, if the range is lower than this, the conductivity between the active materials is reduced, and the battery impedance is sometimes increased.
[0231] Conductive materials
[0232] Any known conductive material can be used as the conductive material. Specific examples include metal materials such as copper and nickel; graphites such as natural graphite and artificial graphite; carbon blacks such as acetylene black; and carbon materials such as amorphous carbon such as needle coke. These materials may be used alone or in any combination and ratio.
[0233] The proportion of the conductive material used in the positive electrode active material layer is generally 0.01% by weight or more, preferably 0.1% by weight or more, more preferably 1% by weight or more, and its upper limit is generally 50% by weight or less, preferably 30% by weight or less, and more preferably 15% by weight or less. If the content is below this range, the conductivity may be insufficient. Conversely, if the content is above this range, the battery capacity may be reduced.
[0234] [[Adhesive]]
[0235] The binder used in manufacturing the positive electrode active material layer is not particularly limited. When a coating method is used, any material that can be dissolved or dispersed in the liquid medium used in electrode manufacturing can be used. Specific examples include resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as SBR (styrene-butadiene rubber), NBR (acrylonitrile-butadiene rubber), fluororubber, isoprene rubber, butadiene rubber, and ethylene-propylene rubber; and styrene-butadiene-styrene block copolymers. or their hydrogenated products, thermoplastic elastomer-like polymers such as EPDM (ethylene-propylene-diene terpolymer), styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, or their hydrogenated products; soft resin-like polymers such as syndiotactic 1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, and propylene-α-olefin copolymer; fluorinated polymers such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer; and polymer compositions having ion conductivity for alkali metal ions (particularly lithium ions). These substances may be used alone or in combination of two or more in any combination and ratio.
[0236] The ratio of the binder in the positive electrode active material layer is usually 0.1% by mass or more, preferably 1% by mass or more, more preferably 3% by mass or more, and its upper limit is usually 80% by mass or less, preferably 60% by mass or less, more preferably 40% by mass or less, and most preferably 10% by mass or less. If the ratio of the binder is too low, the positive electrode active material cannot be fully maintained, the mechanical strength of the positive electrode is insufficient, and the battery performance such as cycle characteristics deteriorates. On the other hand, if the ratio of the binder is too high, it sometimes leads to a decrease in battery capacity or conductivity.
[0237] Liquid medium
[0238] The liquid medium for forming the slurry is not particularly limited as long as it can dissolve or disperse the positive electrode active material, the conductive agent, the binder, and, if necessary, the thickener. Both aqueous solvents and organic solvents can be used.
[0239] Examples of aqueous media include water and mixed solvents of alcohols and water. Examples of organic solvents include aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; and aprotic polar solvents such as hexamethylphosphonamide and dimethyl sulfoxide.
[0240] Especially when using an aqueous solvent, it is preferred to use a latex of a thickener and styrene-butadiene rubber (SBR) etc. to slurry. The thickener is usually used to adjust the viscosity of the slurry. As the thickener, there is no particular limitation, specifically, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein and their salts etc. can be cited. They can be used alone or in any combination and ratio. Two or more kinds can be used in combination. In addition, when adding the thickener, the ratio of the thickener to the active material is usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 0.6% by mass or more, and its upper limit is usually 5% by mass or less, preferably 3% by mass or less, more preferably 2% by mass or less. If it is below this range, the coating property is sometimes significantly reduced. If it exceeds this range, the proportion of the active material in the positive electrode active material layer is reduced, sometimes resulting in a problem of reduced battery capacity or an increased impedance between the positive electrode active materials.
[0241] [[Current Collector]]
[0242] The material of the positive electrode current collector is not particularly limited, and any known material can be used. Specific examples include metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum; and carbon materials such as carbon cloth and carbon paper. Metal materials are preferred, with aluminum being particularly preferred.
[0243] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal film, expansion metal, perforated metal, foamed metal, etc. can be listed; in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be listed. Among these, metal film is preferred. In addition, the film can also be formed into a mesh shape as appropriate. The thickness of the film is arbitrary, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and is usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the film is thinner than this range, the necessary strength as a current collector may be insufficient. On the contrary, if the film is thicker than this range, the operability may be impaired.
[0244] The ratio of the thickness of the current collector and the positive electrode active material layer is not particularly limited, and (the thickness of the active material layer on one side before the non-aqueous electrolyte is injected) / (the thickness of the current collector) is preferably less than 150, more preferably less than 20, and most preferably less than 10, and its lower limit is preferably more than 0.1, more preferably more than 0.4, and most preferably in the range of more than 1. If it exceeds this range, the current collector sometimes generates heat due to Joule heat during high current density charge and discharge. If it is below this range, the volume ratio of the current collector to the positive electrode active material sometimes increases, and the capacity of the battery decreases.
[0245] [[Electrode area]]
[0246] When using the non-aqueous electrolyte of the present invention, from the viewpoint of high output and improved stability at high temperature, the area of the positive electrode active material layer is preferably larger than the outer surface area of the battery casing. Specifically, the sum of the electrode areas of the above-mentioned positive electrode is preferably 15 times or more, more preferably 40 times or more relative to the surface area of the shell of the secondary battery in terms of area ratio. The so-called outer surface area of the shell, in the case of a square shape with a bottom, refers to the total area calculated from the length, width and thickness of the shell part filled with the power generation element excluding the protruding part of the terminal. In the case of a cylindrical shape with a bottom, it is the geometric surface area obtained by approximating the shell part filled with the power generation element excluding the protruding part of the terminal to a cylinder. The so-called sum of the electrode areas of the positive electrode is the geometric surface area of the positive electrode composite material layer opposite to the composite material layer (composite material layer) containing the negative electrode active material. In the structure in which the positive electrode composite material layer is formed on both sides with the collector foil sandwiched, it refers to the sum of the areas of each face calculated separately.
[0247] Discharge capacity
[0248] When using the non-aqueous electrolyte for secondary batteries of the present invention, if the capacitance of the battery elements contained in the battery casing of one secondary battery (the capacitance when the battery is discharged from a fully charged state to a discharged state) is 3 ampere hours (Ah) or more, the effect of improving the low-temperature discharge characteristics becomes greater, so it is preferred.
[0249] Therefore, the positive plate is preferably designed to have a discharge capacity of 3 ampere hours (Ah) or more and less than 20Ah when fully charged, more preferably 4Ah or more and less than 10Ah. When less than 3Ah, when a large current is taken out, the voltage drop caused by the electrode reaction impedance becomes larger, and the power efficiency sometimes deteriorates. When more than 20Ah, although the electrode reaction impedance becomes smaller and the power efficiency becomes better, the temperature distribution caused by the internal heat of the battery during pulse charge and discharge is large, and the durability of repeated charge and discharge is poor. In addition, when the intense heat is generated during abnormalities such as overcharge or internal short circuit, its heat release efficiency also deteriorates, and the probability of the phenomenon (valve operation) of the internal pressure rising and the air release valve working and the phenomenon (rupture) of the battery contents being violently ejected to the outside is sometimes increased.
[0250] [[Thickness of the positive plate]]
[0251] The thickness of the positive electrode plate is not particularly limited, but from the viewpoint of high capacity and high output, the lower limit of the thickness of the composite material layer on one side of the collector after deducting the thickness of the metal foil of the core material is preferably 10 μm or more, more preferably 20 μm, and the upper limit is preferably 200 μm or less, more preferably 100 μm or less.
[0252] 〈Positive electrode[1]〉
[0253] Next, the positive electrode [1] “positive electrode comprising a positive electrode active material containing manganese” used in the lithium secondary battery of the present invention will be described.
[0254] [Positive electrode active material of positive electrode [1]]
[0255] Next, the positive electrode active material used in the positive electrode [1] is described.
[0256] [[composition]]
[0257] The positive electrode active material is a material containing a transition metal capable of electrochemically absorbing and releasing lithium ions. In the present invention, a positive electrode active material containing manganese as at least a portion of the transition metal is used. Preferably, the positive electrode active material further contains lithium, and more preferably, a composite oxide containing lithium and manganese.
[0258] The manganese-containing positive electrode active material is not particularly limited, but is preferably a positive electrode active material having a composition represented by the following composition formula (5).
[0259] Li x Mn (1-y) M 1 y O2 composition formula (5)
[0260] [In the composition formula (5), M 1represents at least one element selected from Ni, Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, and y represents a number satisfying 0.05≤y≤0.8].
[0261] In the composition formula (5), M 1 Ni, Co, and Fe are particularly preferred. In addition, x is particularly preferably 0.2≤x≤1.15, and y is particularly preferably 0.1≤y≤0.7. Specific examples of the material having the composition represented by the composition formula (5) include LiMn 0.5 Ni 0.5 O2.
[0262] In addition, M is particularly preferred 1 The positive electrode active material is Ni and has a composition represented by the following composition formula (6).
[0263] Li x Mn (1-y-z) Ni 1 y M 2 z O2 composition formula (6)
[0264] [In the composition formula (6), M 2 represents at least one element selected from Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, y represents a number satisfying 0.05≤y≤0.8, and z represents a number satisfying 0.01≤z≤0.5].
[0265] In the composition formula (6), M 2 Co, Al, Fe, and Mg are particularly preferred, x is particularly preferred to be 0.2≤x≤1.15, y is particularly preferred to be 0.1≤y≤0.7, z is particularly preferred to be 0.1≤z≤0.7, and y+z is particularly preferred to be 0.2≤y+z≤0.7. Specific examples of substances having a composition represented by composition formula (6) include LiMn 0.33 Ni 0.33 Co 0.33 O2, etc.
[0266] As the positive electrode active material containing manganese, a positive electrode active material having a composition represented by the following composition formula (7) is preferable.
[0267] Li x Mn (2-y) M 3 y O4 composition formula (7)
[0268] [In the composition formula (7), M 3represents at least one element selected from Ni, Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, and y represents a number satisfying 0.05≤y≤0.8].
[0269] In the composition formula (7), M 3 Ni, Co, Al, and Mg are particularly preferred. In addition, x is particularly preferably 0.05≤x≤1.15, and y is particularly preferably 0.1≤y≤0.7. Specific examples of the material having the composition represented by the composition formula (7) include LiMn 1.8 Al 0.2 O4、LiMn 1.5 Ni 0.5 O4, etc.
[0270] [[Surface coating]]
[0271] In addition, it is preferable to use a positive electrode active material having a substance having a composition different from that of the manganese-containing positive electrode active material attached to the surface of the positive electrode active material. The type, attachment method, and amount of the surface-attached substance are the same as those described above.
[0272] [[shape]]
[0273] The particle shape of the positive electrode active material is the same as described above.
[0274] [[Tap density]]
[0275] The tap density of the positive electrode active material is the same as above.
[0276] [[Median particle size d 50 ]]
[0277] The median particle size d of the positive electrode active material particles 50 (When primary particles aggregate to form secondary particles, the secondary particle diameter is the same as above.)
[0278] [[Average primary particle size]]
[0279] When the primary particles aggregate to form secondary particles, the average primary particle size of the positive electrode active material is the same as described above.
[0280] BET surface area
[0281] The BET specific surface area of the positive electrode active material is the same as above.
[0282] [[Manufacturing method]]
[0283] As a method for producing the positive electrode active material, a common method for producing an inorganic compound is used. In particular, when producing a spherical or ellipsoidal active material, various methods can be considered, for example, the following methods can be listed: dissolving or crushing a manganese raw material such as manganese nitrate, manganese sulfate, and raw materials of other elements used as needed in a solvent such as water, adjusting the pH while stirring to produce and obtain a spherical precursor, drying it as needed, adding a Li source such as LiOH, Li2CO3, LiNO3, and sintering it at a high temperature to obtain an active material; dissolving or crushing a manganese raw material such as manganese nitrate, manganese sulfate, manganese oxide, basic manganese hydroxide, and raw materials of other elements used as needed in a solvent such as water, A method in which a raw material of manganese such as manganese nitrate, manganese sulfate, manganese oxide, or basic manganese hydroxide and a Li source such as LiOH, Li2CO3, or LiNO3, as well as raw materials of other elements used as needed are dissolved or crushed and dispersed in a solvent such as water, and then dried and shaped by a spray dryer to form a spherical or ellipsoidal precursor, and then sintered at a high temperature to obtain an active material.
[0284] The positive electrode active material in the present invention may be the manganese-containing positive electrode active material alone, or may be a combination of the manganese-containing positive electrode active material and one or more positive electrode active materials having different compositions or powder properties from the manganese-containing positive electrode active material in any combination and ratio. Preferred combinations in this case include a combination of a manganese-containing positive electrode active material and a material obtained by replacing LiNiO2 or a portion of its Ni with other transition metals; or a combination of a manganese-containing positive electrode active material and a material obtained by replacing LiCoO2 or a portion of its Co with other transition metals. In addition, as particularly preferred combinations, a combination of a positive electrode active material represented by composition formulas (5) to (7) and a material obtained by replacing LiNiO2 or a portion of its Ni with other transition metals; or a combination of a positive electrode active material represented by composition formulas (5) to (7) and a material obtained by replacing LiCoO2 or a portion of its Co with other transition metals may also be mentioned. The manganese-containing positive electrode active material, especially the positive electrode active material represented by composition formulas (5) to (7), preferably accounts for 30% by mass or more of the total positive electrode active material, and more preferably 50% by mass or more. If the usage ratio of the positive electrode active material represented by composition formulae (5) to (7) is reduced, the cost of the positive electrode may not be reduced.
[0285] [Structure of positive electrode of positive electrode [1]]
[0286] Next, the structure of the positive electrode used in the positive electrode [1] is described.
[0287] The electrode structure and manufacturing method of the positive electrode [1], the compaction of the positive electrode active material layer, the conductive material, the binder used in the manufacture of the positive electrode active material layer, the liquid medium for forming the slurry, the current collector, the electrode area, the discharge capacity, the thickness of the positive electrode plate, etc. are the same as those described above.
[0288] 〈Positive electrode[2]〉
[0289] Next, the positive electrode [2] "positive electrode containing a positive electrode active material having a specific composition represented by composition formula (4)" used in the lithium secondary battery of the present invention will be described.
[0290] [Positive electrode active material of positive electrode [2]]
[0291] Next, the positive electrode active material used in the positive electrode [2] is described.
[0292] [[composition]]
[0293] As the positive electrode active material, a material having a composition represented by the following composition formula (4) and containing a transition metal capable of electrochemically occluding and releasing lithium ions (hereinafter simply referred to as "the positive electrode active material") is used.
[0294] Li x Ni (1-y-z) Co y M z O2 composition formula (4)
[0295] [In composition formula (4), M represents at least one element selected from Mn, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, y represents a number satisfying 0.05≤y≤0.5, and z represents a number satisfying 0.01≤z≤0.5].
[0296] In composition formula (4), M is preferably Mn, Al, or Mg. Furthermore, x is preferably 0.2 ≤ x ≤ 1.15. Furthermore, y is preferably 0.08 ≤ y ≤ 0.4, particularly preferably 0.1 ≤ y ≤ 0.3. Furthermore, z is preferably 0.02 ≤ z ≤ 0.4, particularly preferably 0.03 ≤ z ≤ 0.3.
[0297] [[Surface coating]]
[0298] In addition, it is preferable to use a positive electrode active material having a substance having a composition different from that of the positive electrode active material attached to the surface of the positive electrode active material. The type, attachment method, and amount of the surface-attached substance are the same as those described above.
[0299] [[shape]]
[0300] The particle shape of the positive electrode active material is the same as described above.
[0301] [[Tap density]]
[0302] The tap density of the positive electrode active material is the same as above.
[0303] [[Median particle size d 50 ]]
[0304] The median particle size d of the positive electrode active material particles 50 (When primary particles aggregate to form secondary particles, the secondary particle diameter is the same as above.)
[0305] [[Average primary particle size]]
[0306] When the primary particles aggregate to form secondary particles, the average primary particle size of the positive electrode active material is the same as described above.
[0307] BET surface area
[0308] The BET specific surface area of the positive electrode active material is the same as above.
[0309] [[Manufacturing method]]
[0310] As a method for producing the positive electrode active material, a common method for producing an inorganic compound can be used. In particular, when producing a spherical or ellipsoidal active material, various methods can be considered, for example, the following methods: dissolving or crushing and dispersing nickel raw materials such as nickel nitrate and nickel sulfate, cobalt raw materials such as cobalt nitrate and cobalt sulfate, and the raw material of M in the composition formula (4) in a solvent such as water, adjusting the pH while stirring to produce and obtain a spherical precursor, drying it as needed, adding a Li source such as LiOH, Li2CO3, LiNO3, and sintering at a high temperature to obtain an active material; dissolving or crushing nickel raw materials such as nickel nitrate, nickel sulfate, nickel oxide, nickel hydroxide, and nickel hydroxybenzene, cobalt raw materials such as cobalt nitrate, cobalt sulfate, cobalt oxide, cobalt hydroxide, and cobalt hydroxybenzene, and the raw material of M in the composition formula (4); A method of dispersing nickel raw materials such as nickel nitrate, nickel sulfate, nickel oxide, nickel hydroxide, and basic nickel hydroxide, and cobalt raw materials such as cobalt nitrate, cobalt sulfate, cobalt oxide, cobalt hydroxide, and basic cobalt hydroxide, as well as the raw materials of M in the composition formula (4), and Li sources such as LiOH, Li2CO3, and LiNO3, and drying and shaping them into spherical or ellipsoidal precursors in a solvent such as water, and then adding Li sources such as LiOH, Li2CO3, and LiNO3 thereto and sintering them at a high temperature to obtain an active material.
[0311] In order to manufacture the positive electrode of the present invention, the positive electrode active material (the positive electrode active material represented by the composition formula (4) and / or the positive electrode active material represented by the composition formula (4) coated with the above-mentioned surface-attached material) can be used alone, or the positive electrode active material and one or more substances having a different composition from the positive electrode active material can be combined in any combination and proportion. As a preferred combination in this case, a combination of the positive electrode active material and LiMn2O4 or a substance in which a portion of its Mn is replaced by other transition metals; or a combination of the positive electrode active material and LiCoO2 or a substance in which a portion of its Co is replaced by other transition metals can be listed.
[0312] Here, it is preferred that the positive electrode active material is 30% or more by mass of the total positive electrode active material, and more preferably 50% or more by mass. If the proportion of the positive electrode active material used decreases, the battery capacity may decrease. In addition, "the positive electrode active material" and "positive electrode active material other than the positive electrode active material" are collectively referred to as "positive electrode active material".
[0313] [Structure of positive electrode of positive electrode [2]]
[0314] Next, the structure of the positive electrode used in the positive electrode [2] is described.
[0315] The electrode structure and manufacturing method of the positive electrode [2], the compaction of the positive electrode active material layer, the conductive material, the binding material used in the manufacture of the positive electrode active material layer, the liquid medium for forming the slurry, the current collector, the electrode area, the discharge capacity, the thickness of the positive electrode plate, etc. are the same as those described above.
[0316] 〈Positive electrode[3]〉
[0317] Next, the positive electrode [3] "a positive electrode comprising any one of the positive electrode active materials selected from the following (a) to (d)" used in the lithium secondary battery of the present invention will be described.
[0318] (a) BET specific surface area is 0.4 m 2 / g~2m 2 / g of positive electrode active material
[0319] (b) Positive electrode active material with an average primary particle size of 0.1 μm to 2 μm
[0320] (c) Median particle size d 50 Positive electrode active material with a diameter of 1μm to 20μm
[0321] (d) Tap density is 1.3 g / cm 3 ~2.7g / cm 3 positive electrode active material.
[0322] [Positive electrode active material of positive electrode [3]]
[0323] Next, the positive electrode active material used in the positive electrode [3] is described.
[0324] [[composition]]
[0325] The positive electrode active material is not particularly limited as long as it can electrochemically occlude and release lithium ions. Preferred materials include those containing lithium and at least one transition metal, such as lithium-transition metal composite oxides and lithium-containing transition metal phosphates. Specifically, materials having the same composition as described above can be used.
[0326] [[Surface coating]]
[0327] Preferably, a positive electrode active material having a composition different from that of the core positive electrode active material is attached to the surface of the positive electrode active material. The type, attachment method, and amount of the surface-attached material are the same as those described above.
[0328] [[shape]]
[0329] The particle shape of the positive electrode active material is the same as described above.
[0330] BET surface area
[0331] The BET specific surface area of the positive electrode active material is preferably 0.4 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 0.6m 2 / g or more, and the upper limit is preferably 2m 2 / g or less, more preferably 1.8m 2 / g or less, more preferably 1.5m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, while if the BET specific surface area is larger than this range, it is difficult to increase the tap density, which may cause problems in coating properties when forming the positive electrode active material.
[0332] The BET specific surface area is defined as the value measured by the nitrogen adsorption BET 1-point method using a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken) after pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas correctly adjusted to a relative pressure of 0.3 relative to atmospheric pressure.
[0333] [[Average primary particle size]]
[0334] When the primary particles are condensed to form secondary particles, the average primary particle size of the positive electrode active material is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.3 μm or more, most preferably 0.4 μm or more, and its upper limit is preferably 2 μm or less, more preferably 1.6 μm or less, further preferably 1.3 μm or less, and most preferably 1 μm or less. If the average primary particle size exceeds the above upper limit, it is difficult to form spherical secondary particles, which has an adverse effect on powder filling properties, or the specific surface area is greatly reduced. Therefore, the possibility of reduced battery performance such as output characteristics sometimes becomes higher. On the contrary, if the average primary particle size is lower than the above lower limit, it is usually due to incomplete crystallization, and therefore sometimes problems such as poor reversibility of charge and discharge are generated.
[0335] The primary particle size can be measured by observation using a scanning electron microscope (SEM). Specifically, the maximum value of the slice formed by the left and right boundaries of the primary particles on a straight line in the horizontal direction is obtained for 50 random primary particles in a photograph with a magnification of 10,000 times, and the average value is taken.
[0336] [[Median particle size d 50 ]]
[0337] The median particle size d of the positive electrode active material particles 50 (When primary particles aggregate to form secondary particles, the secondary particle diameter is the secondary particle diameter) is preferably 1 μm or more, more preferably 1.2 μm or more, further preferably 1.5 μm or more, and most preferably 2 μm or more. The upper limit is preferably 20 μm or less, more preferably 18 μm or less, further preferably 16 μm or less, and most preferably 15 μm or less. If the median particle size d 50 If the particle size is lower than the lower limit, a product with a high tap density may not be obtained. If the particle size exceeds the upper limit, the diffusion of lithium in the particles takes time, which may cause a decrease in battery performance. In addition, when the positive electrode of the battery is prepared, that is, when the active material and the conductive agent or binder are slurried in a solvent and then coated into a thin film, streaks may be generated. 50 When the positive electrode active material is obtained by adding a positive electrode active material, the filling property when preparing the positive electrode can be further improved, which is preferred.
[0338] In addition, the median particle size d in the present invention is 50 The particle size distribution can be measured using a known laser diffraction / scattering particle size distribution measuring apparatus. An LA-920 manufactured by HORIBA Corporation is used as the particle size distribution meter. A 0.1% by mass sodium hexametaphosphate aqueous solution is used as the dispersion medium for the measurement. After ultrasonic dispersion for 5 minutes, the measurement is performed at a refractive index of 1.24.
[0339] [[Tap density]]
[0340] The tap density of the positive electrode active material is preferably 1.3 g / cm 3 More than 1.5 g / cm 3 More preferably, 1.6 g / cm 3 Above, most preferably 1.7 g / cm 3 Above. If the tap density of the positive electrode active material is lower than the above lower limit, the amount of dispersion medium required for forming the positive electrode active material layer increases, and the necessary amount of conductive material or binder increases, the filling rate of the positive electrode active material in the positive electrode active material layer is restricted, and the battery capacity is sometimes restricted. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. Generally speaking, the larger the tap density, the more preferred, and there is no particular upper limit. However, if the tap density is too large, the diffusion of lithium ions in the positive electrode active material layer with the electrolyte as the medium becomes a factor that determines the speed, and the load characteristics are sometimes easily reduced. Therefore, the upper limit of the tap density is preferably 2.7 g / cm 3 Below, more preferably 2.5g / cm 3 the following.
[0341] In the present invention, the tap density is defined as follows: a sample is passed through a sieve with an aperture of 300 μm and falls to a depth of 20 cm. 3 After filling the container volume, a powder density measuring device (for example, Tapdensor manufactured by Seishin Enterprise Co., Ltd.) is used to vibrate 1000 times with a stroke length of 10 mm, and the bulk density at this time is taken as the tap density.
[0342] In terms of long life and high output, the positive electrode active material in the lithium secondary battery of the present invention preferably satisfies the above-mentioned BET specific surface area, average primary particle size, median particle size d 50 and two or more physical properties of tap density.
[0343] [[Manufacturing method]]
[0344] The method for producing the positive electrode active material is the same as that described above.
[0345] The positive electrode active material in the lithium secondary battery of the present invention can be used alone or in any combination and ratio. Two or more positive electrode active materials with different compositions or different powder properties can be used. In addition, from the perspective of improving life, the positive electrode of the present invention preferably contains a positive electrode active material (the positive electrode active material) having any of the above-mentioned properties and a positive electrode of a positive electrode active material different from the positive electrode active material.
[0346] [Structure of positive electrode of positive electrode [3]]
[0347] Next, the structure of the positive electrode used in the positive electrode [3] is described.
[0348] The electrode structure and manufacturing method of the positive electrode [3], the compaction of the positive electrode active material layer, the conductive material, the binding material used in the manufacture of the positive electrode active material layer, the liquid medium for forming the slurry, the current collector, the electrode area, the discharge capacity, the thickness of the positive electrode plate, etc. are the same as those described above.
[0349] 〈Positive electrode[4]〉
[0350] Next, the positive electrode [4] used in the lithium secondary battery of the present invention, "a positive electrode satisfying any one of the conditions selected from the following (e) to (f)" will be described.
[0351] (e) A positive electrode produced by forming a positive electrode active material layer containing a positive electrode active material, a conductive material, and a binder on a current collector, wherein the content of the conductive material in the positive electrode active material layer is in the range of 6% by mass to 20% by mass (Example 1)
[0352] (f) A positive electrode is prepared by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector, wherein the density of the positive electrode active material layer is 1.7 g / cm 3 ~3.5g / cm 3 Range (Method 2)
[0353] (g) A positive electrode produced by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector, wherein the ratio of the thickness of the positive electrode active material layer and the current collector (the thickness of the active material layer on one side before injection of a non-aqueous electrolyte) / (the thickness of the current collector) is 1.6 to 20 (method 3).
[0354] [Positive electrode active material of positive electrode [4]]
[0355] Next, the positive electrode active material used in the positive electrode [4] is described.
[0356] The positive electrode active material is not particularly limited as long as it can electrochemically occlude and release lithium ions. Preferred materials include those containing lithium and at least one transition metal, such as lithium-transition metal composite oxides and lithium-containing transition metal phosphates. Specifically, materials having the same composition as described above can be used.
[0357] The surface coating, shape, tap density, median particle size d of the positive electrode active material 50 , average primary particle size, BET specific surface area, manufacturing method, etc. are the same as above.
[0358] [Structure of positive electrode of positive electrode [4]]
[0359] Next, the structure of the positive electrode used in the positive electrode [4] is described.
[0360] [[Electrode structure and fabrication method]]
[0361] The positive electrode [4] in the lithium secondary battery of the present invention is produced by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector. The production of a positive electrode using a positive electrode active material can be carried out according to a conventional method. That is, at least the positive electrode active material, the binder, the conductive material used as needed (which is a necessary component in mode 1) and the thickener used as needed are dry-mixed to form a sheet, and then the sheet material is pressed and bonded to the positive electrode current collector, or these materials are dissolved or dispersed in a liquid medium to form a slurry, and then the slurry is applied to the positive electrode current collector and dried, thereby forming a positive electrode active material layer on the current collector, thereby obtaining a positive electrode.
[0362] The content of the positive electrode active material in the positive electrode active material layer is preferably 80% by mass or more, more preferably 82% by mass or more, and particularly preferably 84% by mass or more. The upper limit is preferably 95% by mass or less, more preferably 93% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the capacitance may sometimes become insufficient. On the contrary, if the content of the positive electrode active material is too high, the strength of the positive electrode may sometimes be insufficient.
[0363] Conductive materials
[0364] As the conductive material, any known conductive material can be used, and specific examples include the same conductive materials as those mentioned above.
[0365] The content of the conductive material used in the positive electrode of the lithium secondary battery of the present invention in the positive electrode active material layer is as follows: in embodiment 1, it must be 6% by mass or more, preferably 7% by mass or more, more preferably 8% by mass or more, and even more preferably 9% by mass or more. In embodiments 2 and 3, the content is not particularly limited, but is preferably 6% by mass or more, more preferably 7% by mass or more, and even more preferably 8% by mass or more. If the content of the conductive material in the positive electrode active material layer is too low, the conductivity is insufficient, and high output may not be achieved.
[0366] In addition, the upper limit of the content of the conductive material in the positive electrode active material layer is as follows: in embodiment 1, it must be 20% by mass or less, preferably 18% by mass or less, and particularly preferably 15% by mass or less; in embodiments 2 and 3, there is no particular limitation, but it is preferably 20% by mass or less, more preferably 18% by mass or less, and even more preferably 15% by mass or less. If its content is too high, the battery capacity is reduced, and high output may not be achieved.
[0367] [[Adhesive]]
[0368] The binder used in the production of the positive electrode active material layer is not particularly limited. When a coating method is used, any binder can be used as long as it is soluble or dispersible in the liquid medium used in electrode production. Specific examples include the same substances as mentioned above.
[0369] The ratio of binder in positive electrode active material layer is usually 0.1% by mass or more, preferably 1% by mass or more, more preferably 3% by mass or more, and its upper limit is usually 80% by mass or less, preferably 60% by mass or less, more preferably 40% by mass or less, further preferably 10% by mass or less. If the ratio of binder is too low, positive electrode active material can not be fully maintained, the mechanical strength of positive electrode is insufficient, and battery performance such as cycle characteristics deteriorates. On the other hand, if the ratio of binder is too high, battery capacity or conductivity may sometimes be reduced.
[0370] [[Liquid medium for forming a slurry]]
[0371] The liquid medium used to form the slurry is not particularly limited in type, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive agent, the binder, and the thickener used as needed. Any aqueous solvent or organic solvent can be used. Specific examples include the same substances as those mentioned above. The type and amount of thickening material added are also the same as those mentioned above.
[0372] [[Compact]]
[0373] In order to increase the packing density of the positive electrode active material, the positive electrode active material layer obtained by coating and drying is preferably compacted using a manual press, a roller press, etc. The lower limit of the density of the positive electrode active material layer must be 1.7 g / cm in method 2. 3 Above, preferably 2.0 g / cm 3 Above, particularly preferably 2.2 g / cm 3 In addition, there is no particular limitation in Mode 1 and Mode 3, but it is preferably 1.7g / cm 3 More than 2.0 g / cm 3 More preferably, 2.2 g / cm 3 If the density is below this range, the conductivity between active materials decreases, the battery impedance increases, and high output may not be obtained.
[0374] The upper limit of the density of the positive electrode active material layer must be 3.5 g / cm in embodiment 2. 3 Below, preferably 3.0 g / cm 3 Below, particularly preferably 2.8 g / cm 3In addition, in mode 1 and mode 3, there is no particular limitation, but preferably 3.5g / cm 3 Below, more preferably 3.0 g / cm 3 Below, more preferably 2.8 g / cm 3 If the density exceeds this range, the permeability of the non-aqueous electrolyte to the vicinity of the current collector / active material interface decreases, and the charge and discharge characteristics at high current density are degraded, and high output may not be obtained.
[0375] [[Current Collector]]
[0376] The material of the positive electrode current collector is not particularly limited and is the same as described above. The shape of the current collector and the thickness of the film are also the same as described above.
[0377] Regarding the ratio of the thickness of the positive electrode active material layer to the current collector, the value of (thickness of the active material layer on the side before injection of the non-aqueous electrolyte) / (thickness of the current collector) must be 20 or less, preferably 15 or less, and particularly preferably 10 or less in embodiment 3; and there is no particular limitation in embodiments 1 and 2, but it is preferably 20 or less, more preferably 15 or less, and particularly preferably 10 or less. If this range is exceeded, the current collector may generate heat due to Joule heat during high current density charge and discharge, and the positive electrode may be damaged.
[0378] The lower limit of the value of (thickness of the active material layer on one side before injection of the non-aqueous electrolyte) / (thickness of the current collector) must be 1.6 or more, preferably 1.8 or more, and particularly preferably 2 or more in embodiment 1. In addition, there is no particular limitation in embodiments 1 and 2, but it is preferably 1.6 or more, more preferably 1.8 or more, and even more preferably 2 or more. If it is below this range, the volume ratio of the current collector to the positive electrode active material increases, the capacity of the battery decreases, and high output may not be obtained.
[0379] If the above-mentioned "content of conductive material in the positive electrode active material layer", "density of the positive electrode active material layer", and "ratio of the thickness of the positive electrode active material layer and the collector, that is, the value of (thickness of the active material layer on one side before injection of the non-aqueous electrolyte) / (thickness of the collector)" are combined within their respective preferred ranges, a more preferred high-output lithium secondary battery can be formed.
[0380] [[Electrode area]]
[0381] When the nonaqueous electrolyte of the present invention is used, the area of the positive electrode active material layer is preferably larger than the outer surface area of the battery case from the viewpoint of high output and improved stability at high temperatures, as described above.
[0382] Discharge capacity
[0383] When using the non-aqueous electrolyte for secondary batteries of the present invention, if the capacitance of the battery elements contained in the battery casing of one secondary battery (the capacitance when the battery is discharged from a fully charged state to a discharged state) is 3 ampere hours (Ah) or more, the effect of improving the output characteristics becomes greater, so it is preferred.
[0384] Therefore, the design of the positive electrode plate and the like is also the same as above.
[0385] [[Thickness of the positive plate]]
[0386] The thickness of the positive electrode plate is not particularly limited and is the same as described above.
[0387] 〈Positive electrode[5]〉
[0388] Next, the positive electrode [5] used in the lithium secondary battery of the present invention is described.
[0389] [Positive electrode active material of positive electrode [5]]
[0390] Next, the positive electrode active material used in the positive electrode [5] is described.
[0391] [[composition]]
[0392] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release lithium ions. Preferably, it contains lithium and at least one transition metal, for example, lithium-transition metal composite oxides and lithium-containing transition metal phosphates.
[0393] As the transition metal of the lithium-transition metal composite oxide, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples, there are lithium-cobalt composite oxides such as LiCoO2; lithium-nickel composite oxides such as LiNiO2; lithium-manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO3; substances obtained by replacing part of the transition metal atoms forming the main body of these lithium-transition metal composite oxides with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, etc.
[0394] The lithium-cobalt composite oxide is not particularly limited, but preferably has a composition represented by the following composition formula (8).
[0395] Li x Co (1-y) M 1 y O2 composition formula (8)
[0396] [In the composition formula (8), M 1represents at least one element selected from Ni, Mn, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, and y represents a number satisfying 0.05≤y≤0.8].
[0397] In the composition formula (8), M 1 Ni, Mn, Al, and Fe are particularly preferred. Furthermore, x is particularly preferably 0.2≤x≤1.15, and y is particularly preferably 0.1≤y≤0.5.
[0398] The lithium-nickel composite oxide is not particularly limited, but preferably has a composition represented by the following composition formula (9).
[0399] Li x Ni (1-y) M 2 y O2 composition formula (9)
[0400] [In the composition formula (9), M 2 represents at least one element selected from Co, Mn, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, and y represents a number satisfying 0.05≤y≤0.8].
[0401] In the composition formula (9), M 2 Co, Mn, Al, and Fe are particularly preferred. Furthermore, x is particularly preferably 0.2≤x≤1.15, and y is particularly preferably 0.1≤y≤0.5.
[0402] The lithium-manganese composite oxide is not particularly limited, but preferably has a composition represented by the following composition formula (10).
[0403] Li x Mn (1-y) M 3 y O2 composition formula (10)
[0404] [In the composition formula (10), M 3 represents at least one element selected from Ni, Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, and y represents a number satisfying 0.05≤y≤0.8].
[0405] In the composition formula (10), M 3 Ni, Co, and Fe are particularly preferred. Furthermore, x is particularly preferably 0.2≤x≤1.15, and y is particularly preferably 0.1≤y≤0.7.
[0406] As the lithium-manganese composite oxide, one having a composition represented by the following composition formula (11) is preferred.
[0407] Li x Mn (2-y) M 4 y O4 composition formula (11)
[0408] [In the composition formula (11), M 4 represents at least one element selected from Ni, Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, and y represents a number satisfying 0.05≤y≤0.8].
[0409] In the composition formula (11), M 4 Ni, Co, Al, and Mg are particularly preferred. Furthermore, x is particularly preferably 0.05≤x≤1.15, and y is particularly preferably 0.1≤y≤0.7.
[0410] As the lithium-manganese composite oxide, one having a composition represented by the following composition formula (12) is preferred.
[0411] Li x Mn (1-y) M 5 y O3 composition formula (12)
[0412] [In the composition formula (12), M 5 represents at least one element selected from Ni, Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤2.4, and y represents a number satisfying 0.05≤y≤0.8].
[0413] In the composition formula (12), M 5 Ni, Co, Al, and Mg are particularly preferred. Furthermore, x is particularly preferably 0.1≤x≤2.3, and y is particularly preferably 0.1≤y≤0.5.
[0414] As the transition metal of the transition metal phosphate compound containing lithium, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples, there can be listed iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7; cobalt phosphates such as LiCoPO4; substances obtained by replacing a part of the transition metal atoms that form the main body of these transition metal phosphate compounds containing lithium with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0415] The iron phosphate is not particularly limited, but preferably has a composition represented by the following composition formula (13).
[0416] Li x Fe (1-y) M 6 y PO4 composition formula (13)
[0417] [In the composition formula (13), M 6 represents at least one element selected from Ni, Co, Mn, Al, Ti, Mg, Cr, Ga, Cu, Zn and Nb, x represents a number satisfying 0<x≤1.2, and y represents a number satisfying 0.05≤y≤0.8].
[0418] In the composition formula (13), M 6 Ni, Co, Mn, and Al are particularly preferred. Furthermore, x is particularly preferably 0.2≤x≤1.15, and y is particularly preferably 0.1≤y≤0.5.
[0419] The positive electrode active material in the present invention is preferably used in any combination and ratio combination of two or more substances having different compositions in the above-mentioned positive electrode active material. Since the various positive electrode active materials are each good at different performances, the positive electrode active material is preferably combined according to the purpose of the target battery to obtain the required performance. In general, it is believed that the performance can be averaged by combination, but for life, it is unexpected that the effect of a positive electrode active material with a long life can be further obtained. By combining a positive electrode active material with a relatively good life and a positive electrode active material with a relatively poor life but other good performance, a high output, large capacity, and long-life lithium secondary battery of the present invention can be achieved.
[0420] As examples of preferred combinations, the following combinations can be cited:
[0421] The positive electrode active material represented by the composition formula (8) and the positive electrode active material represented by the composition formula (10),
[0422] The positive electrode active material represented by the composition formula (8) and the positive electrode active material represented by the composition formula (11),
[0423] The positive electrode active material represented by the composition formula (8) and the positive electrode active material represented by the composition formula (12),
[0424] The positive electrode active material represented by the composition formula (8) and the positive electrode active material represented by the composition formula (13),
[0425] The positive electrode active material represented by the composition formula (9) and the positive electrode active material represented by the composition formula (10),
[0426] The positive electrode active material represented by the composition formula (9) and the positive electrode active material represented by the composition formula (11),
[0427] The positive electrode active material represented by the composition formula (9) and the positive electrode active material represented by the composition formula (12),
[0428] The positive electrode active material represented by the composition formula (9) and the positive electrode active material represented by the composition formula (13),
[0429] The positive electrode active material represented by the composition formula (10) and the positive electrode active material represented by the composition formula (11),
[0430] The positive electrode active material represented by the composition formula (10) and the positive electrode active material represented by the composition formula (12),
[0431] A positive electrode active material represented by composition formula (10) and a positive electrode active material represented by composition formula (13).
[0432] Particularly preferably,
[0433] The positive electrode active material represented by the composition formula (9) and the positive electrode active material represented by the composition formula (11),
[0434] A positive electrode active material represented by composition formula (10) and a positive electrode active material represented by composition formula (11).
[0435] The combination ratio is not particularly limited, but is preferably 10:90 to 90:10, and more preferably 20:80 to 80:20.
[0436] The positive electrode used in the lithium secondary battery of the present invention contains two or more positive electrode active materials with different compositions, and preferably at least one of the positive electrode active materials has a BET specific surface area, an average primary particle size, a median particle size d 50 And / or the tap density (hereinafter referred to as "the following physical properties") is within the following specific ranges. Among the two or more positive electrode active materials with different compositions, there are also positive electrode active materials whose physical properties are not within the following ranges, but it is preferred that a certain physical property of all substances of the two or more positive electrode active materials is within the following ranges. The content ratio of "all positive electrode active materials whose any one of the following physical properties is within the following specific ranges" relative to "all positive electrode active materials contained in the positive electrode" depends on its physical properties and is not particularly limited, but is preferably 30% by mass or more, more preferably 50% by mass or more, and particularly preferably all of them. It is preferred that for each of the two or more positive electrode active materials contained in the positive electrode, any one or more of the following physical properties is within the following specific ranges, more preferably any two or more physical properties are within the following specific ranges, particularly preferably any three or more physical properties are within the following specific ranges, and most preferably all of the following physical properties are within the following specific ranges.
[0437] BET surface area
[0438] The BET specific surface area of at least one of the positive electrode active materials is preferably 0.4 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 0.6m 2 / g or above, the upper limit is 2m 2 / g or less, preferably 1.8m 2 / g or less, more preferably 1.5m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, while if the BET specific surface area is larger than this range, it is difficult to increase the tap density, which may cause problems in coating properties when forming the positive electrode active material.
[0439] The BET specific surface area is defined as the value measured by the nitrogen adsorption BET 1-point method using a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken) after pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas correctly adjusted to a relative pressure of 0.3 relative to atmospheric pressure.
[0440] [[Average primary particle size]]
[0441] The average primary particle size of at least one positive electrode active material in the positive electrode active material is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.3 μm or more, most preferably 0.4 μm or more, and its upper limit is preferably 2 μm or less, more preferably 1.6 μm or less, further preferably 1.3 μm or less, and most preferably 1 μm or less. If the above upper limit is exceeded, it is difficult to form spherical secondary particles, which has an adverse effect on powder filling properties, or the specific surface area is greatly reduced. Therefore, the possibility of reduced battery performance such as output characteristics sometimes increases. On the contrary, if it is lower than the above lower limit, it is usually due to incomplete crystallization, so problems such as poor reversibility of charge and discharge sometimes occur.
[0442] Alternatively, the primary particle size can be measured using a scanning electron microscope (SEM). Specifically, the maximum value of a slice formed by the left and right boundaries of a primary particle on a straight horizontal line is determined for 50 random primary particles in a photograph at 10,000x magnification, and the average value is taken. Although primary particles may aggregate to form secondary particles, in this case, only the primary particles are measured.
[0443] [[Median particle size d 50 ]]
[0444] The median particle size d of at least one positive electrode active material in the positive electrode active material50 (When primary particles aggregate to form secondary particles, the secondary particle diameter is the diameter of the secondary particles) is preferably 1 μm or more, more preferably 1.2 μm or more, further preferably 1.5 μm or more, and most preferably 2 μm or more. The upper limit is preferably 20 μm or less, more preferably 18 μm or less, further preferably 16 μm or less, and most preferably 15 μm or less. If it is lower than the above lower limit, sometimes a product with a high tap density cannot be obtained, and if it exceeds the upper limit, the diffusion of lithium in the particles takes time, so sometimes the battery performance is reduced, or when the positive electrode of the battery is made, that is, when the active material and the conductive agent or adhesive are slurried in a solvent and then coated into a thin film, problems such as stripes are generated. Here, by mixing two or more particles with different median particle sizes d 50 The positive electrode active material can further improve the filling property when making the positive electrode.
[0445] The median particle size d in the present invention 50 The particle size distribution can be measured using a known laser diffraction / scattering particle size analyzer. An LA-920 manufactured by HORIBA Corporation is used as the particle size distribution analyzer. A 0.1% by mass sodium hexametaphosphate aqueous solution is used as the dispersion medium for the measurement. After ultrasonic dispersion for 5 minutes, the measurement is performed at a refractive index of 1.24.
[0446] [[[Tap density]]]
[0447] The tap density of at least one of the positive electrode active materials is preferably 1.3 g / cm 3 More than 1.5 g / cm 3 More preferably, 1.6 g / cm 3 Above, most preferably 1.7 g / cm 3 Above. If the tap density of the positive electrode active material is lower than the above lower limit, the amount of dispersion medium required for forming the positive electrode active material layer increases, and the necessary amount of conductive material or binder increases, the filling rate of the positive electrode active material in the positive electrode active material layer is restricted, and the battery capacity is sometimes restricted. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. Generally speaking, the larger the tap density, the more preferred, and there is no particular upper limit. However, if the tap density is too large, the diffusion of lithium ions in the positive electrode active material layer with the non-aqueous electrolyte as the medium becomes a factor that determines the speed, and the load characteristics are sometimes easily reduced. Therefore, the upper limit of the tap density is preferably 2.7 g / cm 3 Below, more preferably 2.5g / cm 3 the following.
[0448] In the present invention, the tap density is defined as follows: a sample is passed through a sieve with an aperture of 300 μm and falls to a depth of 20 cm.3 After filling the container volume, a powder density measuring device (for example, Tapdensor manufactured by Seishin Enterprise Co., Ltd.) is used to vibrate 1000 times with a stroke length of 10 mm, and the bulk density at this time is taken as the tap density.
[0449] [[Surface coating]]
[0450] At least one of the positive electrode active materials preferably has a surface attached with a substance having a different composition from that of the positive electrode active material constituting the main body of the positive electrode active material or the positive electrode active material of the core (hereinafter referred to as "surface-attached substance"). The type, attachment method, and attachment amount of the surface-attached substance are the same as those described above.
[0451] [[shape]]
[0452] The particle shape of at least one of the positive electrode active materials can be the same as that conventionally used and described above.
[0453] [[Manufacturing method]]
[0454] As a method for producing the positive electrode active material, a common method similar to the above-mentioned method for producing an inorganic compound can be used.
[0455] [Structure of positive electrode of positive electrode [5]]
[0456] Next, the structure of the positive electrode used in the positive electrode [5] is described.
[0457] In the present invention, the electrode structure and production method, the compaction of the positive electrode active material layer, the conductive material, the binder used in the production of the positive electrode active material layer, the liquid medium for forming the slurry, the current collector, the electrode area, the discharge capacity, the thickness of the positive electrode plate, etc. are the same as those described above. When producing the positive electrode, two or more positive electrode active materials can be mixed in advance or added simultaneously during the production of the positive electrode.
[0458] <negative electrode>
[0459] The negative electrode used in the lithium secondary battery of the present invention is not particularly limited as long as it is a negative electrode having an active material layer containing an active material capable of occluding and releasing lithium ions formed on a current collector, but the negative electrode is preferably selected from any one of the following negative electrodes [1] to
[10] :
[0460] Negative electrode[1]: A negative electrode containing two or more carbonaceous materials with different crystallinity as negative electrode active materials;
[0461] Negative electrode [2]: A negative electrode containing amorphous carbon as the negative electrode active material, wherein the amorphous carbon has a (002) plane spacing (d002) of 0.337 nm or more as measured by wide-angle X-ray diffraction, a crystallite size (Lc) of 80 nm or less, and a lattice density (C) of 1360 cm-1 as measured by argon ion laser Raman spectroscopy. -1 The peak intensity relative to 1580 cm -1 The Raman R value defined by the ratio of the peak intensities is greater than 0.2;
[0462] Negative electrode [3]: A negative electrode containing a metal oxide as a negative electrode active material, wherein the metal oxide contains titanium capable of absorbing and releasing lithium ions;
[0463] Negative electrode [4]: A negative electrode containing a carbonaceous material as a negative electrode active material, wherein the circularity of the carbonaceous material is greater than 0.85 and the surface functional group O / C value is 0 to 0.01;
[0464] Negative electrode [5]: A negative electrode containing a hetero-oriented carbon composite as a negative electrode active material, wherein the hetero-oriented carbon composite contains two or more carbonaceous materials with different orientations;
[0465] Negative electrode [6]: A negative electrode containing graphite carbon particles as the negative electrode active material, wherein the circularity of the graphite carbon particles is greater than 0.85, the interplanar spacing (d002) of the (002) plane measured by wide-angle X-ray diffraction is less than 0.337nm, and the spectral density of the graphite carbon particles measured by argon ion laser Raman spectroscopy at 1360cm -1 The peak intensity relative to 1580 cm -1 The Raman R value, defined by the ratio of the peak intensities of is 0.12 to 0.8;
[0466] Negative electrode [7]: a negative electrode containing the following multi-element negative electrode active material (C) as a negative electrode active material, wherein the multi-element negative electrode active material (C) contains at least one lithium occluding metal (A) and / or lithium occluding alloy (B) selected from Al, Pb, Zn, Sn, Bi, In, Mg, Ga, Cd, Ag, Si, B, Au, Pt, Pd and Sb, and contains C and / or N as element Z;
[0467] Negative electrode[8]: A negative electrode containing two or more negative electrode active materials with different properties as negative electrode active materials;
[0468] Negative electrode[9]: Contains a tap density of 0.1g / cm 3 A negative electrode having a negative electrode active material having a micropore volume of 0.01 mL / g or more, which is equivalent to particles with a diameter of 0.01 μm to 1 μm, as measured by a mercury porosimeter;
[0469] Negative electrode
[10] : A negative electrode having a reaction resistance of 500Ω or less generated by the opposing battery of the negative electrode when charged to 60% of the nominal capacity of the negative electrode.
[0470] First, the negative electrode generally used in the lithium secondary battery of the present invention will be described below.
[0471] [Negative electrode active material]
[0472] Next, negative electrode active materials generally used in negative electrodes will be described.
[0473] [[composition]]
[0474] As the negative electrode active material, as long as it can electrochemically occlude and release lithium ions, there is no particular limitation, and examples thereof include carbonaceous materials, metal oxides such as tin oxide or silicon oxide, metal composite oxides, lithium alloys such as lithium alloys, Sn or Si, etc., which can form an alloy with lithium. They can be used alone or in any combination and ratio. Among them, from a safety perspective, carbonaceous materials or lithium composite oxides are preferably used.
[0475] The metal composite oxide is not particularly limited as long as it can occlude and release lithium. However, from the viewpoint of high current density charge and discharge characteristics, it preferably contains titanium and / or lithium as constituent components.
[0476] As the carbonaceous material, from the perspective of the balance between initial irreversible capacity and high current density charge and discharge characteristics, the following carbonaceous materials are preferred:
[0477] (1) Natural graphite;
[0478] (2) Artificial carbonaceous materials and artificial graphite materials; carbonaceous materials [e.g., natural graphite, coal coke, petroleum coke, coal pitch, petroleum pitch or materials obtained by oxidation of these pitches, needle coke, pitch coke, and carbon materials obtained by partially graphitizing them; thermal decomposition products of organic materials such as furnace black, acetylene black, and pitch-based carbon fibers; carbonizable organic materials (e.g., coal tar pitch from soft pitch to hard pitch or dry distilled liquefied oil and other coal-based heavy oils, straight-run heavy oils such as atmospheric residual oil and vacuum residual oil; decomposed petroleum heavy oils such as ethylene tar produced as a by-product during thermal decomposition of crude oil, naphtha, etc.; and aromatic hydrocarbons such as acenaphthylene, decacyclene, anthracene, and phenanthrene; nitrogen ring compounds such as phenazine or acridine; sulfur ring compounds such as thiophene and dithiophene) carbon materials formed by heat treatment at least once in the range of 400 to 3200° C.; polyphenylenes such as biphenyl and terphenyl; polyvinyl chloride, polyvinyl alcohol, polyvinyl butyral, their insoluble products, nitrogen-containing polyacrylonitrile, polypyrrole and other organic polymers; sulfur-containing polythiophene, polystyrene and other organic polymers; natural polymers such as polysaccharides represented by cellulose, lignin, mannan, polygalacturonic acid, chitosan and sucrose; thermoplastic resins such as polyphenylene sulfide and polyphenylene ether; thermosetting resins such as furfuryl alcohol resin, phenolic resin and imide resin and their carbides; or solutions formed by dissolving carbonizable organic matter in low molecular weight organic solvents such as benzene, toluene, xylene, quinoline and n-hexane and their carbides;
[0479] (3) The negative electrode active material layer is composed of at least two or more carbonaceous materials with different crystallinity, and / or the carbonaceous materials with different crystallinity have a contact interface;
[0480] (4) The negative electrode active material layer is composed of at least two or more carbonaceous materials having different orientations, and / or the carbonaceous materials having different orientations have an interface in contact with each other.
[0481] [Structure, physical properties and preparation method of negative electrode]
[0482] The properties of the carbon material, the negative electrode containing the carbon material, the electrode polarization method, the current collector, and the lithium secondary battery preferably satisfy any one or more of the following items (1) to (9) simultaneously.
[0483] (1) X-ray parameters
[0484] The carbon material is preferably obtained by X-ray diffraction of the lattice plane (002) using a vibration method. The d value (interlayer distance) is preferably 0.335 nm or more, and its upper limit is usually 0.36 nm or less, preferably 0.35 nm or less, and more preferably 0.345 nm or less. In addition, the crystallite size (Lc) of the carbon material obtained by X-ray diffraction using a vibration method is preferably 1 nm or more, and more preferably 1.5 nm or more.
[0485] (2) Ash content
[0486] The ash content contained in the carbonaceous material is preferably less than 1% by mass relative to the gross mass of the carbonaceous material, more preferably less than 0.5% by mass, particularly preferably less than 0.1% by mass, and as a lower limit, is preferably more than 1ppm. If it exceeds the above range, the deterioration of the battery performance caused by the reaction with the nonaqueous electrolyte during charge and discharge cannot be ignored. If it is less than the scope, then long time and energy and the equipment for preventing pollution are needed in manufacturing, and sometimes cost can rise.
[0487] (3) Volume-based average particle size
[0488] The volume reference average particle size of carbonaceous material is the average particle size (median particle size) of the volume reference sought to by laser diffraction / scattering method, usually more than 1 μm, preferably more than 3 μm, more preferably more than 5 μm, more preferably more than 7 μm. In addition, its upper limit is usually less than 100 μm, preferably less than 50 μm, more preferably less than 40 μm, more preferably less than 30 μm, particularly preferably less than 25 μm. If it is less than the above range, the irreversible capacity increases, sometimes resulting in the loss of initial battery capacity. In addition, if it exceeds the above range, when the electrode is made by coating, it is easy to form an uneven coating surface, which is sometimes not preferred in the battery manufacturing process.
[0489] In the present invention, the volume-based average particle size is defined by the median particle size, which is measured by the following method: dispersing carbon powder in a 0.2 mass % aqueous solution (about 10 mL) of polyoxyethylene (20) sorbitan monolaurate as a surfactant and measuring it using a laser diffraction / scattering particle size distribution meter (for example, LA-700 manufactured by Horiba, Ltd.).
[0490] (4) Raman R value, Raman half-value width
[0491] The R value of the carbonaceous material measured using an argon ion laser Raman spectrometry is generally 0.01 or more, preferably 0.03 or more, more preferably 0.1 or more, and its upper limit is 1.5 or less, preferably 1.2 or less, more preferably 1.0 or less, and further preferably 0.5 or less. If the R value is lower than this range, the crystallinity of the particle surface is too high, and the site (site) where Li enters the interlayer as charge and discharge is sometimes reduced. That is, the charge acceptance is sometimes reduced. In addition, after being coated on the current collector, when the negative electrode is made high-densified by pressing, the crystallization is easily oriented in a direction parallel to the electrode plate, sometimes resulting in a reduction in load characteristics. On the other hand, if it exceeds this range, the crystallinity of the particle surface is reduced, and the reactivity with the non-aqueous electrolyte is increased, sometimes resulting in a reduction in efficiency or an increase in generated gas.
[0492] In addition, carbonaceous materials at 1580 cm -1 There is no particular limit on the Raman half-value width near 10 cm, but it is usually 10 cm -1 Above, preferably 15cm -1 Above, the upper limit is usually 100cm -1 Below, preferably 80cm -1 Below, more preferably 60cm -1 Below, more preferably 40cm -1 The following range. If the Raman half-value width is lower than this range, the crystallinity of the particle surface is too high, and the sites (サイト) at which Li enters the interlayer during charge and discharge sometimes decrease. That is, the charge acceptance sometimes decreases. In addition, after coating on the current collector, when the negative electrode is made high-density by pressing, the crystals tend to be oriented in a direction parallel to the electrode plate, sometimes resulting in reduced load characteristics. On the other hand, if it is higher than this range, the crystallinity of the particle surface decreases, and the reactivity with the non-aqueous electrolyte increases, sometimes resulting in reduced efficiency or increased gas generation.
[0493] The Raman spectrum is measured as follows: using a Raman spectrometer (e.g., a Raman spectrometer manufactured by JASCO Corporation), the sample is allowed to fall naturally and fill a measurement cell. The sample surface in the cell is irradiated with an argon ion laser while the cell is rotated in a plane perpendicular to the laser. The Raman spectrum obtained is measured at 1580 cm -1 Nearby peak P A Intensity I A and 1360cm -1 Nearby peak P B Intensity I B , calculate its intensity ratio R (R=I B / I A ), which is defined as the Raman R value of the carbonaceous material. In addition, the Raman spectrum obtained by measuring the -1 Nearby peak P A The half-value width of the carbonaceous material is defined as the half-value width of the Raman ions.
[0494] In addition, the Raman measurement conditions here are as follows.
[0495] Argon ion laser wavelength: 514.5nm
[0496] Laser power on the sample: 15-25mW
[0497] Resolution: 10-20cm -1
[0498] Measuring range: 1100cm -1 ~1730cm -1
[0499] R value, half-value width analysis: background processing
[0500] ・Smoothing processing: simple averaging, convolution 5 points (コンボリュション5ポイント)
[0501] (5) BET specific surface area
[0502] The specific surface area of the carbonaceous material of the present invention measured by the BET method is usually 0.1 m 2 / g or more, preferably 0.7m 2 / g or more, more preferably 1.0m 2 / g or more, more preferably 1.5m 2 / g or more. Its upper limit is usually 100m 2 / g or less, preferably 25m 2 / g or less, more preferably 15m 2 / g or less, more preferably 10m 2 / g or less. If the value of the specific surface area is lower than the above range, when used as a negative electrode, the acceptance of lithium deteriorates during charging, and lithium is easily precipitated on the electrode surface. On the other hand, if it is higher than the above range, when used as a negative electrode material, the reactivity with the nonaqueous electrolyte increases, the gas generated tends to increase, and sometimes it is difficult to obtain a preferred battery.
[0503] The specific surface area measured by the BET method uses a value measured as follows: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), the sample is pre-dried at 350°C for 15 minutes under nitrogen flow, and then measured by the nitrogen adsorption BET 1-point method using a gas flow method using a nitrogen-helium mixed gas in which the relative pressure of nitrogen relative to atmospheric pressure is accurately adjusted to 0.3.
[0504] (6) Micropore size distribution
[0505] The micropore size distribution of the carbonaceous material used in the present invention is the amount of the voids in the particles with a micropore diameter of 0.01 μm to 1 μm obtained by mercury porosimeter (mercury intrusion method), the concave-convex caused by the unevenness of the particle surface, the contact surface between the particles, etc., which is 0.01 mL / g or more, preferably 0.05 mL / g or more, more preferably 0.1 mL / g or more, and its upper limit is 0.6 mL / g or less, preferably 0.4 mL / g or less, more preferably 0.3 mL / g or less. If it exceeds this range, a large amount of adhesive is sometimes needed when manufacturing the pole plate. If it is below this range, the high current density charge and discharge characteristics are reduced, and the relaxation effect of the electrode expansion and contraction during charge and discharge can sometimes not be obtained.
[0506] In addition, the total micropore volume corresponding to the micropore diameter in the range of 0.01 μm to 100 μm is preferably 0.1 mL / g or more, more preferably 0.25 mL / g or more, further preferably 0.4 mL / g or more, and its upper limit is 10 mL / g or less, preferably 5 mL / g or less, and more preferably 2 mL / g or less. If it is higher than this range, a large amount of adhesive is sometimes required when manufacturing the pole plate. If it is lower than this range, the dispersion effect of the thickener or binder is sometimes not obtained when manufacturing the pole plate.
[0507] In addition, the average pore diameter is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.5 μm or more, with an upper limit of 50 μm or less, preferably 20 μm or less, and more preferably 10 μm or less. If it exceeds this range, a large amount of binder may be required. If it is below this range, the high current density charge and discharge characteristics may be reduced.
[0508] As a device used as a mercury porosimeter, a mercury porosimeter (autopore 9520; manufactured by micrometritics) can be used. About 0.2 g of sample is sealed in a powder container and degassed for 10 minutes at room temperature and vacuum (less than 50 μmHg) for pretreatment. Then, the pressure is reduced to 4 psia (about 28 kPa), mercury is introduced, and the pressure is increased in stages from 4 psia (about 28 kPa) to 40,000 psia (about 280 MPa), and then the pressure is reduced to 25 psia (about 170 kPa). The number of stages during the pressure increase is more than 80 stages, and in each stage, the amount of mercury intrusion is measured after a 10-second equilibrium time. The micropore size distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula. The surface tension (γ) of mercury is 485 dyne / cm, and the contact angle (φ) is 140°. The average pore diameter is the pore diameter at which the cumulative pore volume reaches 50%.
[0509] (7) Circularity
[0510] Circularity is used as the degree of sphericity of the carbonaceous material. The circularity of particles with a particle size range of 3 to 40 μm is preferably 0.1 or greater, particularly preferably 0.5 or greater, more preferably 0.8 or greater, further preferably 0.85 or greater, and most preferably 0.9 or greater. A higher circularity is preferred because it improves high current density charge and discharge characteristics.
[0511] The circularity is defined by the following formula: when the circularity is 1, it is a theoretical true sphere.
[0512] Circularity = (the circumference of an equivalent circle with the same area as the particle's projected shape) / (the actual circumference of the particle's projected shape)
[0513] As the circularity value, the value measured as follows is used: using, for example, a flow particle image analyzer (for example, FPIA manufactured by Sysmex Industrial Corporation), about 0.2 g of the sample is dispersed in a 0.2 mass % aqueous solution (about 50 mL) of polyoxyethylene (20) sorbitan monolaurate as a surfactant, and after irradiating with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, 0.6 to 400 μm is designated as the detection range, and particles in the particle size range of 3 to 40 μm are measured.
[0514] There is no particular limitation on the method for improving circularity, but spheroidization (mechanical energy treatment) is preferred because it can make the shape of the interparticle gaps uniform when the electrode body is formed. Examples of spheroidization include methods for mechanically approaching a spherical shape by applying shear force or compressive force, and mechanical / physical treatment methods for granulating a plurality of microparticles by the adhesive force of a binder or the particles themselves.
[0515] (8) True density
[0516] The true density of carbonaceous materials is usually 1.4g / cm 3 Above, preferably 1.6 g / cm 3 More than 1.8 g / cm 3 More preferably, 2.0 g / cm 3 Above, the upper limit is 2.26g / cm 3 Below. The upper limit is the theoretical value of graphite. If it is below this range, the crystallinity of the carbon is too low, and the initial irreversible capacity may increase. In the present invention, the true density is defined as the value measured by the liquid phase replacement method (hydrometer method) using butanol.
[0517] (9) Tap density
[0518] The tap density of carbonaceous materials is usually 0.1g / cm 3 Above, preferably 0.5g / cm 3 More than 0.7 g / cm 3 Above, particularly preferably 1.0 g / cm 3 In addition, the upper limit is preferably 2g / cm 3 Below, more preferably 1.8g / cm 3 Below, particularly preferably 1.6 g / cm 3Below. If the tap density is lower than this range, when used as a negative electrode, the packing density is difficult to increase, and sometimes a high-capacity battery cannot be obtained. On the other hand, if it exceeds this range, the gaps between the particles in the electrode are too few, making it difficult to ensure the conductivity between the particles, and sometimes it is difficult to obtain preferred battery characteristics. The tap density is measured by the same method as that described in the positive electrode and is defined by this method.
[0519] (10) Orientation ratio
[0520] The orientation ratio of the carbonaceous material is usually 0.005 or more, preferably 0.01 or more, more preferably 0.015 or more, and its upper limit is within the range of a theoretical value of 0.67 or less. If it is below this range, the high-density charge and discharge characteristics may be reduced.
[0521] The orientation ratio was measured by X-ray diffraction after the sample was press-formed. 0.47 g of the sample was filled into a molding machine with a diameter of 17 mm and the pressure was 600 kgf / cm 2 The resulting compact was compressed and fixed with clay so that it was flush with the surface of a sample holder for measurement. X-ray diffraction was then measured. The ratio (integrated intensity of (110) diffraction / integrated intensity of (004) diffraction) was calculated from the peak intensities of the obtained carbon (110) diffraction and (004) diffraction. This ratio was defined as the orientation ratio of the active material.
[0522] The X-ray diffraction measurement conditions here are as follows: In addition, "2θ" represents the diffraction angle.
[0523] Target: Cu (Kα ray) graphite monochromator
[0524] Slit:
[0525] Divergence slit = 0.5 degrees, receiving slit = 0.15 mm, scattering slit = 0.5 degrees
[0526] Measurement range and step angle / measurement time
[0527] (110) surface: 75 degrees ≤ 2θ ≤ 80 degrees 1 degree / 60 seconds
[0528] (004) surface: 52 degrees ≤ 2θ ≤ 57 degrees 1 degree / 60 seconds
[0529] (11) Aspect ratio (powder)
[0530] Theoretically, the aspect ratio is greater than 1, with an upper limit of less than 10, preferably less than 8, and more preferably less than 5. If the upper limit is exceeded, streaks may occur during electrode plate production, a uniform coating surface may not be obtained, and high current density charge and discharge characteristics may be reduced.
[0531] The aspect ratio is expressed as the ratio A / B of the longest diameter A of a carbonaceous material particle to its shortest diameter B, perpendicular thereto, when observed in three dimensions. Observation of the carbon particles was performed using a scanning electron microscope capable of magnification. Fifty graphite particles were randomly selected and fixed to the end surface of a metal plate 50 microns thick or less. The stage holding the sample was rotated and tilted, and the A and B values of each particle were measured. The average value of A / B was calculated.
[0532] (12) Auxiliary material mixing
[0533] The term "auxiliary material mixing" refers to the inclusion of two or more carbonaceous materials with different properties in the negative electrode and / or the negative electrode active material. The properties mentioned here refer to one or more characteristics among X-ray diffraction parameters, median particle size, aspect ratio, BET specific surface area, orientation ratio, Raman R value, tap density, true density, pore distribution, circularity, and ash content.
[0534] Particularly preferred embodiments include those in which the volume-based particle size distribution is bilaterally asymmetric around the median diameter, in which two or more carbonaceous materials having different Raman R values are contained, or in which X-ray parameters are different.
[0535] As an example of its effect, it can be cited that by containing graphite such as natural graphite, artificial graphite; carbon black such as acetylene black; amorphous carbon such as needle coke and other carbonaceous materials as conductive agents, resistance can be reduced. They can be used alone or in any combination and in any proportion. When added as a conductive agent, it is 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 0.6% by mass or more, and its upper limit is 45% by mass or less, preferably in the range of 40% by mass. If it is lower than this range, it is sometimes difficult to obtain the effect of improved conductivity. If it is higher than the above range, it sometimes leads to an increase in the initial irreversible capacity.
[0536] (13) Electrode preparation
[0537] The electrodes can be made by conventional methods. For example, a binder, a solvent, a thickener added as needed, a conductive material, a filler, etc. are added to the negative electrode active material to make a slurry, which is applied to the collector and pressed after drying to form the electrode. At the stage before the non-aqueous electrolyte injection process, the thickness of the negative electrode active material on each side of the battery is usually 15 μm or more, preferably 20 μm or more, more preferably 30 μm or more, and the upper limit is 150 μm or less, preferably 120 μm or less, more preferably 100 μm or less. If this range is exceeded, it is difficult for the non-aqueous electrolyte to penetrate into the vicinity of the collector interface, and therefore the high current density charge and discharge characteristics are reduced. In addition, if it is below this range, the volume ratio of the collector to the negative electrode active material increases, and the battery capacity sometimes decreases. In addition, the negative electrode active material can be roll-formed into a sheet electrode, or can be made into a granular electrode by compression molding.
[0538] (14) Current collector
[0539] As the current collector, any known current collector can be used. As the current collector of the negative electrode, metal materials such as copper, nickel, stainless steel, and nickel-plated steel can be mentioned. Among them, copper is preferred from the viewpoint of ease of processing and cost. When the current collector is a metal material, the shape of the current collector can include metal foil, metal cylinder, metal coil, metal plate, metal film, expansion alloy, perforated metal, foamed metal, etc. Among them, metal film is preferred, copper foil is more preferred, and rolled copper foil obtained by rolling method and electrolytic copper foil obtained by electrolysis are further preferred. Any one of them can be used as the current collector. When the thickness of the copper foil is thinner than 25 μm, a copper alloy (phosphor bronze, titanium copper, Corson alloy, Cu-Cr-Zr alloy, etc.) with higher strength than pure copper can be used. In addition, aluminum foil is preferably used because it has a light specific gravity and can reduce the weight of the battery when used as a current collector.
[0540] In a current collector made from rolled copper foil, the copper crystals are aligned in the rolling direction, making it difficult to break even when the negative electrode is tightly bent or bent at an acute angle, making it suitable for small cylindrical batteries. Electrolytic copper foil is produced by, for example, immersing a metal drum in a non-aqueous electrolyte containing dissolved copper ions, rotating the drum while passing an electric current, thereby depositing copper on the drum's surface, which is then peeled off. Copper can also be deposited electrolytically on the surface of the rolled copper foil. One or both sides of the copper foil can be roughened or surface treated (for example, chromate treatment with a thickness of several nanometers to 1 μm, or a base treatment with titanium, etc.).
[0541] The current collector substrate is required to have the following physical properties.
[0542] (1) Average surface roughness (Ra)
[0543] The average surface roughness (Ra) of the active material film forming surface of the current collector substrate specified in the method described in JIS B 0601-1994 is not particularly limited, but is usually 0.05 μm or more, preferably 0.1 μm or more, particularly preferably 0.15 μm or more, and its upper limit is usually 1.5 μm or less, preferably 1.3 μm or less, and particularly preferably 1.0 μm or less. By making the average surface roughness (Ra) of the current collector substrate in the range between the above lower limit and the upper limit, good charge and discharge cycle characteristics can be expected. By setting it to more than the above lower limit, the interface area with the active material film becomes larger, and the adhesion with the active material is improved. There is no particular restriction on the upper limit of the average surface roughness (Ra). When the average surface roughness (Ra) exceeds 1.5 μm, it is difficult to obtain a foil of suitable thickness as a battery, so it is preferably 1.5 μm or less.
[0544] (2) Tensile strength
[0545] The tensile strength of the current collector substrate is not particularly limited, but is generally 100 N / mm 2 Above, preferably 250N / mm 2 More than 400N / mm 2 Above, particularly preferably 500N / mm 2 The tensile strength is the value obtained by dividing the maximum tensile force required for the test piece to break by the cross-sectional area of the test piece. The tensile strength in the present invention can be measured using the same apparatus and method as for measuring elongation. If the current collector substrate has a high tensile strength, cracking of the current collector substrate caused by expansion / contraction of the active material film during charge / discharge can be suppressed, thereby obtaining good cycle characteristics.
[0546] (3) 0.2% Stamina
[0547] The 0.2% yield strength of the current collector substrate is not particularly limited, but is generally 30 N / mm 2 Above, preferably 150N / mm 2 Above, particularly preferably 300N / mm 2 The so-called 0.2% endurance refers to the load required to produce 0.2% plastic (permanent) deformation. After applying a load of this size, the deformation of 0.2 will be maintained even after the load is removed. The 0.2% endurance in the present invention can be measured by the same device and method as for measuring elongation. If the collector substrate has a high 0.2% endurance, the plastic deformation of the collector substrate caused by the expansion / contraction of the active material film during charging / discharging can be suppressed, thereby obtaining good cycle characteristics.
[0548] The thickness of the metal film is arbitrary, but is typically 1 μm or greater, preferably 3 μm or greater, and more preferably 5 μm or greater. The upper limit is typically 1 mm or less, preferably 100 μm or less, and more preferably 30 μm or less. Thinner than 1 μm can reduce strength and sometimes make coating difficult. Thicker than 100 μm can sometimes cause deformation of the electrode, such as curling. The metal film can also be in the form of a mesh.
[0549] (15) Ratio of thickness of current collector to active material layer
[0550] There is no particular restriction on the ratio of the thickness of the current collector to the thickness of the active material layer. (The thickness of the active material layer on one side before the non-aqueous electrolyte is injected) / (the thickness of the current collector) is preferably less than 150, particularly preferably less than 20, more preferably less than 10, and its lower limit is preferably more than 0.1, more preferably less than 0.4, and further preferably in the range of more than 1. If this range is exceeded, the current collector sometimes generates heat due to Joule heat during high current density charging and discharging. If it is below this range, the volume ratio of the current collector to the negative electrode active material sometimes increases, and the capacity of the battery decreases.
[0551] (16) Electrode density
[0552] The electrode structure when the negative electrode active material is made into an electrode is not particularly limited. The density of the active material on the current collector is preferably 1.0 g / cm 3 More than 1.2 g / cm 3 More preferably, 1.3 g / cm 3 Above, the upper limit is usually 2.0g / cm 3 Below, preferably 1.9 g / cm 3 Below, more preferably 1.8g / cm 3 Below, more preferably 1.7 g / cm 3 If the value exceeds this range, the active material is destroyed, resulting in an increase in the initial irreversible capacity and a decrease in the permeability of the non-aqueous electrolyte to the interface between the current collector and the active material, which leads to a deterioration in the high current density charge and discharge characteristics. In addition, if the value is below this range, the conductivity between the active materials decreases, the battery resistance increases, and the battery capacity per unit volume is sometimes reduced.
[0553] (17) Adhesive
[0554] The binder for binding the active material is not particularly limited as long as it is a material that is stable to the non-aqueous electrolyte or the solvent used in producing the electrode. Specifically, the examples include resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and styrene-propylene rubber; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymers or their hydrogenated products; EPDM (ethylene-propylene-diene terpolymer), styrene-ethylene-butadiene-styrene copolymers, styrene-isobutylene-styrene block copolymers or their hydrogenated products; soft resin polymers such as syndiotactic 1,2 polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. These may be used alone or in combination of two or more in any combination and ratio.
[0555] As a solvent for forming the slurry, as long as it can dissolve or disperse the active material, the binder, and the thickener and conductive agent used as needed, its type is not particularly limited, and any of aqueous solvents or organic solvents can be used. Examples of aqueous solvents include water, alcohol, etc.; examples of organic solvents include N-methylpyrrolidone (NMP), dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N,N-dimethylaminopropylamine, propylene oxide, tetrahydrofuran (THF), toluene, acetone, ether, dimethylacetamide, hexamethylphosphoramide, dimethyl sulfide, benzene, xylene, quinoline, pyridine, methylnaphthalene, hexane, etc. In particular, when using an aqueous solvent, the above-mentioned thickener and dispersant are added at the same time, and a latex such as SBR is used for slurrying. In addition, they can be used alone or in combination of two or more in any combination and ratio.
[0556] The ratio of adhesive to active material is preferably more than 0.1% by mass, particularly preferably more than 0.5% by mass, more preferably more than 0.6% by mass, and its upper limit is usually less than 20% by mass, preferably less than 15% by mass, more preferably less than 10% by mass, and further preferably less than 8% by mass. If it exceeds the scope, the adhesive ratio that will not bring help to battery capacity in the amount of adhesive increases, sometimes resulting in a reduction in battery capacity. In addition, if it is less than the above-mentioned scope, sometimes resulting in a reduction in the strength of the negative electrode. In particular, when the main component contains a rubber-like polymer represented by SBR, the ratio of adhesive to active material is usually more than 0.1% by mass, preferably more than 0.5% by mass, more preferably more than 0.6% by mass, and its upper limit is usually less than 5% by mass, preferably less than 3% by mass, more preferably less than 2% by mass. In addition, when the main component contains a fluorine-based polymer represented by polyvinylidene fluoride, the ratio of the binder to the active material is usually 1% by mass or more, preferably 2% by mass or more, more preferably 3% by mass or more, and the upper limit is usually 15% by mass or less, preferably 10% by mass or less, more preferably 8% by mass or less.
[0557] Thickeners are usually used to adjust the viscosity of the slurry. As thickeners, there are no particular restrictions, and specifically, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof can be cited. They can be used alone or in any combination and ratio. Two or more of them can be used in combination. In addition, when adding a thickener, the ratio of the thickener to the active material is usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 0.6% by mass or more, and its upper limit is usually 5% by mass or less, preferably 3% by mass or less, and more preferably 2% by mass or less. If it is below this range, the coating property is sometimes significantly reduced. If it exceeds this range, the ratio of the active material occupied by the negative electrode active material layer is reduced, sometimes resulting in problems such as reduced battery capacity or increased resistance between the negative electrode active materials.
[0558] (18) Plate orientation ratio
[0559] The plate orientation ratio is preferably 0.001 or greater, more preferably 0.005 or greater, and particularly preferably 0.01 or greater, with the upper limit being the theoretical value, i.e., 0.67 or less. Below this range, high-density charge and discharge characteristics may be degraded.
[0560] The determination of the electrode orientation ratio is carried out as follows. The orientation ratio of the active material of the negative electrode after being pressed into the target density is determined by X-ray diffraction. The specific method is not particularly limited. As a standard method, an asymmetric Pearson VII is used as a profile function to fit the peaks of the (110) diffraction and (004) diffraction of carbon obtained by X-ray diffraction, and the peaks are separated to calculate the integrated intensities of the peaks of (110) diffraction and (004) diffraction, respectively. From the obtained integrated intensities, the ratio represented by the (110) diffraction integrated intensity / (004) diffraction integrated intensity is calculated. The active material orientation ratio of the electrode calculated by this measurement is defined as the electrode orientation ratio.
[0561] The X-ray diffraction measurement conditions here are as follows: In addition, "2θ" represents the diffraction angle.
[0562] Target: Cu (Kα line) graphite monochromator
[0563] Slits: Divergence slit = 1 degree, Receiving slit = 0.1 mm, Scattering slit = 1 degree
[0564] Measurement range and step angle / measurement time
[0565] (110) surface: 76.5 degrees ≤ 2θ ≤ 78.5 degrees 0.01 degrees / 3 seconds
[0566] (004) surface: 53.5 degrees ≤ 2θ ≤ 56.0 degrees 0.01 degrees / 3 seconds
[0567] Sample preparation: Use 0.1mm thick double-sided tape to fix the electrode on the glass plate.
[0568] (19) Impedance
[0569] The negative electrode impedance when charged from the discharge state to 60% of the nominal capacity is preferably 100Ω or less, more preferably 50Ω or less, particularly preferably 20Ω or less, and / or the double layer capacity is preferably 1×10 -6 F or more, more preferably 1×10 -5 F is particularly preferably 1×10 -4 F. This range has good output characteristics and is therefore preferred.
[0570] The negative electrode resistance and double layer capacity are measured according to the following method. The lithium secondary battery to be measured is the following battery: after charging with a current value that can charge to the nominal capacity in 5 hours, it is maintained in a state of no charge or discharge for 20 minutes, and then discharged with a current value that can discharge the nominal capacity in 1 hour, and the capacity at this time is more than 80% of the nominal capacity. For the lithium secondary battery in the above-mentioned discharge state, it is charged to 60% of the nominal capacity with a current value that can charge to the nominal capacity in 5 hours, and the lithium secondary battery is immediately transferred to a spherical container under an argon atmosphere. The lithium secondary battery is quickly disassembled without discharge or short circuit, and the negative electrode is removed. If it is a double-sided coated electrode, the electrode active material on one side is peeled off without damaging the electrode active material on the other side. Two negative electrodes are punched into 12.5mmφ and sandwiched with a separator so that the active material surfaces are facing each other without deviation. 60 μL of non-aqueous electrolyte used in batteries was dripped between the separator and the two negative electrodes to bond them together. The two negative electrode collectors were kept in a non-contact state and the AC impedance method was performed. The measurement was carried out as follows: at a temperature of 25°C, at 10 -2 ~10 5 The complex impedance was measured in a Hz frequency band, and the arc of the negative electrode resistance component of the obtained call·call·plot was approximated to a semicircle to obtain the surface resistance (R) and double layer capacitance (Cd1).
[0571] (20) Area and thickness of negative plate
[0572] The area of the negative electrode plate is not particularly limited, but is typically designed to be slightly larger than the opposing positive electrode plate so that the positive electrode does not protrude beyond the negative electrode. From the perspective of cycle life due to repeated charge and discharge, and to suppress degradation caused by high-temperature storage, it is preferable to have an area as close to that of the positive electrode as possible. This increases the proportion of electrodes that operate uniformly and efficiently, thereby improving performance. Designing this electrode area is particularly important when using at high currents.
[0573] The thickness of the negative electrode plate is designed according to the positive electrode plate used and is not particularly limited. However, the thickness of the composite material layer after deducting the thickness of the metal foil of the core material is usually 15 μm or more, preferably 20 μm or more, and more preferably 30 μm or more. The upper limit is usually 150 μm or less, preferably 120 μm or less, and more preferably 100 μm or less.
[0574] <Negative electrode[1]>
[0575] Hereinafter, the negative electrode [1] “a negative electrode containing two or more carbonaceous materials having different crystallinity as negative electrode active materials” used in the lithium secondary battery of the present invention will be described.
[0576] [Negative electrode active material of negative electrode [1]]
[0577] Next, the negative electrode active material used in the negative electrode [1] will be described.
[0578] [[constitute]]
[0579] The negative electrode active material used in the negative electrode [1] of the lithium secondary battery of the present invention is characterized in that it contains two or more carbonaceous materials with different crystallinity. Here, "containing two or more carbonaceous materials with different crystallinity" means that carbonaceous materials with different crystallinity coexist in the negative electrode. In addition, the coexistence form can be a state in which they exist in the form of individual single particles and are mixed together, or contained in a secondary particle, or a mixture of the above two. In addition, as the negative electrode active material, it is preferred to contain a composite carbonaceous material containing two or more carbonaceous materials with different crystallinity, and it is more preferred that the composite carbonaceous material also contains one or more carbonaceous materials (carbonaceous materials) that are different from the composite carbonaceous material in terms of carbonaceous properties as auxiliary materials.
[0580] The term "contained in a single secondary particle" as used herein refers to a state in which carbonaceous materials of different crystallinity are bound together, a state of physical constraint, a state in which the shape is maintained by electrostatic constraint, and the like. "Physically constrained" refers to a state in which one carbonaceous material of different crystallinity is interspersed with another carbonaceous material, or a state in which the two are attached to each other. "Electrostatic constraint" refers to a state in which one carbonaceous material of different crystallinity is attached to another carbonaceous material through electrostatic energy. Furthermore, "a state of bond constraint" refers to chemical bonds such as hydrogen bonds, covalent bonds, and ionic bonds.
[0581] Among them, in the state where at least part of the surface of the carbonaceous material that becomes the core has an interface with a covering layer of different crystallinity formed by bonding, the movement impedance of lithium between carbonaceous materials with different crystallinity is small, so it is advantageous. The covering layer can be formed by bonding with a material supplied from the outside and / or their modified product, or by modification of the material of the surface portion of the carbonaceous material. Here, the so-called covering means having a chemical bond with at least a part of the interface with the surface of the carbonaceous material, and showing a state of (1) covering the entire surface, (2) covering a local state of carbon particles, (3) selectively covering a part of the surface, and (4) existing in a very small area containing a chemical bond. In addition, the crystallinity can change continuously or discontinuously at the interface.
[0582] The composite carbonaceous material preferably has an interface formed by covering a particulate carbonaceous material with a carbonaceous material having a different crystallinity from the particulate carbonaceous material, and / or an interface formed by bonding a carbonaceous material having a different crystallinity from the particulate carbonaceous material to the particulate carbonaceous material, and the crystallinity of the interface is continuous and / or discontinuously changed. There is no particular limitation on which of the “particulate carbonaceous material” and “carbonaceous material having a different crystallinity from the particulate carbonaceous material” has a higher crystallinity, but when the crystallinity of the particulate carbonaceous material is high, the above-mentioned effect of the present invention can be achieved, so it is preferred.
[0583] Here, the difference in crystallinity is determined by the difference in the interplanar spacing (d002) of the (002) plane measured by X-ray wide-angle diffraction, the difference in Lc, and the difference in La. From the perspective of the effect of the present invention, the difference in crystallinity is preferably more than 0.0002nm in terms of (d002), or more than 1nm in terms of La, or more than 1nm in terms of Lc. In the above range, the difference in (d002) is preferably more than 0.0005nm, more preferably more than 0.001nm, and further preferably more than 0.003nm, with an upper limit generally being less than 0.03nm, preferably less than 0.02nm. If it is lower than this range, the effect caused by the difference in crystallinity sometimes becomes smaller. On the other hand, if it exceeds the above range, the crystallinity of the low-crystalline part tends to become lower, and the irreversible capacity caused thereby may increase. In addition, in the above range, the difference in La or Lc is preferably more than 2nm, more preferably more than 5nm, and further preferably more than 10nm. Generally, graphite cannot be defined above 100nm, and therefore an upper limit cannot be specified. If the content is below this range, the effect of the difference in crystallinity may be reduced.
[0584] A composite carbonaceous material is formed by covering and / or bonding a particulate carbonaceous material with a carbonaceous material having a different crystallinity from that of the particulate carbonaceous material. It is sufficient that either one of the "particulate carbonaceous material" and the "carbonaceous material having a different crystallinity from that of the particulate carbonaceous material" is a graphite-based carbonaceous material and the other is a low-crystalline carbonaceous material. In addition, it is preferred that the "particulate carbonaceous material" is a graphite-based carbonaceous material and the "carbonaceous material having a different crystallinity from that of the particulate carbonaceous material" is a low-crystalline carbonaceous material.
[0585] [[[Particulate carbonaceous material]]]
[0586] As the particulate carbonaceous material, a graphite-based carbonaceous material containing natural graphite and / or artificial graphite, or a carbonaceous material containing at least one of (a), (b) and (c) having slightly lower crystallinity than these materials is preferred.
[0587] (a) a thermal decomposition product of an organic substance selected from coal coke, petroleum coke, furnace black, acetylene black and pitch-based carbon fiber;
[0588] (b)Carbonized organic gases;
[0589] (c) A carbonaceous material obtained by graphitizing part or all of (a) or (b).
[0590] [[[[Graphite-like carbonaceous materials]]]]
[0591] The particulate carbonaceous material is preferably a graphite-based carbonaceous material containing natural graphite and / or artificial graphite. Graphite-based carbonaceous materials refer to various highly crystalline carbonaceous materials having a (002) plane spacing (d002) of less than 0.340 nm as measured by wide-angle X-ray diffraction.
[0592] Specific examples of graphite-based carbonaceous materials include powders of natural graphite, artificial graphite, or mechanically crushed products thereof, reheated products thereof, reheated products of expanded graphite, or high-purity purified products of these graphites. Specific examples of the aforementioned artificial graphite include those obtained by graphitizing one or more organic substances, typically at a sintering temperature of approximately 2500°C to 3200°C, and then pulverizing the resulting powder using an appropriate pulverization method. The organic substances are preferably selected from the group consisting of coal tar pitch, coal-based heavy oil, atmospheric residual oil, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymers, polyphenylene sulfide, polyphenylene ether, furfuryl alcohol resin, phenolic resin, and imide resin.
[0593] (Physical properties of graphite-based carbonaceous materials)
[0594] The properties of the graphite-based carbonaceous material preferably satisfy any one or more of the following (1) to (11) simultaneously.
[0595] (1) X-ray parameters
[0596] The d value (interlayer distance) of the lattice plane (002) of the graphite-like carbonaceous material obtained by X-ray diffraction using the learning vibration method is preferably 0.335nm or more. In addition, from the definition point of view, the lower limit is less than 0.340nm, preferably less than 0.337nm. If the d value is too large, the crystallinity is reduced, and the initial irreversible capacity is sometimes increased. On the other hand, 0.335 is the theoretical value of graphite. In addition, the crystallite size (Lc) of the carbon material obtained by X-ray diffraction using the learning vibration method is generally 30nm or more, preferably 50nm or more, and more preferably in the range of 100nm or more. If it is below this range, the crystallinity is reduced, and it is possible to increase the initial irreversible capacity.
[0597] (2) Ash content
[0598] The ash content contained in the graphite-based carbonaceous material is preferably less than 1% by mass, more preferably less than 0.5% by mass, particularly preferably less than 0.1% by mass, relative to the total mass of the graphite-based carbonaceous material, and the lower limit is 1 ppm or more. If the above range is exceeded, the degradation of battery performance caused by the reaction with the electrolyte during charge and discharge cannot be ignored. If it is below this range, a long time and energy and equipment for preventing pollution are required in the manufacture, and sometimes the cost will rise.
[0599] (3) Volume-based average particle size
[0600] The volume reference average particle size of graphite-based carbonaceous material is the volume reference average particle size (median particle size) sought to by laser diffraction / scattering method, usually more than 1 μm, preferably more than 3 μm, more preferably more than 5 μm, and more preferably more than 7 μm. In addition, its upper limit is usually less than 100 μm, preferably less than 50 μm, more preferably less than 40 μm, more preferably less than 30 μm, and particularly preferably less than 25 μm. If it is less than the above range, the irreversible capacity increases, sometimes resulting in a loss of initial battery capacity. In addition, if it exceeds the above range, when an electrode pad is made, it is easy to form an uneven coating surface, which is sometimes not preferred in a battery manufacturing process.
[0601] In the present invention, the volume-based average particle size is defined by the median particle size, which is measured by the following method: dispersing carbon powder in a 0.2 mass % aqueous solution (about 1 mL) of polyoxyethylene (20) sorbitan monolaurate as a surfactant and measuring it using a laser diffraction / scattering particle size distribution meter (for example, LA-700 manufactured by Horiba, Ltd.).
[0602] (4) Raman R value, Raman half-value width
[0603] The R value of the graphite-like carbonaceous material measured using argon ion laser Raman spectroscopy is generally more than 0.01, preferably more than 0.03, more preferably more than 0.10, and its upper limit is generally less than 0.60, preferably less than 0.40. If the R value is lower than the range, the crystallinity of the particle surface is too high, and the site of the interlayer is sometimes reduced as charge and discharge Li enters. That is, charge acceptance is sometimes reduced. On the other hand, if it exceeds the range, the crystallinity of the particle surface is reduced, and the reactivity with the electrolyte is increased, sometimes resulting in a decrease in efficiency or an increase in the gas produced.
[0604] In addition, graphite-like carbonaceous substances have a -1 There is no particular limit on the Raman half-value width near 10 cm, but it is usually 10 cm -1 Above, preferably 15cm-1 Above, the upper limit is usually 60cm -1 Below, preferably 45cm -1 Below, more preferably 40cm -1 The Raman half-width is within the range below. If the Raman half-width is below this range, the crystallinity of the particle surface is too high, and the number of sites for Li to enter the interlayer during charging and discharging may decrease. In other words, the charge acceptance may be reduced. On the other hand, if it is above this range, the crystallinity of the particle surface decreases, and the reactivity with the electrolyte increases, which may lead to reduced efficiency or increased gas generation.
[0605] The Raman spectrum is measured as follows: using a Raman spectrometer (e.g., a Raman spectrometer manufactured by JASCO Corporation), the sample is allowed to fall naturally and fill a measuring cell. The sample surface in the cell is irradiated with an argon ion laser while the cell is rotated in a plane perpendicular to the laser. The obtained Raman spectrum is measured at 1580 cm -1 Nearby peak P A Intensity I A and 1360cm -1 Nearby peak P B Intensity I B , calculate its intensity ratio R (R=I B / I A ), which is defined as the Raman R value of the carbon material. In addition, the Raman spectrum obtained by measurement is at 1580cm -1 Nearby peak P A The half-value width of the carbon material is defined as the half-value width of the Raman ions.
[0606] In addition, the Raman measurement conditions here are as follows.
[0607] Argon ion laser wavelength: 514.5nm
[0608] Laser power on the sample: 15-25mW
[0609] Resolution: 10-20cm -1
[0610] Measuring range: 1100cm -1 ~1730cm -1
[0611] R value, half-value width analysis: background processing
[0612] Smoothing: simple averaging, convolution 5 points
[0613] (5) BET specific surface area
[0614] The specific surface area of the graphite-based carbonaceous material of the present invention measured by the BET method is usually 0.1 m 2 / g or more, preferably 0.7m 2 / g or more, more preferably 1m 2 / g or more, more preferably 1.5m 2 / g or more. Its upper limit is usually 100m 2 / g or less, preferably 25m 2 / g or less, more preferably 15m 2 / g or less, more preferably 10m 2 / g or less. If the specific surface area value is lower than the above range, when used as a negative electrode, the lithium acceptance deteriorates during charging, and lithium is easily precipitated on the electrode surface. On the other hand, if it exceeds the above range, when used as a negative electrode material, the reactivity with the electrolyte increases, the gas generated becomes more, and sometimes it is difficult to obtain a preferred battery.
[0615] The BET specific surface area is defined as a value measured as follows: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), the sample is pre-dried at 350°C for 15 minutes under nitrogen flow, and then measured by the nitrogen adsorption BET 1-point method using a gas flow method using a nitrogen-helium mixed gas in which the relative pressure of nitrogen relative to atmospheric pressure is accurately adjusted to 0.3.
[0616] (6) Micropore distribution
[0617] As a graphite-based carbonaceous material, the void in the particle equivalent to 0.01 μm to 1 μm in diameter obtained by mercury porosimeter (mercury intrusion method), the amount of concave and convex caused by the unevenness of the particle surface is usually 0.01 mL / g or more, preferably 0.05 mL / g or more, more preferably 0.1 mL / g or more, and the upper limit is usually 0.6 mL / g or less, preferably 0.4 mL / g or less, more preferably 0.3 mL / g or less. If it exceeds this range, a large amount of adhesive is needed when manufacturing the pole plate. On the other hand, if it is lower than this range, the high current density charge and discharge characteristics are reduced, and the relaxation effect of the electrode expansion and contraction during charge and discharge can sometimes not be obtained.
[0618] In addition, total micropore volume is preferably more than 0.1mL / g, more preferably more than 0.25mL / g, and its upper limit is usually below 10mL / g, preferably below 5mL / g, more preferably below 2mL / g scope.If it exceeds this scope, then when making substrate, sometimes need a large amount of adhesives.If it is lower than this scope, then when making pole plate, sometimes can not obtain the dispersion effect of thickener or binding agent.
[0619] In addition, the average pore diameter is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.5 μm or more. The upper limit is usually 50 μm or less, preferably 20 μm or less, and more preferably 10 μm or less. If it exceeds this range, a large amount of binder may be required. On the other hand, if it is below this range, the high current density charge and discharge characteristics may be reduced.
[0620] As a device for a mercury porosimeter, a mercury porosimeter (autopore9520; manufactured by Micrometritics) can be used. About 0.2 g of the sample (negative electrode material) is weighed, sealed in a powder container, and degassed for 10 minutes at room temperature and vacuum (below 50 μmHg) to perform pretreatment. Next, the pressure is reduced to 4 psia (about 28 kPa), mercury is introduced, and the pressure is increased in stages from 4 psia (about 28 kPa) to 40,000 psia (about 280 MPa), and then the pressure is reduced to 25 psia (about 170 kPa). The number of stages during the pressure increase is more than 80 stages, and in each stage, the amount of mercury intrusion is measured after a 10-second equilibrium time. The micropore distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula. In addition, the surface tension (γ) of mercury is 485 dyne / cm, and the contact angle (φ) is 140°. The average micropore diameter used was the micropore diameter at which the cumulative micropore volume reached 50%.
[0621] (7) Circularity
[0622] Circularity is used as the degree of sphericity of graphite-based carbonaceous materials. The circularity of particles of graphite-based carbonaceous materials with a particle size in the range of 3 to 40 μm is preferably 0.1 or greater, particularly preferably 0.5 or greater, more preferably 0.8 or greater, further preferably 0.85 or greater, and most preferably 0.9 or greater. A large circularity improves high current density charge and discharge characteristics, and is therefore preferred. Circularity is defined by the following formula: when the circularity is 1, it becomes a theoretical true sphere.
[0623] Circularity = (the circumference of an equivalent circle with the same area as the particle's projected shape) / (the actual circumference of the particle's projected shape)
[0624] The circularity value is determined as follows: using, for example, a flow particle image analyzer (e.g., FPIA manufactured by Sysmex Industrial), about 0.2 g of a sample is dispersed in a 0.2 mass % aqueous solution (about 50 mL) of polyoxyethylene (20) sorbitan monolaurate as a surfactant, and after irradiating the sample with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, the detection range is designated as 0.6 to 400 μm, and particles with a particle size range of 3 to 40 μm are measured.
[0625] There are no particular limitations on the method for improving circularity, but spheroidization is preferred because it allows for uniform interparticle shape when fabricated into an electrode body. Examples of spheroidization include mechanical approaches to sphericity through the application of shear or compression forces, and mechanical / physical granulation of multiple fine particles using a binder or the inherent adhesive force of the particles.
[0626] (8) True density
[0627] The true density of graphite-like carbonaceous materials is usually 2g / cm 3 Above, preferably 2.1 g / cm 3 More than 2.2 g / cm 3 More preferably, 2.22 g / cm 3 Above, the upper limit is 2.26g / cm 3 Below. The upper limit is the theoretical value of graphite. If it is below this range, the crystallinity of the carbon is too low, and the initial irreversible capacity may increase. In the present invention, the true density is defined as the value measured by the liquid phase replacement method (hydrometer method) using butanol.
[0628] (9) Tap density
[0629] The tap density of graphite-based carbonaceous materials is usually 0.1 g / cm 3 Above, preferably 0.5g / cm 3 More than 0.7 g / cm 3 Above, particularly preferably 0.9 g / cm 3 In addition, the upper limit is preferably 2g / cm 3 Below, more preferably 1.8g / cm 3 Below, particularly preferably 1.6 g / cm 3 If the tap density is below this range, when used as a negative electrode, it is difficult to increase the packing density, and a high-capacity battery may not be obtained. On the other hand, if it is above this range, the gaps between the particles in the electrode are too small, making it difficult to ensure the conductivity between the particles, and sometimes it is difficult to obtain preferred battery characteristics.
[0630] In the present invention, the tap density is defined as follows: the sample is passed through a sieve with an aperture of 300 μm and falls on a surface of 20 cm 3 The sample is vibrated in a compaction container until the upper end surface of the container is filled. Then, a powder density meter (for example, Tap densor manufactured by Seishin Enterprise Co., Ltd.) is used to perform 1000 vibrations with a stroke length of 10 mm. The bulk density at this time is defined as the tap density.
[0631] (10) Orientation ratio (powder)
[0632] The orientation ratio of the graphite-based carbonaceous material is usually 0.005 or more, preferably 0.01 or more, more preferably 0.015 or more, and the upper limit is theoretically 0.67 or less. If it is below this range, the high-density charge and discharge characteristics may be reduced.
[0633] The orientation ratio was determined by X-ray diffraction. Using an asymmetric Pearson VII distribution function, the (110) and (004) diffraction peaks of carbon obtained by X-ray diffraction were fitted, and the peaks were separated. The integrated intensities of the (110) and (004) diffraction peaks were calculated. From the obtained integrated intensities, the ratio ((110) diffraction integrated intensity / (004) diffraction integrated intensity) was calculated, and this ratio was defined as the active material orientation ratio.
[0634] The X-ray diffraction measurement conditions here are as follows: In addition, "2θ" represents the diffraction angle.
[0635] Target: Cu (Kα ray) graphite monochromator
[0636] Slit:
[0637] Divergence slit = 1 degree, receiving slit = 0.1 mm, scattering slit = 1 degree
[0638] Measurement range and step angle / measurement time
[0639] (110) surface: 76.5 degrees ≤ 2θ ≤ 78.5 degrees 0.01 degrees / 3 seconds
[0640] (004) surface: 53.5 degrees ≤ 2θ ≤ 56.0 degrees 0.01 degrees / 3 seconds
[0641] (11) Aspect ratio (powder)
[0642] The aspect ratio of graphite-based carbonaceous materials is theoretically greater than 1, and the upper limit is usually less than 10, preferably less than 8, and more preferably less than 5. If the upper limit is exceeded, streaks may be generated when the electrode plate is made, a uniform coating surface may not be obtained, and high current density charge and discharge characteristics may sometimes be reduced.
[0643] The aspect ratio is expressed as the ratio A / B of the longest diameter A of a carbon material particle to its shortest diameter B, perpendicular thereto, when observed in three dimensions. Observation of the carbon particles was performed using a scanning electron microscope capable of magnification. Fifty graphite particles were randomly selected and fixed to the end surface of a metal with a thickness of 50 μm or less. The stage holding the sample was rotated and tilted, and the A and B values of each particle were measured. The average value of A / B was then calculated.
[0644] [[[[Low crystalline carbonaceous material]]]]
[0645] The low-crystalline carbonaceous material refers to a low-crystalline carbonaceous material having a (002) plane spacing (d002) of 0.340 nm or more as measured by wide-angle X-ray diffraction.
[0646] (Composition of low-crystalline carbonaceous material)
[0647] The "carbonaceous material having a different crystallinity from the particulate carbonaceous material" is preferably a low-crystalline carbonaceous material having a lower crystallinity than the particulate carbonaceous material. In addition, the following carbides (d) or (e) are particularly preferred.
[0648] (d) a carbonizable organic matter selected from coal-based heavy oil, straight-run heavy oil, decomposed petroleum heavy oil, aromatic hydrocarbons, N-ring compounds, S-ring compounds, polyphenylene, organic synthetic polymers, natural polymers, thermoplastic resins, and thermosetting resins;
[0649] (e) A solution obtained by dissolving these carbonizable organic substances in a low-molecular organic solvent.
[0650] As coal-based heavy oil, coal tar pitch from soft pitch to hard pitch or dry distillation liquefied oil are preferred; as straight-run heavy oil, atmospheric residual oil, vacuum residual oil, etc. are preferred; as decomposition-based petroleum heavy oil, ethylene tar produced as a by-product during thermal decomposition of crude oil, naphtha, etc. are preferred; as aromatic hydrocarbons, acenaphthylene, decacyclene, anthracene, phenanthrene, etc. are preferred; as N-ring compounds, phenazine, acridine, etc. are preferred; as S-ring compounds, thiophene, dithiophene, etc. are preferred; as polyphenyl, biphenyl, terphenyl, etc. are preferred; as organic polymers, polyvinyl chloride, polyvinyl alcohol, polyvinyl butyral, their insoluble treated products, polyacrylonitrile, polypyrrole, polythiophene, polystyrene, etc. are preferred; as natural polymers, polysaccharides such as cellulose, lignin, mannan, polygalacturonic acid, chitosan, sucrose, etc. are preferred; as thermoplastic resins, polyphenylene sulfide, polyphenylene ether, etc. are preferred; as thermosetting resins, furfuryl alcohol resins, phenolic resins, imide resins, etc. are preferred.
[0651] The "carbonaceous material having different crystallinity from the particulate carbonaceous material" is preferably a carbide of the aforementioned "carbonizable organic material." Furthermore, a carbide obtained by dissolving the "carbonizable organic material" in a low-molecular organic solvent such as benzene, toluene, xylene, quinoline, or n-hexane to obtain a solution thereof is also preferred. Furthermore, the "carbonaceous material having different crystallinity from the particulate carbonaceous material" is preferably a carbide of coal coke or petroleum coke.
[0652] As the above-mentioned (d) or (e), a liquid state is particularly preferred. That is, from the viewpoint of forming an interface with the graphite-based carbonaceous material portion, carbonization is preferably performed in a liquid phase.
[0653] (Physical properties of low-crystalline carbonaceous materials)
[0654] The physical properties of the low-crystalline carbonaceous material preferably satisfy any one or more of the following (1) to (5). In addition, a low-crystalline carbonaceous material exhibiting these physical properties may be used alone, or two or more may be used in any combination and ratio.
[0655] (1) X-ray parameters
[0656] For low crystalline carbonaceous material part, the d value (interlayer distance) of the lattice plane (002 face) obtained by adopting the X-ray diffraction of the learning vibration method is defined as more than 0.340nm, preferably more than 0.340nm, particularly preferably more than 0.341nm. In addition, its upper limit is less than 0.380nm, particularly preferably less than 0.355nm, more preferably less than 0.350. If the d value is too large, a surface with significantly low crystallinity is formed, which sometimes increases the irreversible capacity, and if the d value is too small, the effect of the improved charge acceptance obtained by arranging low crystalline carbonaceous material on the surface becomes smaller, so that the effect of the present invention becomes smaller. In addition, the crystallite size (Lc) of the carbon material obtained by adopting the X-ray diffraction of the learning vibration method is generally more than 1nm, preferably in the range of more than 1.5nm. If it is below the range, the crystallinity is reduced, and the increase of the initial irreversible capacity is sometimes increased.
[0657] (2) Ash content
[0658] The ash content of the low-crystalline carbonaceous material portion is preferably 1% by mass or less relative to the total mass of the composite carbonaceous material, more preferably 0.5% by mass or less, particularly preferably 0.1% by mass or less, and as a lower limit, preferably 1 ppm or more. If the above range is exceeded, the degradation of battery performance caused by the reaction with the electrolyte during charge and discharge cannot be ignored. If it is below this range, a long time and energy as well as equipment for preventing pollution are required in the manufacture, and sometimes the cost will increase.
[0659] (3) Raman R value, Raman half-value width
[0660] The R value of the low crystalline carbonaceous material portion measured using argon ion laser Raman spectroscopy is generally more than 0.5, preferably more than 0.7, more preferably more than 0.9, and its upper limit is generally less than 1.5, preferably less than 1.2. If the R value is lower than the range, the crystallinity of the particle surface is too high, and the site of the interlayer is sometimes reduced as the charge and discharge Li enters. That is, the charge acceptance is sometimes reduced. In addition, after being coated on the collector, when the negative electrode is made high-densified by pressing, the crystallization is easily oriented in a direction parallel to the electrode plate, sometimes resulting in a reduction in load characteristics. On the other hand, if it exceeds the range, the crystallinity of the particle surface is reduced, and the reactivity with the electrolyte is increased, sometimes resulting in a reduction in efficiency or an increase in the gas produced.
[0661] In addition, the low-crystalline carbonaceous material part is at 1580 cm -1 There is no particular limit on the Raman half-value width near 40 cm. -1 Above, preferably 50cm -1 Above, the upper limit is usually 100cm -1 Below, preferably 90cm -1 Below, more preferably 80cm -1 The following range. If the Raman half-value width is lower than this range, the crystallinity of the particle surface is too high, and the sites where Li enters the interlayer sometimes decrease with charging and discharging. That is, the charge acceptance is sometimes reduced. In addition, after coating on the collector, when the negative electrode is made high-density by pressing, the crystals are easily oriented in a direction parallel to the electrode plate, sometimes resulting in reduced load characteristics. On the other hand, if it exceeds this range, the crystallinity of the particle surface is reduced, and the reactivity with the electrolyte is increased, sometimes resulting in reduced efficiency or increased gas generation.
[0662] (4) True density
[0663] The true density of low-crystalline carbonaceous material is usually 1.4 g / cm 3 Above, preferably 1.5 g / cm 3 More than 1.6 g / cm 3 More preferably, 1.7 g / cm 3 Above, the upper limit is usually 2.1g / cm 3 Below, preferably 2g / cm 3 If the carbon content exceeds this range, the charge acceptance may be impaired. If the carbon content is below this range, the crystallinity of the carbon may be too low, and the initial irreversible capacity may increase.
[0664] (5) Orientation ratio (powder)
[0665] The orientation ratio of the low-crystalline carbonaceous material portion is generally more than 0.005, preferably more than 0.01, more preferably more than 0.015, and its upper limit is less than the theoretical value of 0.67. If it is lower than this range, the high-density charge-discharge characteristics are sometimes reduced, which is not preferred. The orientation ratio is determined by X-ray diffraction. Using asymmetric Pearson VII as a distribution function, the peaks of (110) diffraction and (004) diffraction obtained by X-ray diffraction are fitted, and peak separation is performed to calculate the integrated intensity of the peaks of (110) diffraction and (004) diffraction, respectively. The ratio represented by (110) diffraction integrated intensity / (004) diffraction integrated intensity is calculated from the obtained integrated intensity, and the ratio is defined as the active material orientation ratio.
[0666] [[[Compound carbonaceous material]]]
[0667] The composite carbonaceous material used in the negative electrode [1] of the lithium secondary battery of the present invention preferably contains a "particulate carbonaceous material" and a "carbonaceous material having a different crystallinity from the particulate carbonaceous material". In this case, any one of the two materials can be a graphite-based carbonaceous material and the other a low-crystalline carbonaceous material. In addition, it is preferred that the "particulate carbonaceous material" is a graphite-based carbonaceous material and the "carbonaceous material having a different crystallinity from the particulate carbonaceous material" is a low-crystalline carbonaceous material.
[0668] In the composite carbonaceous material, the mass ratio of the graphite carbonaceous material and the low crystalline carbonaceous material is preferably 50 / 50 or more, more preferably 80 / 20 or more, particularly preferably 90 / 10 or more, and preferably 99.9 / 0.1 or less, more preferably 99 / 1 or less, and particularly preferably 98 / 2 or less. If it exceeds the above range, the effect of the carbonaceous material with two kinds of crystallinity can sometimes not be obtained. If it is lower than the above range, the initial irreversible capacity shows an increased tendency, and sometimes there are problems in the battery design. The graphite carbonaceous material is 50% by mass or more relative to the total composite carbonaceous material.
[0669] (Physical properties of composite carbonaceous materials)
[0670] The composite carbonaceous material preferably satisfies any one or more of the following (1) to (11) simultaneously. A single composite carbonaceous material exhibiting these properties may be used alone, or two or more composite carbonaceous materials may be used in any combination and ratio.
[0671] (1) X-ray parameters
[0672] The d value (interlayer distance) of the lattice plane (002) of the composite carbonaceous material obtained by the X-ray diffraction of the learning vibration method is preferably more than 0.335nm, and is generally less than 0.350nm, preferably less than 0.345nm, more preferably less than 0.340nm. In addition, the crystallite size (Lc) of the carbon material obtained by the X-ray diffraction of the learning vibration method is generally more than 1.5nm, preferably more than 3.0nm. If it is less than the range, the crystallinity is reduced, and it is possible to increase the increase of the initial irreversible capacity.
[0673] (2) Ash content
[0674] The ash content of the composite carbonaceous material is preferably less than 1% by mass relative to the total mass of the composite carbonaceous material, more preferably less than 0.5% by mass, particularly preferably less than 0.1% by mass, and as its lower limit, preferably more than 1 ppm. If the above range is exceeded, the degradation of battery performance caused by the reaction with the electrolyte during charge and discharge cannot be ignored. If it is below this range, a long time and energy and equipment for preventing pollution are required in the manufacture, and sometimes the cost will rise.
[0675] (3) Volume-based average particle size
[0676] The volume reference average particle size of the composite carbonaceous material is the average particle size (median particle size) of the volume reference sought to by laser diffraction / scattering method, usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, further preferably 7 μm or more. In addition, its upper limit is usually 100 μm or less, preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, particularly preferably 25 μm or less. If it is less than the above range, the irreversible capacity increases, sometimes resulting in a loss of initial battery capacity. In addition, if it exceeds the above range, it is easy to form an uneven coating surface when making an electrode pad, which is sometimes not preferred in the battery manufacturing process.
[0677] (4) Raman R value, Raman half-value width
[0678] The R value of the composite carbonaceous material measured using argon ion laser Raman spectroscopy is generally more than 0.03, preferably more than 0.10, more preferably more than 0.15, and its upper limit is generally less than 0.60, preferably the range of less than 0.50. If the R value is lower than the range, the crystallinity of the particle surface is too high, and the site of the interlayer is sometimes reduced as the charge and discharge Li enters. That is, the charge acceptance is sometimes reduced. In addition, after being coated on the collector, when the negative electrode is made high-densified by pressing, the crystallization is easily oriented in a direction parallel to the electrode plate, sometimes resulting in a reduction in load characteristics. On the other hand, if it exceeds the range, the crystallinity of the particle surface is reduced, and the reactivity with the electrolyte is increased, sometimes resulting in a reduction in efficiency or an increase in the gas produced.
[0679] In addition, the composite carbonaceous matter is at 1580 cm -1 There is no particular limit on the Raman half-value width near the -1 Above, preferably 20cm -1 Above, the upper limit is usually 70cm -1 Below, preferably 60cm -1 Below, more preferably 50cm -1 The following range. If the Raman half-value width is lower than this range, the crystallinity of the particle surface is too high, and the sites where Li enters the interlayer sometimes decrease with charge and discharge. That is, the charge acceptance is sometimes reduced. In addition, after coating on the collector, when the negative electrode is made high-density by pressing, the crystals are easily oriented in a direction parallel to the electrode plate, sometimes resulting in a decrease in load characteristics. On the other hand, if it exceeds this range, the crystallinity of the particle surface is reduced, and the reactivity with the electrolyte is increased, sometimes resulting in a decrease in efficiency or an increase in gas generated.
[0680] (5) BET specific surface area
[0681] The specific surface area of the composite carbonaceous material of the present invention measured by the BET method is usually 0.1 m 2 / g or more, preferably 0.7m 2 / g or more, more preferably 1m 2 / g or more, more preferably 1.5m 2 / g or more. Its upper limit is usually 100m 2 / g or less, preferably 25m 2 / g or less, more preferably 15m 2 / g or less, more preferably 10m 2 / g or less. If the specific surface area value is below the above range, when used as a negative electrode material, the lithium acceptance becomes poor during charging, and lithium is easily deposited on the electrode surface. On the other hand, if it exceeds the above range, when used as a negative electrode material, the reactivity with the electrolyte increases, the gas generated becomes more, and sometimes it is difficult to obtain a preferred battery.
[0682] (6) Micropore distribution
[0683] As a composite carbonaceous material, the void in the particle equivalent to 0.01 μm to 1 μm in diameter obtained by mercury porosimeter (mercury intrusion method), the amount of concave and convex caused by the unevenness of the particle surface is usually 0.01 mL / g or more, preferably 0.05 mL / g or more, more preferably 0.1 mL / g or more, and its upper limit is usually 0.6 mL / g or less, preferably 0.4 mL / g or less, more preferably 0.3 mL / g or less. If it exceeds this range, a large amount of adhesive is needed when making the pole plate. If it is lower than this range, the high current density charge and discharge characteristics are reduced, and the relaxation effect of the electrode expansion and contraction during charge and discharge can sometimes not be obtained.
[0684] In addition, the total micropore volume is preferably 0.1 mL / g or more, more preferably 0.25 mL / g or more, and its upper limit is usually 10 mL / g or less, preferably 5 mL / g or less, more preferably 2 mL / g or less. If it exceeds this range, a large amount of adhesive is sometimes required. If it is less than this range, the dispersion effect of the thickener or binder cannot sometimes be obtained when the pole plate is made.
[0685] The average pore diameter is preferably 0.05 μm or larger, more preferably 0.1 μm or larger, and even more preferably 0.5 μm or larger. The upper limit is generally 80 μm or smaller, preferably 50 μm or smaller, and more preferably 20 μm or smaller. Exceeding this range may require a large amount of binder. Below this range may result in reduced high current density charge and discharge characteristics.
[0686] (7) Circularity
[0687] Circularity is used as the degree of sphericity of the composite carbonaceous material. The circularity of particles of the composite carbonaceous material with a particle size range of 3 to 40 μm is preferably 0.85 or greater, more preferably 0.87 or greater, and even more preferably 0.9 or greater. A higher circularity is preferred because it improves high current density charge and discharge characteristics.
[0688] (8) True density
[0689] The true density of composite carbonaceous materials is usually 1.9g / cm 3 Above, preferably 2g / cm 3 More than 2.1 g / cm 3 More preferably, 2.2 g / cm 3 Above, the upper limit is 2.26g / cm 3 The upper limit is the theoretical value of graphite. If it is below this range, the crystallinity of carbon is too low, and the initial irreversible capacity may increase.
[0690] (9) Tap density
[0691] The tap density of composite carbonaceous materials is usually 0.1g / cm 3 Above, preferably 0.5g / cm 3 More than 0.7 g / cm 3 Above, particularly preferably 1 g / cm 3 In addition, the upper limit is preferably 2g / cm 3 Below, more preferably 1.8g / cm 3 Below, particularly preferably 1.6 g / cm 3 Below. If the tap density is lower than this range, when used as a negative electrode, the packing density is difficult to improve, and sometimes a high-capacity battery cannot be obtained. On the other hand, if it exceeds this range, the gaps between the particles in the electrode are too few, making it difficult to ensure the conductivity between the particles, and sometimes it is difficult to obtain preferred battery characteristics. The tap density is measured by the same method as described above and is defined according to this method.
[0692] (10) Orientation ratio (powder)
[0693] The orientation ratio of the composite carbonaceous material is usually 0.005 or more, preferably 0.01 or more, more preferably 0.015 or more, and its upper limit is theoretically 0.67 or less. Below this range, high-density charge and discharge characteristics may be reduced.
[0694] (11) Aspect ratio (powder)
[0695] The aspect ratio of the composite carbonaceous material is theoretically greater than 1, and its upper limit is usually less than 10, preferably less than 8, and more preferably less than 5. If the upper limit is exceeded, streaks may sometimes be generated when the electrode plate is made, a uniform coating surface may not be obtained, and high current density charge and discharge characteristics may be reduced.
[0696] (Method for producing composite carbonaceous material)
[0697] The method for producing these composite carbonaceous materials is not particularly limited, and examples thereof include the following methods.
[0698] The composite of graphite-like carbonaceous material and low-crystalline carbonaceous material can be achieved by the following methods: directly using a carbon precursor for obtaining low-crystalline carbonaceous material, heating a mixture of carbon precursor and graphite-like carbonaceous material powder to obtain a composite powder; partially carbonizing the above-mentioned carbon precursor, pre-preparing low-crystalline carbonaceous material powder, and then mixing it with graphite-like carbonaceous material powder, and heating it to perform a composite method; pre-preparing the above-mentioned low-crystalline carbonaceous material powder, mixing graphite-like carbonaceous material powder, low-crystalline carbonaceous material powder and carbon precursor, and heating to perform a composite method, etc. In addition, in the latter two methods of pre-preparing low-crystalline carbonaceous material powder, it is preferred to use low-crystalline carbonaceous material particles having an average particle size of less than one-tenth of the average particle size of the graphite-like carbonaceous material. In addition, the following method can also be used: by applying mechanical energy such as crushing to the pre-prepared low-crystalline carbonaceous material and graphite-like carbonaceous material, a structure in which one substance is mixed with another substance, or a structure of electrostatic adhesion is prepared.
[0699] Preferably, a mixture of graphite-like carbonaceous material particles and a carbon precursor is heated to obtain an intermediate substance, or a mixture of graphite-like carbonaceous material particles and low-crystalline carbonaceous material particles is heated to obtain an intermediate substance, which is then carbonized, sintered, and pulverized to finally obtain a composite carbonaceous material in which low-crystalline carbonaceous material is composited in graphite-like material particles.
[0700] The production process for obtaining the composite carbonaceous material is divided into the following four steps.
[0701] Step 1: Using various commercially available mixers or kneaders, (graphite carbonaceous material particles or (mixed particles of graphite carbonaceous material particles and low-crystalline carbonaceous material particles)) and a carbon precursor of low-crystalline carbonaceous material particles and, if necessary, a solvent are mixed to obtain a mixture.
[0702] Step 2: The mixture is heated to obtain an intermediate product from which the solvent and volatile components generated from the carbon precursor have been removed. This heating may be performed while stirring the mixture, if necessary. Even if any volatile components remain, they can be removed in the subsequent step 3.
[0703] Step 3: The mixture or intermediate material is heated to 400° C. to 3200° C. in an inert gas atmosphere such as nitrogen, carbon dioxide, or argon to obtain a graphite-low-crystalline carbonaceous material composite material.
[0704] Step 4: The composite material is subjected to powder processing such as pulverization, crushing, and classification as needed.
[0705] Of these steps, the second and fourth steps may be omitted depending on circumstances, or the fourth step may be performed before the third step. However, when the fourth step is performed before the third step, powder processing such as pulverization, crushing, and classification may be performed again as necessary to obtain a composite carbonaceous material.
[0706] In addition, as the heat treatment condition of the third step, the thermal history temperature condition is important. The lower limit of the temperature varies depending on the type of carbon precursor and the thermal history, but is usually above 400°C, preferably above 900°C. On the other hand, the upper limit temperature can reach a temperature at which the structural order of the crystalline structure of the graphite-like carbonaceous material particle core is basically not exceeded. Therefore, as the upper limit temperature of the heat treatment, it is usually below 3200°C, preferably below 2000°C, and more preferably below 1500°C. Under such heat treatment conditions, the heating rate, cooling rate, heat treatment time, etc. can be arbitrarily set according to the purpose. In addition, it is also possible to heat the reactor in a relatively low temperature region and then heat it to a specified temperature. In addition, the reactor used in this process may be a batch type or a continuous type, and may be one or more reactors.
[0707] [[Secondary material mixing]]
[0708] In addition to the above-mentioned composite carbonaceous material, the negative electrode active material of the lithium secondary battery of the present invention contains one or more carbonaceous materials (carbonaceous materials) that are different from the above-mentioned composite carbonaceous material in terms of carbonaceous properties, thereby further seeking to improve battery performance. The "physical properties of carbonaceous" mentioned here refer to one or more characteristics of X-ray diffraction parameters, median particle size, aspect ratio, BET specific surface area, orientation ratio, Raman R value, tap density, true density, micropore distribution, circularity, and ash content. In addition, as a preferred embodiment, it can be cited that the volume-based particle size distribution is asymmetric when the median particle size is the center, contains two or more carbonaceous materials with different Raman R values, or has different X-ray parameters. As an example of its effect, it can be cited that the resistance is reduced by containing graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; amorphous carbon such as needle coke as auxiliary materials. They can be used alone or in combination with two or more in any combination and in any proportion. When added as an auxiliary material, its addition is more than 0.1 mass %, preferably more than 0.5 mass %, more preferably more than 0.6 mass %, and its upper limit is less than 80 mass %, preferably less than 50 mass %, more preferably less than 40 mass %, and further preferably less than 30 mass %. If it is less than this scope, it is sometimes difficult to obtain the effect of improved conductivity. If it exceeds the above range, it sometimes leads to an increase in initial irreversible capacity.
[0709] [Making the negative electrode[1]]
[0710] The negative electrode [1] can be manufactured by a conventional method and can be formed in the same manner as described above. The current collector, the thickness ratio of the current collector and the active material layer, the electrode density, the binder, the electrode plate orientation ratio, the impedance, etc. are also the same as described above.
[0711] <Negative electrode[2]>
[0712] Next, the negative electrode [2] used in the lithium secondary battery of the present invention is described. The negative electrode contains amorphous carbon as an active material. The amorphous carbon has a (002) plane spacing (d002) of 0.337 nm or more, a crystallite size (Lc) of 80 nm or less, and an argon ion laser Raman spectroscopy at 1360 cm -1 The peak intensity relative to 1580 cm -1 The Raman R value defined by the ratio of the peak intensities is 0.2 or greater.
[0713] [Negative electrode active material of negative electrode [2]]
[0714] Next, the negative electrode active material used in the negative electrode [2] is described.
[0715] The negative electrode active material used in the negative electrode [2] of the lithium secondary battery of the present invention is an amorphous carbon material containing at least the following (a), (b) and (c).
[0716] (a) the interplanar spacing (d002) of the (002) planes measured by wide-angle X-ray diffraction is 0.337 nm or greater;
[0717] (b) The crystallite size Lc of the (002) plane measured by wide-angle X-ray diffraction is less than 80 nm;
[0718] (c) Argon ion laser Raman spectroscopy at 1360 cm -1 The peak intensity relative to 1580 cm -1 The Raman R value defined by the ratio of the peak intensities of α and β (hereinafter, sometimes simply referred to as “Raman R value”) is 0.2 or more.
[0719] The negative electrode active material used in the present invention contains at least an amorphous carbonaceous material that satisfies (a), (b), and (c). The content of such amorphous carbonaceous material in the total negative electrode active material is preferably 10% by mass or more, more preferably 50% by mass or more, and particularly preferably 100% by mass, that is, all active materials are amorphous carbonaceous. There is no particular limitation on the negative electrode active material used in combination with the amorphous carbonaceous material, and known negative electrode active materials such as artificial graphite and natural graphite can be used.
[0720] [[Surface spacing (d002), Lc]]
[0721] The amorphous carbonaceous material used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention has a plane spacing (d002) of (002) measured by wide-angle X-ray diffraction of 0.337 nm or more, preferably 0.34 nm or more. Its upper limit is usually 0.39 nm or less, preferably 0.38 nm or less, more preferably 0.37 nm or less, further preferably 0.36 nm or less, and particularly preferably 0.35 nm or less. If it exceeds this range, the crystallinity is significantly reduced, the reduction in electrical conductivity between particles cannot be ignored, and it is sometimes difficult to obtain the effect of improving the short-time high current density charge-discharge characteristics. On the other hand, if it is lower than this range, the crystallinity becomes too high, and it is sometimes difficult to obtain the effect of improving the short-time high current density charge-discharge characteristics.
[0722] The interplanar spacing (d002) of the (002) plane measured by wide-angle X-ray diffraction in the present invention refers to the d value (interlayer distance) of the lattice plane (002) obtained by X-ray diffraction using the Gakushin method.
[0723] The crystallite size (Lc) of the (002) face of the amorphous carbonaceous obtained by the X-ray diffraction determined by learning the vibration method is less than 80nm, preferably less than 35nm, more preferably less than 20nm, further preferably less than 10nm. Its lower limit is usually more than 0.1nm, preferably more than 1nm. If it is less than the scope, the crystallinity is significantly reduced, and the reduction of interparticle conductivity can not be ignored sometimes, and it is sometimes difficult to obtain the improvement effect of short-time high current density charge and discharge. On the other hand, if it exceeds the scope, the crystallinity becomes too high, and it is sometimes difficult to obtain the improvement effect of short-time high current density charge and discharge.
[0724] [[Raman R value]]
[0725] The Raman R value of the amorphous carbonaceous material used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention must be 0.2 or more, preferably 0.5 or more, particularly preferably 0.7 or more, and more preferably 0.8 or more. Its upper limit is usually 1.5 or less, more preferably 1.2 or less. If the Raman R value is lower than this range, the crystallinity of the particle surface is too high, and the charge acceptance is reduced. Therefore, it is sometimes difficult to obtain the effect of improving the short-time high current density charge and discharge characteristics. On the other hand, if it exceeds this range, the crystallinity of the particle surface is significantly reduced. Therefore, the contact resistance between the particles becomes large, and it is sometimes difficult to obtain the effect of improving the short-time high current density charge and discharge characteristics.
[0726] Raman spectra are measured as follows: Using a Raman spectrometer (e.g., one manufactured by JASCO Corporation), a sample is naturally dropped into a measuring container to fill the container. During the measurement process, the sample surface in the container is irradiated with an argon ion laser while the container is rotated in a plane perpendicular to the laser. The resulting Raman spectrum is measured at 1580 cm -1 Peak P A Intensity I A and 1360cm -1 Peak P B Intensity I B , calculate its intensity ratio R (R=I B / I A ), which is defined as the Raman R value of amorphous carbon. In addition, the Raman spectrum obtained by measurement is at 1580cm -1 Peak P A The half-value width of the Raman lattice is defined as the half-value width of the amorphous carbon.
[0727] In addition, the Raman measurement conditions here are as follows.
[0728] Argon ion laser wavelength: 514.5nm
[0729] Laser power on the sample: 15-25mW
[0730] Resolution: 10-20cm -1
[0731] Measuring range: 1100cm -1 ~1730cm -1
[0732] Raman R value, Raman half-value width analysis: background processing
[0733] Smoothing: simple averaging, convolution 5 points
[0734] In addition, the amorphous carbon used as the negative electrode active material of the lithium secondary battery of the present invention has a peak at 1580 cm -1 There is no particular limit on the Raman half-value width, but it is usually 20 cm -1 Above, preferably 25cm -1 Above, in addition, its upper limit is usually 150cm -1 Below, preferably 140cm -1 The following range. If the Raman half-value width is lower than the scope, the crystallinity of the particle surface becomes too high, and the charge acceptance is reduced. Therefore, it is sometimes difficult to obtain the improvement effect of short-time high current density charge and discharge. On the other hand, if it exceeds the above range, the crystallinity of the particle surface is significantly reduced. Therefore, the contact resistance between particles becomes large, and it is likely to be difficult to obtain the improvement effect of short-time high current density charge and discharge. However, the Raman half-value width can sometimes not be judged by peak shape.
[0735] The amorphous carbon used in the present invention satisfies the above-mentioned conditions of interplanar spacing (d002), crystallite size (Lc) and Raman R value, but from the perspective of battery balance, it is more preferable to simultaneously satisfy any one or more of the following conditions. Among these, it is particularly preferable to simultaneously satisfy any one or more of the conditions of true density, H / C value, O / C value, tap density, BET specific surface area, micropore volume in the range of 0.01 μm to 1 μm, ash content and volume average particle size.
[0736] [[True density]]
[0737] The true density of amorphous carbon is usually 2.22 g / cm 3 Below, preferably 2.2 g / cm 3 Below, more preferably 2.1g / cm 3 Below, more preferably 2.0 g / cm 3 Below, the lower limit is usually 1.4g / cm 3 Above, preferably 1.5 g / cm 3 More than 1.6 g / cm 3More preferably, 1.7 g / cm 3 Above, particularly preferably 1.8 g / cm 3 If the carbon content is below this range, the crystallinity of the carbon is too low, and the initial irreversible capacity is sometimes increased. If the carbon content exceeds this range, the crystallinity of the carbon is too high, and it is difficult to obtain the effect of improving the short-time high current density charge and discharge.
[0738] In the present invention, true density is defined as a value measured by a liquid phase replacement method (density meter method) using butanol.
[0739] [[O / C value]]
[0740] The upper limit of the atomic ratio O / C value of the amorphous carbonaceous material is usually 0.15 or less, preferably 0.1 or less, more preferably 0.05 or less, and further preferably 0.03 or less, and the lower limit is usually 0 or more, preferably 0.01 or more.
[0741] The O / C value represents the ratio of the molar concentration of oxygen atoms to the molar concentration of carbon atoms in amorphous carbonaceous material and is an indicator of the amount of functional groups present, such as carboxyl groups, phenolic hydroxyl groups, and carbonyl groups. Amorphous carbonaceous materials with large O / C values often have oxygen-containing functional groups bonded to the end faces of carbon crystallites. O / C values exceeding the above range may increase the irreversible capacity.
[0742] [[H / C value]]
[0743] The upper limit of the atomic ratio H / C value of the amorphous carbonaceous material is usually 0.3 or less, preferably 0.15 or less, more preferably 0.1 or less, and further preferably 0.08 or less, and the lower limit is usually 0 or more, preferably 0.01 or more.
[0744] The so-called H / C value represents the ratio of the molar concentration of hydrogen atoms to the molar concentration of carbon atoms in amorphous carbonaceous materials and is an indicator of the amount of hydrogen present on the crystallite end faces of the amorphous carbonaceous materials. Amorphous carbonaceous materials with large H / C values often have an excess of carbon on the crystallite end faces of the particle surface. If the H / C value exceeds the above range, the irreversible capacity may increase.
[0745] The "O / C value" and "H / C value" referred to in the present invention are determined by the following CHN elemental analysis.
[0746] [[CHN elemental analysis]]
[0747] The amorphous carbonaceous material to be measured is dried under reduced pressure at 120°C for about 15 hours, and then placed on a hot plate in a drying oven and dried at 100°C for 1 hour. Next, in an argon atmosphere, the sample is placed in an aluminum cup, and the carbon content is calculated by the weight of the carbon dioxide gas produced by combustion. In addition, the hydrogen content is calculated by the weight of the water produced, the nitrogen content is calculated by the weight of the nitrogen dioxide produced, and the inorganic content is calculated by the weight of the residue remaining after combustion. The value of the oxygen content is obtained by subtracting the carbon content, hydrogen content, nitrogen content, and inorganic content from the total weight. The molar number is calculated from these values, and the O / C value and H / C value are calculated using the following formula using the molar number of each content obtained.
[0748] O / C value = moles of oxygen / moles of carbon
[0749] H / C value = moles of hydrogen / moles of carbon
[0750] [[Tap density]]
[0751] The tap density of the amorphous carbon used as the active material of the negative electrode [2] in the lithium secondary battery of the present invention is preferably 0.1 g / cm 3 More than 0.2 g / cm 3 More preferably, 0.5 g / cm 3 Above, particularly preferably 0.7 g / cm 3 In addition, the upper limit is preferably 1.4 g / cm 3 Below, more preferably 1.2 g / cm 3 Below, particularly preferably 1.1 g / cm 3 Below. If the tap density is lower than this range, it is difficult to increase the packing density when used as a negative electrode, and the contact area between the particles is reduced, so the impedance between the particles increases, sometimes reducing the short-time high current density charge-discharge characteristics. On the other hand, if it exceeds this range, the gaps between the particles in the electrode are too few, the flow path of the non-aqueous electrolyte is reduced, and therefore sometimes reducing the short-time high current density charge-discharge characteristics.
[0752] In the present invention, the tap density is defined as follows: a sample is passed through a sieve with an aperture of 300 μm and the sample is dropped into a 20 cm 3 In a compaction container, after the sample fills the upper end surface of the container, use a powder density meter (for example, Tap densor manufactured by Seishin Enterprise Co., Ltd.) to vibrate 1000 times with a stroke length of 10 mm, and the density calculated from the volume at this time and the weight of the sample is used as the tap density.
[0753] BET surface area
[0754] The amorphous carbon used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention preferably has a specific surface area of 0.1 m 2 / g or more, particularly preferably 0.5m 2 / g or more, more preferably 0.7m 2 / g or more, more preferably 1.5m 2 / g or more. The upper limit is preferably 100m 2 / g or less, particularly preferably 50m 2 / g or less, more preferably 25m 2 / g or less, more preferably 15m 2 / g or less. If the BET specific surface area value is below this range, when used as a negative electrode material, the lithium acceptance is likely to deteriorate during charging, and lithium may sometimes precipitate on the electrode surface. On the other hand, if the BET specific surface area value exceeds this range, when used as a negative electrode material, the reactivity with the non-aqueous electrolyte increases, the gas generated increases, and sometimes an optimal battery cannot be obtained.
[0755] The BET specific surface area is defined as the following value: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), the sample is pre-dried at 350°C for 15 minutes under nitrogen circulation, and then the value is measured by the nitrogen adsorption BET 1-point method using the gas flow method using a nitrogen-helium mixed gas in which the relative pressure of nitrogen relative to atmospheric pressure is accurately adjusted to 0.3.
[0756] [[Volume average particle size]]
[0757] The volume average particle size of the amorphous carbonaceous material used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention is defined as the average particle size (median particle size) of the volume basis obtained by the laser diffraction / scattering method, which is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and further preferably 7 μm or more. In addition, its upper limit is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less, and further preferably 25 μm or less. If it is lower than the above range, the irreversible capacity increases, sometimes resulting in a loss of initial battery capacity. In addition, if it exceeds the above range, it is easy to form an uneven coating surface when the electrode plate is made, which is sometimes not preferred in the battery manufacturing process.
[0758] Micropore volume
[0759] The micropore volume of the amorphous carbon used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention is equal to the voids in the particles with a diameter of 0.01 μm to 1 μm, and the amount of concave and convex caused by the unevenness of the particle surface obtained by mercury porosimetry (mercury intrusion method) is 0.01 mL / g or more, preferably 0.05 mL / g or more, more preferably 0.1 mL / g or more, and its upper limit is usually 0.6 mL / g or less, preferably 0.4 mL / g or less, and more preferably 0.3 mL / g or less. If it exceeds this range, a large amount of binder is required when manufacturing the electrode plate. If it is lower than this range, the short-term high current density charge and discharge characteristics are reduced, and sometimes the effect of mitigating the expansion and contraction of the electrode during charge and discharge cannot be obtained.
[0760] In addition, the total micropore volume is preferably more than 0.1mL / g, more preferably more than 0.25mL / g, and its upper limit is usually less than 10mL / g, preferably less than 5mL / g, more preferably less than 2mL / g. If it exceeds this range, a large amount of adhesives are sometimes needed. If it is lower than this range, the dispersion effect of thickener or binder can sometimes not be obtained when making a pole plate.
[0761] In addition, the average pore diameter is preferably 0.05 μm or more, more preferably 0.1 μm or more, and further preferably 0.5 μm or more. The upper limit is usually 50 μm or less, preferably 20 μm or less, and more preferably 10 μm or less. If it exceeds this range, a large amount of binder may be required. On the other hand, if it is below this range, the short-term high current density charge and discharge characteristics may be reduced.
[0762] As a device for a mercury porosimeter, a mercury porosimeter (autopore9520; manufactured by Micrometritics) can be used. About 0.2 g of the sample (negative electrode material) is weighed, sealed in a powder container, and degassed for 10 minutes at room temperature and vacuum (below 50 μmHg) to perform pretreatment. Next, the pressure is reduced to 4 psia (about 28 kPa), mercury is introduced, and the pressure is increased in stages from 4 psia (about 28 kPa) to 40,000 psia (about 280 MPa), and then the pressure is reduced to 25 psia (about 170 kPa). The number of stages during the pressure increase is more than 80 stages, and in each stage, the amount of mercury intrusion is measured after a 10-second equilibrium time. The micropore distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula. In addition, the surface tension (γ) of mercury is 485 dyne / cm, and the contact angle (φ) is 140°. The average micropore diameter used was the micropore diameter at which the cumulative micropore volume reached 50%.
[0763] Ash content
[0764] The ash content contained in the carbonaceous material is preferably less than 1 mass % relative to the gross mass of the carbonaceous material, more preferably less than 0.5 mass %, particularly preferably less than 0.1 mass %, in addition, as a lower limit, in mass, preferably more than 1ppm. If it exceeds the above scope, the deterioration of the battery performance caused by the reaction with the nonaqueous electrolyte during charge and discharge can not be ignored. On the other hand, if it is less than the scope, then long time and energy and the equipment for preventing pollution are needed in manufacturing, and sometimes cost can rise.
[0765] [[Circularity]]
[0766] The circularity of the amorphous carbonaceous material used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention is usually 0.1 or more, preferably 0.8 or more, more preferably 0.85 or more, and even more preferably 0.9 or more. As an upper limit, a circularity of 1 is a theoretical true sphere. If it is below this range, the packing of the negative electrode active material is reduced, the impedance between particles is increased, and sometimes the short-time high current density charge and discharge characteristics are reduced.
[0767] The circularity in the present invention is defined by the following formula.
[0768] Circularity = (the circumference of an equivalent circle with the same area as the particle's projected shape) / (the actual circumference of the particle's projected shape)
[0769] The following value is used as the circularity value: using, for example, a flow particle image analyzer (for example, FPIA manufactured by Sysmex Industrial), about 0.2 g of a sample is dispersed in a 0.2 mass % aqueous solution (about 50 mL) of polyoxyethylene (20) sorbitan monolaurate as a surfactant, and after irradiating with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, 0.6 to 400 μm is designated as the detection range, and particles with a particle size range of 3 to 40 μm are measured, and the average value of the measurements is used.
[0770] [[Orientation Ratio]]
[0771] The orientation ratio of the amorphous carbonaceous material used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention is usually 0.005 or more, preferably 0.01 or more, more preferably 0.015 or more, and its upper limit is theoretically 0.67 or less. If it is below this range, the short-time high-density charge and discharge characteristics may be reduced.
[0772] The orientation ratio was determined by X-ray diffraction. Using an asymmetric Pearson VII distribution function, the (110) and (004) diffraction peaks of carbon obtained by X-ray diffraction were fitted, and the peaks were separated. The integrated intensities of the (110) and (004) diffraction peaks were calculated. From the obtained integrated intensities, the ratio ((110) diffraction integrated intensity / (004) diffraction integrated intensity) was calculated, and this ratio was defined as the active material orientation ratio.
[0773] The X-ray diffraction measurement conditions here are as follows: In addition, "2θ" represents the diffraction angle.
[0774] Target: Cu (Kα ray) graphite monochromator
[0775] Slit:
[0776] Divergence slit = 1 degree, receiving slit = 0.1 mm, scattering slit = 1 degree
[0777] Measurement range and step angle / measurement time
[0778] (110) surface: 76.5 degrees ≤ 2θ ≤ 78.5 degrees 0.01 degrees / 3 seconds
[0779] (004) surface: 53.5 degrees ≤ 2θ ≤ 56.0 degrees 0.01 degrees / 3 seconds
[0780] [[Aspect Ratio]]
[0781] The aspect ratio of the amorphous carbon used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention is theoretically greater than 1, and the upper limit is usually less than 10, preferably less than 8, and more preferably less than 5. If the upper limit is exceeded, streaks may sometimes be generated when the electrode plate is made, and a uniform coating surface cannot be obtained, and the short-time high current density charge and discharge characteristics are reduced.
[0782] The aspect ratio is expressed as the ratio A / B of the longest diameter A of a carbonaceous material particle to its shortest diameter B, perpendicular thereto, when observed in three dimensions. Carbon particles were observed using a scanning electron microscope capable of magnification. Fifty particles were randomly selected and fixed to the end surface of a metal plate with a thickness of 50 μm or less. The stage holding the sample was rotated and tilted, and the A and B values of each particle were measured. The average value of A / B was calculated.
[0783] In addition, the amorphous carbonaceous material used as the negative electrode active material of the negative electrode [2] in the lithium secondary battery of the present invention is preferably selected from the following amorphous carbonaceous materials (1) to (4).
[0784] (1) a substance obtained by heat-treating a carbide selected from coal coke, petroleum coke, furnace black, acetylene black and pitch-based carbon fiber;
[0785] (2) organic matter selected from asphalt raw materials, aromatic hydrocarbons, N-ring compounds, S-ring compounds, polyphenylene, organic synthetic polymers, natural polymers, thermoplastic resins and thermosetting resins and / or their thermal decomposition products and / or substances obtained by further heat treatment;
[0786] (3) dissolving the organic matter of (2) in a low molecular weight organic solvent to obtain a thermal decomposition product of the solution and / or further heat-treating the solution to obtain a substance;
[0787] (4) Carbonized gases containing organic matter.
[0788] For (2), any substance that can be carbonized can be used, and examples thereof include asphalt raw materials, aromatic hydrocarbons such as acenaphthylene, decacyclene, anthracene, and phenanthrene; N-ring compounds such as phenazine or acridine; S-ring compounds such as thiophene and dithiophene; polyphenylenes such as biphenyl and terphenyl; organic polymers such as polyvinyl chloride, polyvinyl alcohol, polyvinyl butyral, their cross-linked products, insoluble products, nitrogen-containing polyacrylonitrile, polypyrrole; organic polymers such as sulfur-containing polythiophene and polystyrene; natural polymers such as polysaccharides represented by cellulose, lignin, mannan, polygalacturonic acid, chitosan, and sucrose; thermoplastic resins such as polyphenylene sulfide and polyphenylene ether; thermosetting resins such as furfuryl alcohol resin, phenolic resin, and imide resin; or organic substances such as solutions formed by dissolving them in low-molecular organic solvents such as benzene, toluene, xylene, quinoline, and n-hexane; and carbonizable gases containing these organic substances.
[0789] Among these, since the residual carbon rate (residual carbon rate) of the asphalt raw material is high, a material with high yield can be produced, so it is preferred. In addition, in this specification, "asphalt raw material" refers to asphalt and substances belonging to asphalt, and refers to substances that can be carbonized or graphitized by appropriate treatment. As specific examples of asphalt raw materials, tar, heavy oil or asphalt can be used. As specific examples of tar, coal tar, petroleum tar, etc. can be listed. As specific examples of heavy oil, contact decomposition oil, thermal decomposition oil, atmospheric residual oil, vacuum residual oil, etc. of petroleum heavy oil can be listed. In addition, as specific examples of asphalt, coal tar pitch, petroleum pitch, synthetic asphalt, etc. can be listed. Among them, the aromaticity of coal tar pitch is high, so it is preferred. These asphalt raw materials can be used alone or in combination of two or more in any combination and ratio.
[0790] As a preferred example of (3), the organic substance of (2) is dissolved in a low molecular weight organic solvent such as benzene, toluene, xylene, quinoline, n-hexane, etc. to obtain a solution, and the thermal decomposition product of the solution is used as the carbonized precursor.
[0791] Regarding (4), hydrocarbon compounds such as methane, ethane, propane, benzene, acetylene, and ethylene; and carbon monoxide can be cited.
[0792] It is preferable to perform a crosslinking treatment. The crosslinking treatment is performed to make the carbonaceous material obtained by heat-treating the crosslinked pitch raw material difficult to graphitize. By performing such treatment, the charge capacity per unit mass can be increased.
[0793] Examples of crosslinking treatments include: using vinyl monomers such as divinylbenzene, trivinylbenzene, diallyl phthalate, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide with α,α'-azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), lauroyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, and hydrogen peroxide as free radical polymerization initiators; and oxidizing agent treatments using oxidizing gases such as oxygen, ozone, and nitrogen dioxide, or oxidizing liquids such as sulfuric acid, nitric acid, and aqueous hydrogen peroxide. Another example of a crosslinking treatment method involves mixing the asphalt raw material with a crosslinking agent or oxidizing agent while maintaining the temperature at 50°C to 400°C.
[0794] [[Li-NMR shift]]
[0795] If the amorphous carbon used as the negative electrode active material of the lithium secondary battery of the present invention is subjected to 7 In Li-NMR analysis, a main resonance peak shifted 80 to 200 ppm to the low-field side of the resonance line of the reference substance LiCl is observed. Therefore, in order to increase the capacity per unit mass of the amorphous carbonaceous material, it is preferable to use a cross-linked amorphous carbonaceous material.
[0796] [[Method for producing amorphous carbon]]
[0797] The preparation method of the above-mentioned amorphous carbonaceous material is not particularly limited as long as it does not exceed the scope of the main points of the present invention, and various methods can be listed. In the production of amorphous carbonaceous material, it is necessary to go through one heat treatment process, but the heat treatment can also be divided into two or more times, and it is also preferred to perform various treatments before and after the heat treatment and / or in the intermediate stage of the heat treatment. The so-called various treatments include crushing, classification, the above-mentioned cross-linking treatment, etc., and the crushing and classification treatments can be performed before, after, or in any of the intermediate stages of the heat treatment as long as they are in a solid state. The cross-linking treatment is preferably performed before or in the intermediate stage of the heat treatment. By performing these treatments, the specific surface area of the negative electrode active material can be controlled and the capacity per unit mass can be increased.
[0798] There is no particular limitation on the apparatus used for pulverization before heat treatment. For example, as a coarse pulverizer, there can be mentioned a shear mill, a jaw crusher, an impact crusher, a cone crusher, etc.; as an intermediate pulverizer, there can be mentioned a roller crusher, a hammer mill, etc.; as a fine pulverizer, there can be mentioned a ball mill, a vibration mill, a pin mill, a stirred mill, a jet mill, etc.
[0799] There are no particular limitations on the apparatus used for heat treatment of raw materials, and examples thereof include a shuttle furnace, a tunnel furnace, an electric furnace, a coke roaster, a rotary kiln, a reactor such as an autoclave, a coke (a heat treatment tank manufactured by Cokes), a direct current furnace, etc. The raw materials may be stirred as needed during treatment.
[0800] The temperature conditions during heat treatment are not particularly limited, but are generally 600°C or higher, preferably 900°C or higher. The upper limit is generally 2500°C or lower, preferably 1300°C or lower. When the temperature is lower than the above range, the crystallinity becomes too low, which may increase the irreversible capacity. On the other hand, when the upper limit is exceeded, the crystallinity becomes too high, which may reduce the short-time high current density charge and discharge characteristics.
[0801] The amorphous carbonaceous material after heat treatment can be crushed or classified according to the size of its block or particles. There is no particular limitation on the device used for crushing. For example, as a coarse crusher, a shearing mill, a jaw crusher, an impact crusher, a cone crusher, etc. can be cited. As an intermediate crusher, a roller crusher, a hammer crusher, etc. can be cited. As a fine crusher, a ball mill, a vibration mill, a pin crusher, a stirring mill, a jet mill, etc. can be cited. There is no particular limitation on the device used in the classification treatment. For example, in the case of dry screening, a rotary screen, a shaking screen, a rotating screen (rotating screen), a vibrating screen, etc. can be used. In the case of dry airflow classification, a gravity classifier, an inertial force classifier, a centrifugal force classifier (granulator, cyclone separator), etc. can be used. In addition, a mechanical wet classifier, a hydraulic classifier, a sedimentation classifier, a centrifugal wet classifier, etc. can be used for wet screening.
[0802] [Electrode for making negative electrode [2]]
[0803] The negative electrode [2] can be manufactured by a conventional method and can be formed in the same manner as described above. The current collector, the thickness ratio of the current collector and the active material layer, the electrode density, the binder, the electrode plate orientation ratio, the impedance, etc. are also the same as described above.
[0804] Negative electrode[3]
[0805] Next, the negative electrode [3] used in the lithium secondary battery of the present invention is described. The negative electrode contains a metal oxide as a negative electrode active material, and the metal oxide contains titanium capable of occluding and releasing lithium.
[0806] [Negative electrode active material of negative electrode [3]]
[0807] Next, the negative electrode active material used in the negative electrode [3] is described.
[0808] [[Composition of negative electrode active material]]
[0809] The negative electrode active material used in the negative electrode [3] of the lithium secondary battery of the present invention contains a metal oxide, and the metal oxide contains titanium that can occlude and release lithium. Among the metal oxides, a composite oxide of lithium and titanium (hereinafter referred to as "lithium-titanium composite oxide") is preferred. In addition, the metal oxide is preferably a titanium-containing metal oxide having a spinel structure. In addition, when a metal oxide that satisfies all of these conditions is used in the negative electrode active material for a lithium secondary battery, that is, when a lithium-titanium composite oxide having a spinel structure is used, the output impedance can be greatly reduced, so it is particularly preferred.
[0810] In addition, lithium or titanium in the lithium-titanium composite oxide is preferably replaced by other metal elements, for example, at least one element selected from Na, K, Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn and Nb.
[0811] The metal oxide is a lithium-titanium composite oxide represented by the general formula (1). In view of structural stability during doping / dedoping of lithium ions, it is preferred that in the general formula (1), 0.7≤x≤1.5, 1.5≤y≤2.3, and 0≤z≤1.6 are satisfied.
[0812] Li x Ti y M z O4(1)
[0813] [In the general formula (1), M represents at least one element selected from the group consisting of Na, K, Co, Al, Fe, Ti, Mg, Cr, Ga, Cu, Zn, and Nb].
[0814] Among the compositions represented by the general formula (1), the following structures are particularly preferred because they provide a good balance in battery performance.
[0815] In the general formula (1)Li x Ti y M z In O4,
[0816] (a)1.2≤x≤1.4, 1.5≤y≤1.7, z=0
[0817] (b)0.9≤x≤1.1, 1.9≤y≤2.1, z=0
[0818] (c)0.7≤x≤0.9, 2.1≤y≤2.3, z=0
[0819] The particularly preferred representative composition of the above compounds is: (a) Li 4 / 3 Ti 5 / 3 O4, (b) is Li1Ti2O4, (c) is Li 4 / 5 Ti 11 / 5 O4.
[0820] In addition, for the structure of Z≠0, for example, Li 4 / 3 Ti 4 / 3 Al 1 / 3 O4 is the preferred composition.
[0821] [[Physical properties, shape, etc. of the negative electrode active material]]
[0822] The negative electrode active material used in the negative electrode [3] of the lithium secondary battery of the present invention preferably satisfies at least one of the following physical properties in addition to the above requirements. In addition, it is particularly preferred that at least two or more of the following physical properties are satisfied simultaneously in addition to the above requirements.
[0823] [[[BET specific surface area]]]
[0824] The specific surface area of the titanium-containing metal oxide used in the negative electrode active material of the negative electrode [3] in the lithium secondary battery of the present invention as measured by the BET method is preferably 0.5 m 2 / g or more, more preferably 0.7m 2 / g or more, particularly preferably 1.0m 2 / g or more, more preferably 1.5m 2 / g or more. The upper limit is preferably 200m 2 / g or less, more preferably 100m 2 / g or less, particularly preferably 50m 2 / g or less, more preferably 25m 2 / g or less. If the BET specific surface area value is below this range, when used as a negative electrode material, the reaction area in contact with the non-aqueous electrolyte is reduced, and the output impedance may increase. On the other hand, if the BET specific surface area value exceeds this range, the crystal surface or end face portion of the titanium-containing metal oxide increases, and this also causes uneven crystallization (distortion), the irreversible capacity becomes non-negligible, and a preferred battery may not be obtained.
[0825] The BET specific surface area is defined as the following value: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), the sample is pre-dried at 350°C for 15 minutes under nitrogen circulation, and then the value is measured by the nitrogen adsorption BET 1-point method using the gas flow method using a nitrogen-helium mixed gas in which the relative pressure of nitrogen relative to atmospheric pressure is accurately adjusted to 0.3.
[0826] [[[Volume average particle size]]]
[0827] The volume average particle size (secondary particle size when primary particles aggregate to form secondary particles) of the titanium-containing metal oxide used as the negative electrode active material of the negative electrode [3] in the lithium secondary battery of the present invention is defined as the volume-based average particle size (median particle size) obtained by the laser diffraction / scattering method, preferably 0.1 μm or more, more preferably 0.5 μm or more, and further preferably 0.7 μm or more. In addition, its upper limit is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less, and further preferably 25 μm or less. If it is lower than the above range, a large amount of binder is required when making the electrode, and as a result, the battery capacity is sometimes reduced. In addition, if it exceeds the above range, it is easy to form an uneven coating surface when making the electrode plate, which is sometimes not preferred in the battery manufacturing process.
[0828] [[[Average primary particle size]]]
[0829] When the primary particles are condensed to form secondary particles, the average primary particle size of the metal oxide containing titanium used as the negative electrode active material of the lithium secondary battery of the present invention is preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, most preferably 0.2 μm or more, and its upper limit is preferably 2 μm or less, more preferably 1.6 μm or less, further preferably 1.3 μm or less, and most preferably 1 μm or less. If the average primary particle size exceeds the above upper limit, it is difficult to form spherical secondary particles, which has an adverse effect on the powder filling property, or the specific surface area is greatly reduced. Therefore, the possibility of reducing battery performance such as output characteristics sometimes becomes high. On the contrary, if the average primary particle size is lower than the above lower limit, it is usually due to incomplete crystallization, and therefore sometimes problems such as poor reversibility of charge and discharge are generated.
[0830] The primary particle size can be measured by observation using a scanning electron microscope (SEM). Specifically, the maximum value of a slice formed by the left and right boundaries of the primary particles on a straight horizontal line is determined for 50 random primary particles in a photograph with a magnification of 10,000 to 100,000 times, and the average value is calculated.
[0831] [[[shape]]]
[0832] The particle shape of the titanium-containing metal oxide used in the negative electrode [3] of the lithium secondary battery of the present invention can be a block, polyhedron, spherical, ellipsoidal, plate-like, needle-like, columnar, etc. that have been used in the past, wherein it is preferred that the primary particles are condensed to form secondary particles, and the shape of the secondary particles is spherical or ellipsoidal. Generally, as the electrochemical element is charged and discharged, the active material in the electrode expands and contracts, and it is easy to cause degradation such as destruction of the active material or disconnection of the conductive path due to the stress. Therefore, compared with a single particle active material that is only a primary particle, it is preferred that the primary particles are condensed to form secondary particles, because the formation of secondary particles can alleviate the stress of expansion and contraction, thereby preventing degradation. In addition, compared with plate-like equiaxially oriented particles, spherical or ellipsoidal particles are preferred because the spherical or ellipsoidal particles have less orientation when the electrode is formed, the electrode expands and contracts less during charging and discharging, and it is also easy to mix evenly with the conductive agent when making the electrode.
[0833] [[[Tap density]]]
[0834] The tap density of the titanium-containing metal oxide used as the negative electrode active material of the negative electrode [3] in the lithium secondary battery of the present invention is preferably 0.05 g / cm 3 More than 0.1 g / cm 3 More preferably, 0.2 g / cm 3 Above, particularly preferably 0.4 g / cm 3 In addition, the upper limit is preferably 2.8 g / cm 3 Below, more preferably 2.4g / cm 3 Below, particularly preferably 2 g / cm 3 If the tap density is below this range, it is difficult to increase the packing density when used as a negative electrode, and the contact area between particles is reduced, thereby increasing the impedance between particles and sometimes increasing the output resistance. On the other hand, if it exceeds this range, the gaps between particles in the electrode are too small, and the flow path of the non-aqueous electrolyte is reduced, thereby sometimes increasing the output resistance.
[0835] In the present invention, the tap density is defined as follows: a sample is passed through a sieve with an aperture of 300 μm and the sample is dropped into a 20 cm 3 In a compaction container, after the sample fills the upper end surface of the container, use a powder density meter (for example, Tap densor manufactured by Seishin Enterprise Co., Ltd.) to vibrate 1000 times with a stroke length of 10 mm, and the density calculated from the volume at this time and the weight of the sample is used as the tap density.
[0836] [[[Circularity]]]
[0837] The circularity of the titanium-containing metal oxide used as the negative electrode active material of the negative electrode [3] in the lithium secondary battery of the present invention is usually 0.10 or more, preferably 0.80 or more, more preferably 0.85 or more, and even more preferably 0.90 or more. As an upper limit, a circularity of 1 is a theoretical true sphere. If it is below this range, the packing of the negative electrode active material is reduced, the impedance between particles is increased, and sometimes the short-time high current density charge and discharge characteristics are reduced.
[0838] The circularity in the present invention is defined by the following formula.
[0839] Circularity = (the circumference of an equivalent circle with the same area as the particle's projected shape) / (the actual circumference of the particle's projected shape)
[0840] The following value is used as the circularity value: using, for example, a flow particle image analyzer (for example, FPIA manufactured by Sysmex Industrial), about 0.2 g of a sample is dispersed in a 0.2 mass % aqueous solution (about 50 mL) of polyoxyethylene (20) sorbitan monolaurate as a surfactant, and after irradiating with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, 0.6 to 400 μm is designated as the detection range, and the value obtained by measuring particles in the particle size range of 3 to 40 μm is obtained.
[0841] [[[Aspect Ratio]]]
[0842] The aspect ratio of the titanium-containing metal oxide used as the negative electrode active material of the negative electrode [3] in the lithium secondary battery of the present invention is theoretically 1 or more, with an upper limit of 5 or less, preferably 4 or less, more preferably 3 or less, and further preferably 2 or less. If the upper limit is exceeded, streaks may sometimes be generated when the electrode plate is produced, a uniform coating surface cannot be obtained, and the short-time high current density charge and discharge characteristics are reduced.
[0843] In three-dimensional observation, the longest diameter of a particle is defined as A, and the shortest diameter perpendicular to it is defined as B. The aspect ratio is expressed as A / B. Particle observation was performed using a scanning electron microscope capable of magnification. Fifty graphite particles were randomly selected and fixed to the end surface of a metal plate with a thickness of 50 μm or less. The stage holding the sample was rotated and tilted, and the A and B values of each particle were measured. The average value of A / B was calculated.
[0844] [[Method for producing negative electrode active material]]
[0845] The method for producing the negative electrode active material of the negative electrode [3] in the lithium secondary battery of the present invention is not particularly limited within the scope of the present invention, and several methods can be cited, and a common method for producing an inorganic compound can be used. For example, a method can be cited in which a titanium raw material such as titanium oxide, raw materials of other elements used as needed, and a lithium source such as LiOH, Li2CO3, LiNO3 are uniformly mixed and sintered at a high temperature to obtain an active material. In particular, when preparing spherical or ellipsoidal active materials, various methods can be considered, for example, the following methods can be listed: a titanium raw material such as titanium oxide and a raw material of other elements used as needed are dissolved or crushed and dispersed in a solvent such as water, the pH is adjusted while stirring, and a spherical precursor is prepared and obtained, which is dried as needed, and a Li source such as LiOH, Li2CO3, LiNO3 is added, and the active material is sintered at a high temperature; a titanium raw material such as titanium oxide and a raw material of other elements used as needed are dissolved or crushed and dispersed in a solvent such as water, and then dried and formed by a spray dryer to prepare a spherical or ellipsoidal precursor, and then Li source such as LiOH, Li2CO3, LiNO3 is added thereto and sintered at a high temperature to obtain an active material; and a titanium raw material such as titanium oxide and a Li source such as LiOH, Li2CO3, LiNO3 and a raw material of other elements used as needed are dissolved or crushed and dispersed in a solvent such as water, and then dried and formed by a spray dryer to prepare a spherical or ellipsoidal precursor, and then sintered at a high temperature to obtain an active material.
[0846] Furthermore, in these steps, elements other than Ti, such as Al, Mn, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, C, Si, Sn, and Ag, may be present in the structure of the titanium-containing metal oxide and / or in contact with the titanium-containing oxide. The inclusion of these elements can control the operating voltage and capacity of the battery.
[0847] [Electrode for making negative electrode [3]]
[0848] The negative electrode [3] can be manufactured by a conventional method and can be formed in the same manner as described above. The current collector, the thickness ratio of the current collector and the active material layer, the electrode density, the binder, the electrode plate orientation ratio, the impedance, etc. are also the same as described above.
[0849] Negative electrode[4]
[0850] Next, the negative electrode [4] used in the lithium secondary battery of the present invention is described. The negative electrode contains a carbonaceous material as a negative electrode active material. The circularity of the carbonaceous material is 0.85 or more and the surface functional group amount O / C value is 0 to 0.01.
[0851] [Negative electrode active material of negative electrode [4]]
[0852] Next, the negative electrode active material used in the negative electrode [4] is described.
[0853] The negative electrode active material used in the negative electrode [4] of the lithium secondary battery of the present invention contains at least a carbonaceous material that satisfies the following conditions (a) and (b).
[0854] (a) The circularity is 0.85 or above;
[0855] (b) The surface functional group amount O / C value is 0 to 0.01.
[0856] Next, the carbonaceous material used in the present invention will be described in detail.
[0857] [[Circularity]]
[0858] The circularity of the carbonaceous material is generally more than 0.85, preferably more than 0.87, more preferably more than 0.89, and particularly preferably more than 0.92. As an upper limit, it becomes a theoretical true sphere when the circularity is 1. If it is lower than this range, the fillability of the negative electrode active material is reduced, and the compaction of the negative electrode becomes difficult, resulting in the destruction of the particles during compaction, and the surface of the particle interior having poor tolerance to high temperature storage at a low depth of charge may be easily exposed.
[0859] The circularity referred to in the present invention is defined by the following formula.
[0860] Circularity = (the circumference of an equivalent circle with the same area as the particle's projected shape) / (the actual circumference of the particle's projected shape)
[0861] The following value is used as the circularity value: using, for example, a flow particle image analyzer (for example, FPIA manufactured by Sysmex Industrial), about 0.2 g of a sample is dispersed in a 0.2 mass % aqueous solution (about 50 mL) of polyoxyethylene (20) sorbitan monolaurate as a surfactant, and after irradiating with 28 kHz ultrasonic waves at an output power of 60 W for 1 minute, 0.6 to 400 μm is designated as the detection range, and the value obtained by measuring particles in the particle size range of 3 to 40 μm is obtained.
[0862] [[O / C value]]
[0863] The surface functional group amount O / C value of the carbonaceous material must be 0 to 0.01. The upper limit of the O / C value is preferably 0.005 or less, and the closer to 0, the more preferable.
[0864] The O / C value referred to in the present invention is the ratio of the amount of surface functional groups measured using X-ray photoelectric spectroscopy (XPS). If the surface functional group amount O / C value exceeds the above range, the amount of functional groups on the particle surface increases, and when charging is carried out under conditions where specific compounds are present, the stability of the SEI coating film generated on the surface is insufficient, sometimes resulting in a decrease in high-temperature storage characteristics at low charge depths.
[0865] The surface functional group amount O / C value represents the ratio of the molar concentration of oxygen atoms to the molar concentration of carbon atoms present in the surface of a graphite material, etc., and is an indicator of the amount of functional groups such as carboxyl groups, phenolic hydroxyl groups, and carbonyl groups present on the surface. Carbon materials with large surface functional group amount O / C values are mostly combined with surface oxygen-containing functional groups on the microcrystalline end faces of the particle surface carbon, etc. In addition, as the surface functional group amount O / C value of the graphite material, the following value is used: in X-ray photoelectric spectroscopy analysis, the peak area of the spectrum of C1s and O1s is obtained, and the atomic concentration ratio of C and O (O atomic concentration / C atomic concentration) is calculated. The specific measurement procedure is not particularly limited, and an example thereof is described below.
[0866] Specifically, an X-ray photoelectric spectrometer (e.g., ESCA manufactured by Ulvac-Phi) is used for X-ray photoelectric spectrometry. The object to be measured (here, a graphite material) is placed on a sample table and the surface is flattened. Using aluminum Kα radiation as the X-ray source, multiplexed measurement is performed to measure the spectra of C1s (280-300 eV) and O1s (525-545 eV). The peak top of the obtained C1s is set to 284.3 eV for charge compensation. The peak areas of the C1s and O1s spectra are calculated and multiplied by the device sensitivity coefficient to calculate the surface atomic concentrations of C and O, respectively. The obtained atomic concentration ratio of O to C, O / C (O atomic concentration / C atomic concentration), is calculated and defined as the surface functional group amount O / C value of the graphite material.
[0867] The carbonaceous material used in the present invention satisfies the above-mentioned conditions of "circularity" and "surface functional group amount O / C value", but from the perspective of battery balance, it is more preferred to further simultaneously satisfy any one or more of the following conditions. Among these, it is preferred to simultaneously satisfy any one or more of the tap density, Raman R value, and volume average particle size.
[0868] [[Tap density]]
[0869] The tap density of carbonaceous materials is usually 0.55g / cm 3 Above, preferably 0.7 g / cm 3 More than 0.8 g / cm 3 Above, particularly preferably 0.9 g / cm 3In addition, the upper limit is preferably 2g / cm 3 Below, more preferably 1.8g / cm 3 Below, particularly preferably 1.6 g / cm 3 If the tap density is below this range, it is difficult to increase the packing density when used as a negative electrode, and a high-capacity battery may not be obtained. On the other hand, if it exceeds this range, the interparticle spaces in the electrode are too few, making it difficult to ensure interparticle conductivity, and it is sometimes difficult to obtain preferred battery characteristics.
[0870] In the present invention, the tap density is defined as follows: a sample is passed through a sieve with an aperture of 300 μm and the sample is dropped into a 20 cm 3 In a tapping container, after the sample fills the upper end surface of the container, use a powder density meter (for example, Tap densor manufactured by Seishin Enterprise Co., Ltd.) to vibrate 1000 times with a stroke length of 10 mm. The density is calculated from the volume and weight at this time, and this value is used as the tap density.
[0871] [[Raman R value, half-value width]]
[0872] The R value of the carbonaceous material measured using argon ion laser Raman spectroscopy is generally more than 0.001, preferably more than 0.01, and its upper limit is generally less than 0.2, preferably less than 0.18, more preferably less than 0.15. If the R value is lower than the scope, the crystallinity of the particle surface is too high, and the site of the interlayer is sometimes reduced as charge and discharge Li enters. That is, charging acceptance is reduced. On the other hand, if it exceeds the scope, the crystallinity of the particle surface is reduced, and when charging is carried out under conditions in the presence of a specific compound, the stability of the SEI capping film generated on the surface is insufficient, sometimes resulting in a reduction in high temperature storage characteristics under low charge depth.
[0873] In addition, carbonaceous matter is at 1580 cm -1 There is no particular limit on the Raman half-value width near 10 cm, but it is usually 10 cm -1 Above, preferably 15cm -1 Above, the upper limit is usually 35cm -1 Below, preferably 30cm -1 The Raman half-width is within the range below. If the Raman half-width is below this range, the crystallinity of the particle surface is too high, and the number of sites where Li can enter the interlayer during charging and discharging may decrease. In other words, the charge acceptance may be reduced. On the other hand, if it is above this range, the crystallinity of the particle surface is reduced, and when charging is performed in the presence of specific compounds, the stability of the SEI film formed on the surface is insufficient, sometimes leading to a decrease in high-temperature storage characteristics at low charge depths.
[0874] Raman spectroscopy is measured as follows: Using a Raman spectrometer (e.g., a Raman spectrometer manufactured by JASCO Corporation), the sample is allowed to naturally fall into a measurement container and filled with the sample. During the measurement process, the sample surface in the container is irradiated with an argon ion laser while the container is rotated in a plane perpendicular to the laser. The resulting Raman spectrum is measured at 1580 cm -1 Nearby peak P A Intensity I A and 1360cm -1 Nearby peak P B Intensity I B , calculate its intensity ratio R (R=I B / I A ), which is defined as the Raman R value of the carbonaceous material. In addition, the Raman spectrum obtained by measurement is at 1580cm -1 Nearby peak P A The half-value width of the Raman spectroscopy is defined as the half-value width of the carbonaceous material.
[0875] In addition, the Raman measurement conditions here are as follows.
[0876] Argon ion laser wavelength: 514.5nm
[0877] Laser power on the sample: 15-25mW
[0878] Resolution: 10-20cm -1
[0879] Measuring range: 1100cm -1 ~1730cm -1
[0880] R value, half-value width analysis: background processing
[0881] Smoothing: simple averaging, convolution 5 points
[0882] [[Volume-based average particle size]]
[0883] The volume reference average particle size of the carbonaceous material is the average particle size (median particle size) of the volume reference sought to by laser diffraction / scattering method, usually more than 1 μm, preferably more than 3 μm, more preferably more than 5 μm, and more preferably more than 7 μm. In addition, its upper limit is usually less than 50 μm, preferably less than 40 μm, more preferably less than 30 μm, and more preferably less than 25 μm. If it is less than the above range, the irreversible capacity increases, sometimes resulting in the loss of initial battery capacity. In addition, if it exceeds the above range, when the pole plate of the electrode is made, it is easy to form an uneven coating surface, which is sometimes not preferred in the battery manufacturing process.
[0884] In addition, the ratio of the 90% particle size to the 10% particle size (d 90 / d 10 ) is 1.2 or more, preferably 1.5 or more, more preferably 1.7 or more. The upper limit is 8 or less, preferably 5 or less, more preferably 4 or less, and further preferably within the range of 3 or less.
[0885] In the present invention, the volume-based average particle size is defined as the median particle size, which is measured by dispersing carbon powder in a 0.2 mass % aqueous solution (about 1 mL) of polyoxyethylene (20) sorbitan monolaurate as a surfactant and measuring it using a laser diffraction / scattering particle size distribution analyzer (e.g., LA-700 manufactured by Horiba, Ltd.). The median particle size is the ratio of the 90% particle size to the 10% particle size (d 90 / d 10 ), the volume-based 90% particle size and 10% particle size can be similarly measured and their ratio (d 90 / d 10 ).
[0886] [[X-ray parameters]]
[0887] The d value (interlayer distance) of the lattice plane (002) of the carbonaceous material obtained by X-ray diffraction using the learning vibration method is preferably 0.335nm or more. In addition, the upper limit is 0.340nm or less, preferably 0.337nm or less. If the d value is too large, the crystallinity is reduced, and the initial irreversible capacity is sometimes increased. On the other hand, 0.335 is the theoretical value of graphite. In addition, the crystallite size (Lc) of the carbon material obtained by X-ray diffraction using the learning vibration method is generally 30nm or more, preferably 50nm or more, and more preferably in the range of 80nm or more. If it is below this range, the crystallinity of the particle is reduced, and it is possible to increase the initial irreversible capacity.
[0888] Ash content
[0889] The ash content in the carbonaceous material is less than 1% by mass, preferably less than 0.5% by mass, particularly preferably less than 0.1% by mass, relative to the total mass of the carbonaceous material, and its lower limit is 1 ppm or more. If the above range is exceeded, the degradation of battery performance caused by the reaction with the electrolyte during charge and discharge cannot be ignored. If the range is lower than this, a long time, energy, and equipment for preventing pollution are required in the manufacture, and sometimes the cost will increase.
[0890] BET surface area
[0891] The specific surface area of carbonaceous materials measured by the BET method is usually 0.1 m 2 / g or more, preferably 0.7m 2 / g or more, more preferably 1m 2 / g or more, more preferably 1.5m 2 / g or more. Its upper limit is usually 100m 2 / g or less, preferably 25m 2 / g or less, more preferably 15m 2 / g or less, more preferably 10m 2 / g or less. If the specific surface area value is lower than the above range, when used as a negative electrode material, the lithium acceptance deteriorates during charging, and lithium is easily deposited on the electrode surface. On the other hand, if it exceeds the above range, when used as a negative electrode material, the reactivity with the electrolyte increases, the gas generated becomes more, and sometimes it is difficult to obtain a preferred battery.
[0892] The BET specific surface area is defined as a value measured as follows: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), the sample is pre-dried at 350°C for 15 minutes under nitrogen flow, and then measured by the nitrogen adsorption BET 1-point method using a gas flow method using a nitrogen-helium mixed gas in which the relative pressure of nitrogen relative to atmospheric pressure is accurately adjusted to 0.3.
[0893] [[Micropore distribution]]
[0894] The voids in the particles of the carbonaceous material obtained by mercury porosimeter (mercury intrusion method) equivalent to 0.01 μm to 1 μm in diameter, the amount of the concave and convex caused by the unevenness of the particle surface are usually 0.01 mL / g or more, preferably 0.05 mL / g or more, more preferably 0.1 mL / g or more, and the upper limit is usually 0.6 mL / g or less, preferably 0.4 mL / g or less, more preferably 0.3 mL / g or less. If it exceeds this range, a large amount of adhesive is sometimes needed when manufacturing the pole plate. On the other hand, if it is lower than this range, the high current density charge and discharge characteristics are reduced, and the relaxation effect of the electrode expansion and contraction during charge and discharge can sometimes not be obtained.
[0895] In addition, total micropore volume is preferably more than 0.1mL / g, more preferably more than 0.25mL / g, and its upper limit is usually below 10mL / g, preferably below 5mL / g, more preferably below 2mL / g scope.If it exceeds this scope, then when making substrate, sometimes need a large amount of adhesives.If it is lower than this scope, then when making pole plate, sometimes can not obtain the dispersion effect of thickener or binding agent.
[0896] In addition, the average pore diameter is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.5 μm or more. The upper limit is usually 50 μm or less, preferably 20 μm or less, and more preferably 10 μm or less. If it exceeds this range, a large amount of binder may be required. On the other hand, if it is below this range, the high current density charge and discharge characteristics may be reduced.
[0897] As a device for a mercury porosimeter, a mercury porosimeter (autopore9520; manufactured by Micrometritics) can be used. About 0.2 g of the sample (negative electrode material) is weighed, sealed in a powder container, and degassed for 10 minutes at room temperature and vacuum (below 50 μmHg) to perform pretreatment. Next, the pressure is reduced to 4 psia (about 28 kPa), mercury is introduced, and the pressure is increased in stages from 4 psia (about 28 kPa) to 40,000 psia (about 280 MPa), and then the pressure is reduced to 25 psia (about 170 kPa). The number of stages during the pressure increase is more than 80 stages, and in each stage, the amount of mercury intrusion is measured after a 10-second equilibrium time. The micropore distribution is calculated from the mercury intrusion curve obtained in this way using the Washburn formula. In addition, the surface tension (γ) of mercury is 485 dyne / cm, and the contact angle (φ) is 140°. The average micropore diameter used was the micropore diameter at which the cumulative micropore volume reached 50%.
[0898] [[True density]]
[0899] The true density of carbonaceous materials is usually 2g / cm 3 Above, preferably 2.1 g / cm 3 More than 2.2 g / cm 3 More preferably, 2.22 g / cm 3 Above, the upper limit is 2.26g / cm 3 Below. The upper limit is the theoretical value of graphite. If it is below this range, the crystallinity of the carbon is too low, and the initial irreversible capacity may increase. In the present invention, the true density is defined as the value measured by the liquid phase replacement method (hydrometer method) using butanol.
[0900] [[Orientation Ratio]]
[0901] The orientation ratio of the carbonaceous material is usually 0.005 or more, preferably 0.01 or more, more preferably 0.015 or more, and the upper limit is theoretically 0.67 or less. If it is below this range, the high-density charge and discharge characteristics may be reduced.
[0902] The orientation ratio was determined by X-ray diffraction. Using an asymmetric Pearson VII distribution function, the (110) and (004) diffraction peaks of carbon obtained by X-ray diffraction were fitted, and the peaks were separated. The integrated intensities of the (110) and (004) diffraction peaks were calculated. From the obtained integrated intensities, the ratio ((110) diffraction integrated intensity / (004) diffraction integrated intensity) was calculated, and this ratio was defined as the active material orientation ratio.
[0903] The X-ray diffraction measurement conditions here are as follows: In addition, "2θ" represents the diffraction angle.
[0904] Target: Cu (Kα ray) graphite monochromator
[0905] Slits: Divergence slit = 1 degree, Receiving slit = 0.1 mm, Scattering slit = 1 degree
[0906] Measurement range and step angle / measurement time
[0907] (110) surface: 76.5 degrees ≤ 2θ ≤ 78.5 degrees 0.01 degrees / 3 seconds
[0908] (004) surface: 53.5 degrees ≤ 2θ ≤ 56.0 degrees 0.01 degrees / 3 seconds
[0909] [[Aspect Ratio]]
[0910] The aspect ratio of the carbonaceous material is theoretically greater than 1, with an upper limit of less than 10, preferably less than 8, and more preferably less than 5. If the upper limit is exceeded, streaks may be generated when the electrode plate is made, a uniform coating surface may not be obtained, and high current density charge and discharge characteristics may sometimes be reduced.
[0911] The aspect ratio is expressed as the ratio A / B, the ratio of the longest diameter A of a particle to its shortest diameter B, perpendicular thereto, when observed in three dimensions. Particles were observed using a scanning electron microscope capable of magnification. Fifty graphite particles were randomly selected and fixed to the end surface of a metal with a thickness of 50 microns or less. The stage holding the sample was rotated and tilted, and the A and B values of each particle were measured. The average value of A / B was then calculated.
[0912] [[Production method and raw materials of carbonaceous materials]]
[0913] The carbonaceous material used in the present invention may be a naturally occurring material or an artificially produced material, but is preferably a material derived from natural graphite. In addition, naturally occurring materials or artificially produced materials may also be subjected to specific treatment. The manufacturing method (also comprising a sorting method) is not particularly limited, and for example, may be a material obtained by sorting the carbonaceous material having the above-mentioned characteristics using a classification method such as screening or wind classification.
[0914] Among these, from the perspective of being easy to obtain and easy to process in the previous steps, it is preferred to use a carbonaceous material obtained by heat-treating a naturally produced carbon material (natural graphite raw material). In addition, from the perspective of improving filling properties, it is preferred to use a carbonaceous material obtained as follows: a naturally produced carbon material (natural graphite raw material) or an artificially produced carbon material is subjected to mechanical energy treatment and modified and spheroidized, and the obtained spheroidized carbonaceous material is heat-treated. In addition, from the perspective of the balance of the performance of lithium secondary batteries, it is particularly preferred to use a carbonaceous material prepared as follows: a natural graphite raw material is subjected to mechanical energy treatment, and the obtained spheroidized natural graphite is heat-treated. Below, the carbon material (raw material) before the heat treatment of the above-mentioned natural graphite raw material, etc. is sometimes referred to as only "raw material before heat treatment".
[0915] [[Natural graphite raw materials]]
[0916] As described above, natural graphite is particularly preferred as the raw material of the carbonaceous material.
[0917] Natural graphite is classified according to its properties into flake graphite, crystalline (Vein) graphite, and amorphous graphite (see "Powder and Particle Process Technology Integration," Industrial Technology Center Co., Ltd., published in 1977, under the section on graphite; and "HAND BOOK OF CARBON, GRAPHITE, DIAMOND AND FULLERENES," published by Noyes Publications). Flake graphite has the highest degree of graphitization, at 100%, followed by flake graphite at 99.9%, while amorphous graphite has a low degree of graphitization, at 28%. The quality of natural graphite is primarily determined by its origin and mineral vein. Flake graphite is primarily produced in Madagascar, China, Brazil, Ukraine, and Canada; crystalline graphite is primarily produced in Sri Lanka; and amorphous graphite is primarily produced in North Korea, South Korea, China, and Mexico. Among these natural graphites, flake graphite and scale graphite have advantages such as a high degree of graphitization and a low amount of impurities, and are therefore preferred as a raw material for the carbonaceous material.
[0918] [[[Mechanical energy treatment, spherical treatment]]]
[0919] The mechanical energy treatment is performed so that the volume average particle size before and after the treatment is 1 or less. The so-called "volume average particle size ratio before and after the treatment" is the value obtained by dividing the volume average particle size after the treatment by the volume average particle size before the treatment. In the present invention, the mechanical energy treatment performed to produce the raw material before heat treatment is preferably performed so that the average particle size ratio before and after the treatment is 1 or less.
[0920] Dynamic energy treatment reduces particle size to a ratio of the average particle size before and after treatment of powder particles to less than 1, while also controlling particle shape. Among the engineering unit operations that can be effectively utilized in particle design, such as pulverization, classification, mixing, granulation, surface modification, and reaction, dynamic energy treatment falls under the category of pulverization.
[0921] The so-called pulverization refers to applying force to a substance to reduce its size in order to adjust the particle size, particle size distribution, and filling properties of the substance. Pulverization treatments are classified according to the type of force applied to the substance and the treatment form. The force applied to the substance is roughly divided into the following four types: (1) beating force (impact force), (2) crushing force (compression force), (3) grinding force (grinding force), and (4) scraping force (shear force). On the other hand, the treatment form is roughly divided into the following two types: volume pulverization that generates cracks inside the particles and propagates them, and surface pulverization that cuts off the surface of the particles. Volume pulverization can be carried out using impact force, compression force, and shear force; surface pulverization can be carried out using grinding force and shear force. Pulverization is a treatment that combines the type of force applied to these substances and the treatment form in various ways. The combination can be appropriately determined according to the treatment purpose.
[0922] Although pulverization can also be carried out using chemical reactions such as blasting or volume expansion, it is usually carried out using a mechanical device such as a pulverizer. The pulverization treatment used in the manufacture of the spheroidized carbonaceous material as the raw material of the present invention is preferably a treatment in which the proportion of the final surface treatment becomes higher, regardless of whether there is volume pulverization. This is because it is important to remove the corners of the particle surface pulverization to introduce a round shape to the particle. Specifically, the surface treatment can be carried out after a certain degree of volume pulverization, or only the surface treatment can be carried out without almost any volume pulverization, or the volume pulverization and surface treatment can be carried out at the same time. It is preferred to carry out the surface pulverization last and remove the corners from the surface of the particle.
[0923] The device for performing the mechanical energy treatment is selected from the devices capable of performing the above-mentioned preferred treatment. The mechanical energy treatment can be achieved by using one or more of the four forces applied to the above-mentioned substance, but it is preferred that the main body is repeatedly subjected to mechanical actions such as compression, friction, and shear force including the interaction of the particles, thereby imparting impact force to the particles. Therefore, specifically, the following device is preferred: the device has a rotor provided with a plurality of blades inside the box, and the rotor is rotated at high speed to impart mechanical actions such as impact compression, friction, and shear force to the carbon material introduced into the interior, thereby performing volume crushing while performing surface treatment. In addition, a device having a mechanism for repeatedly imparting mechanical action by circulating or convection of the carbonaceous material is more preferred.
[0924] As preferred devices, a mixing system (manufactured by Nara Machinery Manufacturing Co., Ltd.), Kryptron (manufactured by Earth Technica), CF mill (manufactured by Ube Industries, Ltd.), and mechanical melting system (manufactured by Hosokawamicron) are listed. Among these, a mixing system manufactured by Nara Machinery Manufacturing Co., Ltd. is preferred. When using the device for treatment, the circumferential speed of the rotating rotor is preferably set to 30 to 100 m / s, more preferably to 40 to 100 m / s, and further preferably to 50 to 100 m / s. In addition, the treatment may be simply to pass the carbonaceous material, but it is preferably circulated or retained in the device for more than 30 seconds for treatment, and more preferably circulated or retained in the device for more than 1 minute for treatment.
[0925] This mechanical energy treatment results in carbon particles that retain high crystallinity overall, but become roughened near the surface, becoming tilted and exposing edge faces. This increases the surface area available for lithium ions to enter and exit, resulting in high capacity even at high current densities.
[0926] Generally speaking, the smaller the particle size of flaky, scale-like, or plate-like carbon materials, the worse their packing properties tend to be. This is believed to be due to the following reasons: the particles become more amorphous due to pulverization, the increase in protrusions such as "burrs," "peeling," and "bends" on the particle surface, and the presence of even finer amorphous particles adhering to the particle surface with a certain degree of strength. This increases the impedance between adjacent particles and worsens the packing properties.
[0927] If the amorphous nature of these particles is reduced and the particle shape is close to spherical, the filling capacity will be only slightly reduced even if the particle size is reduced. In theory, large-particle carbon powder and small-particle carbon powder should show the same degree of tap density.
[0928] [[[Physical properties of raw materials before heat treatment]]]
[0929] The physical properties of the raw material before heat treatment preferably satisfy any one or more of the following (1) to (11) simultaneously. The intangible measurement method and definition are the same as those for the carbonaceous material described above.
[0930] (1) X-ray parameters
[0931] The raw material before heat treatment is preferably more than 0.335nm by the d value (interlayer distance) of the lattice plane (002) obtained by X-ray diffraction using the learning vibration method. In addition, its lower limit is less than 0.340nm, preferably less than 0.337nm. If the d value is too large, the crystallinity is reduced, and the initial irreversible capacity is sometimes increased. On the other hand, 0.335 is the theoretical value of graphite. In addition, the crystallite size (Lc) of the carbon material obtained by X-ray diffraction using the learning vibration method is generally more than 30nm, preferably more than 50nm, and more preferably in the range of more than 80nm. If it is less than this range, the crystallinity is reduced, and it is possible to increase the initial irreversible capacity.
[0932] (2) Ash content
[0933] The ash content contained in the raw material before heat treatment is usually below 1 mass % relative to the gross mass of the raw material before heat treatment, preferably below 0.5 mass %, particularly preferably below 0.1 mass %, and its lower limit is usually more than 1ppm. If it exceeds the above range, the deterioration of battery performance caused by the reaction with the electrolyte during charge and discharge cannot be ignored. If it is lower than the scope, then long time and energy and the equipment for preventing pollution are needed in manufacturing, and sometimes cost can rise.
[0934] (3) Volume-based average particle size
[0935] The volume reference average particle size of the raw material before heat treatment is the average particle size (median particle size) of the volume reference sought to by laser diffraction / scattering method, usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, further preferably 7 μm or more. In addition, its upper limit is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less, further preferably 25 μm or less. If it is less than the above range, the irreversible capacity increases, sometimes resulting in a loss of initial battery capacity. In addition, if it exceeds the above range, when the electrode pad is made, it is easy to form an uneven coating surface, which is sometimes not preferred in the battery manufacturing process.
[0936] (4) Raman R value, Raman half-value width
[0937] The R value of the raw material before the heat treatment measured using argon ion laser Raman spectroscopy is usually more than 0.10, preferably more than 0.15, more preferably more than 0.17, more preferably more than 0.2, and its upper limit is usually less than 0.8, preferably less than 0.6, more preferably less than 0.4 scope.If the R value is lower than the scope, it is possible not to carry out the spheroidization of particle, it is possible not to obtain the effect of fillability improvement.On the other hand, if it exceeds the scope, the crystallinity of particle surface is reduced, and the reactivity with electrolyte increases, sometimes resulting in efficiency reduction or the increase of generated gas.
[0938] In addition, the raw material before heat treatment is at 1580cm -1 There is no particular limit on the Raman half-value width near 10 cm, but it is usually 10 cm -1 Above, preferably 15cm -1 Above, the upper limit is usually 80cm -1 Below, preferably 60cm -1 Below, more preferably 45cm -1 Below, more preferably 40cm -1 If the Raman half-value width is below this range, the particles may not be sphericalized, and the effect of improving the filling capacity may not be achieved. On the other hand, if it is above this range, the crystallinity of the particle surface is reduced, and the reactivity with the electrolyte is increased, which may sometimes lead to reduced efficiency or increased gas generation.
[0939] (5) BET specific surface area
[0940] The specific surface area of the raw material before heat treatment measured by the BET method is usually 0.1 m 2 / g or more, preferably 0.7m 2 / g or more, more preferably 1m 2 / g or more, more preferably 1.5m 2 / g or more. Its upper limit is usually 100m 2 / g or less, preferably 50m 2 / g or less, more preferably 15m 2 / g or less, more preferably 10m 2 / g or less. If the specific surface area value is below the above range, when used as a negative electrode material, the lithium acceptance deteriorates during charging, and lithium is easily deposited on the electrode surface. On the other hand, if it exceeds the above range, the specific surface area is reduced by heat treatment, and more reactions with the electrolyte occur than necessary, resulting in increased gas generation, which sometimes makes it difficult to obtain an optimal battery.
[0941] (6) Micropore distribution
[0942] The amount of the voids in the particles with a diameter of 0.01 μm to 1 μm, and the concave-convex amount caused by the unevenness of the particle surface, of the raw material before the heat treatment obtained by the mercury porosimeter (mercury intrusion method) is usually 0.01 mL / g or more, preferably 0.05 mL / g or more, more preferably 0.1 mL / g or more, and its upper limit is usually 0.6 mL / g or less, preferably 0.4 mL / g or less, more preferably 0.3 mL / g or less. If it exceeds this range, a large amount of adhesive is needed when manufacturing the pole plate. On the other hand, if it is lower than this range, the high current density charge and discharge characteristics are reduced, and sometimes the relaxation effect of the electrode expansion and contraction during charge and discharge cannot be obtained.
[0943] In addition, total micropore volume is preferably more than 0.1mL / g, more preferably more than 0.25mL / g, and its upper limit is usually below 10mL / g, preferably below 5mL / g, more preferably below 2mL / g scope.If it exceeds this scope, then when making substrate, sometimes need a large amount of adhesives.If it is lower than this scope, then when making pole plate, sometimes can not obtain the dispersion effect of thickener or binding agent.
[0944] In addition, the average pore diameter is preferably 0.05 μm or more, more preferably 0.1 μ...
Claims
1. A lithium secondary battery, comprising at least: an electrode group formed by sandwiching a microporous membrane separator between a positive electrode and a negative electrode, and a non-aqueous electrolyte solution containing a lithium salt in a non-aqueous solvent, and the two are placed in a battery case, wherein: The positive electrode and the negative electrode respectively form active material layers on the current collector, and the active material layers contain active materials capable of absorbing and releasing lithium ions; The non-aqueous electrolyte contains difluorophosphate, and the content of the difluorophosphate in the entire non-aqueous electrolyte is 10 ppm or more. Furthermore, the non-aqueous solvent constituting the non-aqueous electrolyte contains at least one type of chain carboxylic acid ester.
2. The lithium secondary battery according to claim 1, wherein The non-aqueous electrolyte contains 0.01 mass % to 5 mass % of difluorophosphate.
3. The lithium secondary battery according to claim 1 or 2, wherein: The chain carboxylic acid ester constituting the non-aqueous electrolyte is at least one selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate, and ethyl propionate.
4. The lithium secondary battery according to claim 1 or 2, wherein: The nonaqueous solvent constituting the nonaqueous electrolyte is a mixed solvent of the chain carboxylate ester and a nonaqueous solvent other than the chain carboxylate ester, and the content ratio of the chain carboxylate ester in the entire nonaqueous solvent is 3 volume % to 50 volume %.
5. The lithium secondary battery according to claim 1 or 2, wherein: The nonaqueous solvent constituting the nonaqueous electrolyte contains the chain carboxylic acid ester and at least one cyclic carbonate ester.
6. The lithium secondary battery according to claim 1 or 2, wherein: The secondary battery has any property selected from the following (1) to (3): (1) The total area of the positive electrodes is 20 times or more relative to the surface area of the secondary battery casing; (2) The DC resistance component of the secondary battery is less than 20 milliohms (mΩ); (3) The battery element contained in one battery casing of the secondary battery has a capacity of 3 ampere hours (Ah) or more.
7. A non-aqueous electrolyte for a secondary battery, which is a non-aqueous electrolyte for a secondary battery formed by at least containing a non-aqueous solvent and a lithium salt, wherein: The non-aqueous electrolyte contains difluorophosphate, and the content of the difluorophosphate in the entire non-aqueous electrolyte is 10 ppm or more. Furthermore, the non-aqueous solvent constituting the non-aqueous electrolyte contains at least one type of chain carboxylic acid ester.
8. The non-aqueous electrolyte for a secondary battery according to claim 7, wherein The non-aqueous electrolyte contains 0.01 mass % to 5 mass % of difluorophosphate.
9. The non-aqueous electrolyte for secondary battery according to claim 7 or 8, wherein The chain carboxylic acid ester constituting the non-aqueous electrolyte is at least one selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate, and ethyl propionate.
10. A non-aqueous electrolyte for a secondary battery, the electrolyte comprising at least a non-aqueous solvent and a lithium salt, wherein: The non-aqueous electrolyte further contains difluorophosphate; The non-aqueous solvent is a mixed solvent containing at least ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate; The non-aqueous electrolyte may also contain one or more compounds selected from LiN(CF3SO2)2, lithium di(oxalato)borate, vinylene carbonate, 1,3-propane sultone, fluoroethylene carbonate, and cyclohexylbenzene.
Citation Information
Patent Citations
Lithium secondary cell and nonaqueous electrolytic solution for use therein
CN113571772A
Electrode material
JP1986168512A
Lithium secondary battery
JP1991055770A
Lithium secondary battery and manufacture of its negative electrode
JP1994275263A
Lithium storage battery with carbon anode
JP1996045545A